Articles comprising combinations of polymer aerogels and melamino-formaldehyde foams, and related systems and methods
By forming a polymer gel in the outer border of melamine formaldehyde foam, combining the advantages of the two to create a combination of gas gel/foam material, solving the problem of difficulty combining high mechanical properties and low thermal guidance in existing technologies, realized it, and achieved it. Suitable for material characteristics of a variety of applications.
Patent Information
- Application Number
- CN202380046574.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-15
- Filing Date
- 2023-04-13
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art has difficulty in effectively combining the material properties of polymer aerogels and melamine formaldehyde foams, resulting in the inability to meet the needs of high mechanical properties and low thermal conductivity in some applications.
The aerogel/foam combination is created by forming a polymer aerogel within the outer boundaries of melamine-formaldehyde foam, combining the best of both worlds. The combination works by contacting the polymeric airgel precursor with the melamine formaldehyde foam, allowing the airgel precursor to penetrate and form an aerogel within the outer boundary of the foam.
The high mechanical properties and low thermal conductivity of gas gel/foam material combination are realized, and it is suitable for the fields of aircraft internal parts, automotive insulation materials, electric vehicle battery pack insulation materials, bulletproof shield materials and other fields.
Smart Images

Figure CN119365523A_ABST
Abstract
Description
[0001] Related Applications
[0002] This application claims priority under 35 U.S.C. §119(e) to U.S. Provisional Patent Application No. 63 / 331,718, filed on April 15, 2022, and entitled “Articles Comprising a Combination of Polymer Aerogel and Melamine Formaldehyde Foam, and Related Systems and Methods,” and to U.S. Provisional Patent Application No. 63 / 331,750, filed on April 15, 2022, and entitled “Articles Comprising a Combination of Polymer Aerogel and Melamine Formaldehyde Foam, and Related Systems and Methods,” which applications are incorporated herein by reference in their entirety for all purposes. Technical Field
[0003] Articles of manufacture comprising a combination of polymer aerogel and melamine formaldehyde foam and related systems and methods are generally described. Summary of the invention
[0004] The present disclosure relates to articles comprising a combination of polymer aerogel and melamine formaldehyde foam and related systems and methods. In some cases, the subject matter of the present disclosure relates to interrelated products, alternative solutions to a particular problem, and / or multiple different uses of one or more systems and / or articles.
[0005] In certain embodiments, a material combination is provided. In some embodiments, the material combination comprises a melamine formaldehyde foam including an outer boundary; and a polyimide aerogel at least partially located within the outer boundary of the melamine formaldehyde foam.
[0006] In some embodiments, the combination of materials comprises a melamine formaldehyde foam including an outer boundary; and a polymer aerogel at least partially located within the outer boundary of the melamine formaldehyde foam.
[0007] Certain aspects relate to methods. In some embodiments, the method includes establishing contact between melamine formaldehyde foam and a liquid comprising a polyimide aerogel precursor such that the polyimide aerogel precursor penetrates an outer boundary of the melamine formaldehyde foam; and forming a polyimide aerogel from the polyimide aerogel precursor such that the polyimide aerogel is present within the outer boundary of the melamine formaldehyde foam.
[0008] In certain embodiments, the method includes establishing contact between melamine formaldehyde foam and a liquid containing a polymer aerogel precursor such that the polymer aerogel precursor penetrates an outer boundary of the melamine formaldehyde foam; and forming a polymer aerogel from the polymer aerogel precursor such that the polymer aerogel is present within the outer boundary of the melamine formaldehyde foam.
[0009] Other advantages and novel features of the present disclosure will become apparent from the following detailed description of various non-limiting embodiments of the present disclosure when considered in conjunction with the accompanying drawings. In the event that this specification and the documents incorporated by reference contain conflicting and / or inconsistent disclosures, this specification shall prevail. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Non-limiting embodiments of the present disclosure will be described by way of example with reference to the accompanying drawings, which are schematic and not drawn to scale unless otherwise indicated. In the drawings, each identical or nearly identical component shown is typically represented by a single numeral. For clarity, not every component is labeled in every drawing, nor is every component illustrated for every embodiment of the present disclosure, where such display is not necessary for one of ordinary skill in the art to understand the present disclosure. In the drawings:
[0011] Figure 1 Melamine formaldehyde foam according to certain embodiments is depicted.
[0012] FIG. 2A to FIG. 2B Depicted are material combinations comprising aerogel and melamine formaldehyde foam, according to certain embodiments.
[0013] Figure 3A Depicted are hydrophobic polyimide portions according to certain embodiments.
[0014] Figure 3B Depicted according to some embodiments Figure 3A Magnified view of the hydrophobic polyimide portion of the PDMS probe. Figure 3A To the left of the section in the zoomed view Figure 3B The top of the Figure 3A to the right of the section in the Figure 3B The bottom is shown.
[0015] Figure 4 Depicted are the molecular structures of several monomers according to certain embodiments.
[0016] Figure 5A Depicted are a foam / aerogel material combination with a water droplet on an exterior surface of the material combination, and the contact angle between the water droplet and the surface of the material combination, according to certain embodiments.
[0017] Figure 5B Depicted are a foam / aerogel material combination (left), submerged in liquid water, the material combination after holding the material combination underwater under a mesh (center), and the material combination after being submerged in liquid water (right), according to certain embodiments.
[0018] Figure 6Depicted is an apparatus used to measure thermal conductivity according to the calibrated hot plate (CHP) method described herein, according to certain embodiments.
[0019] Figure 7 Depicted is an apparatus used to measure flexural strength and modulus of a material according to ASTM D790-10 as described herein, according to certain embodiments.
[0020] Figure 8 Aerogels comprising particulate material, according to certain embodiments, are depicted.
[0021] Fig. 9 Depicted are a foam / aerogel material combination before exposure to elevated temperature (left), during exposure to elevated temperature (center), and after exposure to elevated temperature (right), according to certain embodiments.
[0022] FIG. 10A to FIG. 10B An apparatus for measuring dust shedding of a material combination as described herein in extended and retracted positions is shown, according to certain embodiments.
[0023] Fig.11 Depicted are foam / aerogel material combinations and their radii of curvature, according to certain embodiments.
[0024] Fig. 12A Depicted is a foam / aerogel material combination according to certain embodiments, with a facing material covering the entire outer surface of the material combination.
[0025] Fig. 12B Depicted is a foam / aerogel material combination having a facing material covering a portion of an outer surface of the material combination, according to certain embodiments.
[0026] Fig. 12C Depicted is a foam / aerogel material combination having an adhesive material located on an outer surface of the material combination, according to certain embodiments.
[0027] Fig.12D Depicted is a foam / aerogel material combination having an adhesive located on the exterior of the material combination and a facing material located over the adhesive, according to certain embodiments.
[0028] Fig.12E Depicted is a foam / aerogel material combination adhered to another foam / aerogel material combination, according to some embodiments.
[0029] Fig.13 Depicted are garments comprising a foam / aerogel material combination according to certain embodiments.
[0030] Fig.14 Shoes incorporating a foam / aerogel material combination are depicted in accordance with certain embodiments.
[0031] Fig.15A Depicted is a foam / aerogel material combination between individual battery cells, according to certain embodiments.
[0032] Fig. 15B Depicted is a foam / aerogel material combination surrounding a plurality of battery cells, according to certain embodiments.
[0033] Fig.16 Depicted is a melamine formaldehyde foam contacting an aerogel precursor and the precursor located in at least one pore of the melamine formaldehyde foam, according to certain embodiments.
[0034] Fig.17 Depicted is a melamine formaldehyde foam contacting a vapor containing a hydrophobe, according to certain embodiments.
[0035] Fig.18 Depicted are melamine formaldehyde foam before mechanical or thermal processing (left), melamine formaldehyde foam while undergoing mechanical and thermal processing (center), and melamine formaldehyde foam after undergoing mechanical or thermal processing (right), according to certain embodiments.
[0036] Fig.19A Depicted is pouring an aerogel precursor onto melamine formaldehyde foam according to certain embodiments.
[0037] Fig.19B Depicted is spraying an aerogel precursor onto melamine formaldehyde foam according to certain embodiments.
[0038] Fig.19C Depicted is the injection of an aerogel precursor into melamine formaldehyde foam according to certain embodiments.
[0039] Fig.19D Depicted is a melamine formaldehyde foam immersed in an aerogel precursor, according to certain embodiments.
[0040] Fig. 20A Depicted is melamine formaldehyde foam passing through a bath of aerogel precursor according to certain embodiments.
[0041] Fig. 20B Depicted is a melamine formaldehyde foam being compressed while in contact with an aerogel precursor and re-expanding while still in contact with the aerogel precursor, according to certain embodiments.
[0042] Fig.21 Depicted is a foam / gel material combination immersed in a bath of a transfer solvent, wherein the transfer solvent continuously replaces liquid in the pores of the material combination, according to certain embodiments.
[0043] FIG. 22A to FIG. 22Fis a schematic diagram of volumes showing interior percentages of those volumes according to certain embodiments.
[0044] Fig.23 2 is a pair of SEM images of a foam / aerogel material combination of sample number 2 of Example 1 according to certain embodiments, showing both the nanostructure phase and the macrostructure phase of the material combination. The left image shows the pores of melamine formaldehyde foam and solid skeleton melamine formaldehyde material. Inside these pores, it can be seen that the polyimide aerogel is not attached to the melamine formaldehyde skeleton in some cases and is attached to the melamine formaldehyde skeleton in some cases. The right image is an enlarged (120,000x) image of the polyimide aerogel of the left image (2000x magnification), showing the aerogel nanoporous structure within the foam pores.
[0045] Fig.24 According to certain embodiments, the nitrogen adsorption isotherm (left) and the plot of pore volume versus pore width (right) for the foam / aerogel material combination of Sample 2 of Example 1. These graphs summarize the nanostructure and nanoporosity of the aerogel in the foam / aerogel material combination.
[0046] FIG. 25A to FIG. 25C are stress-strain curves for three different foam / aerogel material combinations according to certain embodiments. Fig.25A is the stress-strain curve of sample 1 of Example 1. Fig.25B is the stress-strain curve of sample 3 of Example 1. Fig.25C is the stress-strain curve of sample 5 of Example 1. DETAILED DESCRIPTION
[0047] Articles comprising a combination of a polymer aerogel and a melamine formaldehyde foam and related systems and methods are generally described. The melamine formaldehyde foam can be combined (e.g., injected) with a polymer aerogel or a polymer aerogel precursor to produce a material combination comprising a foam and a polymer aerogel. Such a material combination comprises an aerogel (e.g., a polymer aerogel such as a polyimide aerogel) and a foam (e.g., a melamine formaldehyde foam), wherein the aerogel is at least partially located within the outer boundary of the foam, and is also referred to herein as an "aerogel / foam material combination".
[0048] In certain embodiments, the aerogel / foam material combination comprises a polyimide aerogel combined with a melamine formaldehyde foam, and according to certain embodiments, such a combination can provide many advantages. However, it should be understood that the disclosure is not limited thereto, and other aerogel / foam material combinations are also available. Therefore, the aerogel / foam material combinations described herein include combinations comprising other types of aerogels (e.g., other types of polymer aerogels, such as other types of organic polymer aerogels) and / or other types of foams.
[0049] Material combinations comprising polymer aerogel and melamine formaldehyde foam (e.g., melamine formaldehyde foam infused with polymer aerogel) can potentially combine many of the following valuable material properties into a single material package: for example, high mass normalized strength and stiffness properties, low density, low and constant dielectric constant and loss tangent over a wide frequency range, low sound velocity, high sound transmission loss, low flammability or non-flammability, machinability, and low thermal conductivity. Potential applications of aerogel / foam material combinations (such as aerogel / foam material combinations comprising polymer aerogel and melamine formaldehyde foam) include aircraft interior parts such as wall panels, floors, cockpit doors, and kitchen furniture; insulation materials for automobile engine hoods or body frames; insulation materials for electric vehicle battery packs; shock wave reflection and / or energy absorption materials in ballistic shields; insulation components for shoes, boots, and insoles; shock absorption and sound insulation materials for rocket fairings; low-k substrates for applications such as electronic products and antennas. For example, FIG. 15A to FIG. 15B The foam / aerogel material combination 1503 is schematically shown adjacent to the battery 1545. Fig.15A In the embodiment, the aerogel / foam material combination 1503 is positioned between the battery cells. In particular, the aerogel / foam material combination 1503 is arranged to form a matrix of compartments in which the battery cells are positioned. Fig. 15B In , an aerogel / foam material combination is used to form the outer walls of the compartment containing the battery cell 1545. Combinations of these arrangements are also possible.
[0050] Aerogels are different types of low-density solid materials composed of porous three-dimensional solid phase networks. Aerogels generally exhibit a variety of desirable material properties, including high specific surface area, low bulk density, high specific strength and stiffness, low thermal conductivity and / or low dielectric constant.
[0051] In some embodiments, the aerogel comprises a polymer aerogel. A polymer aerogel is an aerogel made at least in part of a polymer material. In some embodiments, it may be particularly advantageous to use an aerogel comprising a relatively large amount of polymer material. Therefore, in some embodiments, at least 25wt%, at least 50wt%, at least 75wt%, at least 90wt%, at least 95wt%, at least 98wt%, at least 99wt%, at least 99.9wt% or all of the aerogel in the aerogel / foam material combination is composed of a polymer material. In some embodiments, at least 25wt%, at least 50wt%, at least 75wt%, at least 90wt%, at least 95wt%, at least 98wt%, at least 99wt%, at least 99.9wt% or all of the aerogel in the aerogel / foam material combination is composed of an organic polymer (i.e., a polymer having carbon atoms in its backbone). In some embodiments, it may be particularly advantageous to use a polymer aerogel in which at least 75 atomic percent (at%) (or at least 85 at%, at least 95 at%, at least 99 at%, at least 99.9 at% or more) of the aerogel material is a polymer material comprising covalently bonded carbon in its backbone and in which at least 75 at% of the backbone atoms are carbon, nitrogen, oxygen, phosphorus or sulfur. Examples of organic polymers that can be used as all or part of the aerogel component of the aerogel / foam material combination include, but are not limited to, polyamides, polyimides, polyureas, polyurethanes, polybenzoxazines, polycyclopentadienes, polyolefins, polynorbornenes, and biopolymers.
[0052] According to certain embodiments, polymer aerogels can provide aerogel-infused foams having desirable properties when combined with melamine formaldehyde foams.Polymer aerogel systems particularly suitable for use in combination with melamine formaldehyde foam materials include polyimides and polyisocyanates (eg, polyureas and polyamides).
[0053] In some cases, the combination of melamine formaldehyde foam and polyimide aerogel results in particularly advantageous properties. The inventors have observed unexpected results: combining melamine formaldehyde foam with polyimide aerogel (e.g., by any of the various methods described herein) results in improved thermal and / or mechanical properties compared to either material measured alone. This result is more pronounced in the polyimide aerogel / melamine formaldehyde foam combination than in other aerogel-infused foams. The inventors have also observed an unexpected increase in the thermal stability of the polyurea aerogel / foam material combination while maintaining hydrophobicity and advantageous mechanical properties.
[0054] In some embodiments, a material combination is provided that includes melamine formaldehyde foam and a polymer aerogel at least partially located within the outer boundary of the melamine formaldehyde foam. By way of illustration and not limitation, Figure 11 is a schematic diagram of a foam 100. The foam 100 is porous and includes a solid foam material 101 in which a plurality of pores 102 are arranged. Aerogel or aerogel precursor can be introduced into the pores of the foam (e.g., by filling, injecting or any other form of penetration into the open cells of the foam) and processed to form a material combination of foam and aerogel. For example, Figure 2A As schematically shown in FIG. 1 , an aerogel precursor is introduced into pores 102A (and other pores) of foam 100 and processed to form aerogel 103 within pores 102A (and likewise other pores of the foam). Thus, Figure 2A The schematic diagram in FIG. 1 is an example of an aerogel / foam material combination 104 .
[0055] Figure 2B yes Figure 2A Schematic diagram of an aerogel / foam material combination, wherein enlarged views 200A and 200B of the aerogel component are shown. As shown in views 200A and 200B, the aerogel 103 includes a solid aerogel material 201 in which a plurality of pores 202 are arranged. When arranged in this manner, the foam can form a relatively large foam domain with relatively large pores, wherein the relatively large pores are at least partially occupied by smaller aerogel subdomains with smaller pores. In some embodiments, the smaller aerogel subdomains are connected to each other so that they together form a larger continuous aerogel domain.
[0056] As described above, according to certain embodiments, an aerogel / foam material combination can be made by injecting or otherwise combining an aerogel precursor into a foam. For example, some embodiments include combining an aerogel precursor with a foam, optionally gelling the precursor to form a gel at least partially within the pores of the foam, and forming an aerogel from the gel (e.g., by removing a liquid from the gel) to form an aerogel / foam material combination. Various methods of forming an aerogel / foam material combination will be described below and elsewhere herein. Similarly, various methods of forming precursors of such combinations (e.g., a combination of a gel precursor and a foam, a combination of a gel and a foam, etc.) are described below.
[0057] A gel is a colloidal system in which a porous solid network spans the volume occupied by a liquid medium. Thus, a gel has two components: a sponge-like solid skeleton (which gives the gel its solid-like cohesive properties) and a liquid that permeates the pores of this skeleton.
[0058] Certain aspects relate to methods of forming aerogels, gels, combinations of materials (eg, a combination of gel and foam, a combination of aerogel and foam), and / or precursors thereof.
[0059] In some embodiments, a method of producing an aerogel / foam material combination comprising a polymer aerogel (e.g., a polyimide aerogel) and melamine formaldehyde foam is provided. In some embodiments, contact is established between the melamine formaldehyde foam and a liquid comprising a polymer aerogel precursor such that the polymer aerogel precursor penetrates the outer boundary of the melamine formaldehyde foam.
[0060] The polymer aerogel precursor may be present in a liquid in any of a variety of suitable forms. In some embodiments, the liquid is a carrier liquid, and the prepolymer (e.g., monomer, short-chain polymer, etc.) may be dissolved, suspended, or otherwise carried in the carrier liquid. In some embodiments, the combination of the liquid and the prepolymer may be gelled (e.g., such that the prepolymer is polymerized and / or cross-linked), optionally in the presence of a catalyst, such that in the formed gel, the carrier liquid is present in the pores of the polymerized and / or cross-linked prepolymer. In some embodiments, the carrier liquid may first be exchanged with another carrier liquid, and then gelling may be performed such that the second carrier liquid is present in the pores of the polymerized and / or cross-linked prepolymer.
[0061] The contact between the foam and the liquid can be achieved using any of a variety of suitable methods. In some embodiments, a liquid comprising a polymer aerogel precursor is contacted with the melamine formaldehyde foam. In some embodiments, the liquid can be added to the foam, for example, by pouring the liquid onto the foam, spraying the liquid onto the foam, or otherwise adding the liquid to the foam. By way of illustration and not limitation, Fig.16 An example of this process is shown schematically. Fig.16 In the embodiment, conduit 1646 dispenses liquid 1647 (comprising a polymer aerogel precursor) onto foam 1601. Fig.16 In the process, liquid 1647 penetrates into pores 1648 of foam 1601.
[0062] In some embodiments, the melamine formaldehyde foam is contacted with a liquid comprising a polymer aerogel precursor. In some embodiments, the foam can be added to the liquid by immersing the foam in the liquid, contacting the foam with the liquid so that the liquid penetrates the pores of the foam by capillary action, or otherwise contacting the foam with the liquid. Fig.19A In, liquid 1947 is poured onto foam 1901. Fig.19B In the process, liquid 1947 is sprayed on foam 1901. Fig.19C In the process, liquid 1947 is injected into foam 1901. Fig.19D In the embodiment of the present invention, foam 1901 is immersed in a bath of liquid 1947. Of course, other techniques for contacting the liquid (including the aerogel precursor) with the foam are also possible, as the present disclosure is not limited thereto.
[0063] In certain embodiments, the polymer aerogel is formed from a polymer aerogel precursor such that the polymer aerogel resides within an outer boundary of the melamine formaldehyde foam.
[0064] Various embodiments are described in which the aerogel is located within a foam body. Such an arrangement can be achieved, for example, by combining an aerogel precursor with a foam such that the aerogel precursor is located within the foam body (eg, via infusion, injection, or other means) and forms an aerogel within the foam body.
[0065] In some embodiments, the aerogel precursor, gel and / or aerogel is present within the inner 90%, inner 75%, inner 50%, inner 25%, inner 15%, inner 10%, inner 5%, or inner 2% of the foam. The "inner 90%" of the foam represents a subvolume of the foam consisting of all points occupied by all line segments starting from the geometric center of the foam and extending to 90% of the distance of the outer boundary line trace of the foam. Similarly, the "inner 20%" of the foam represents a subvolume of the foam consisting of all points occupied by all line segments starting from the geometric center of the foam and extending to 20% of the distance of the outer boundary line trace of the foam. Such a subvolume of the foam will have the same shape as the overall foam, but with a smaller size. FIG. 22A to FIG. 22C An example of such sub-volumes is shown, each showing a view of a volume 2200 (eg, foam). Fig.22A is a side view of volume 2200, Fig. 22B is a perspective view of volume 2200, and Fig. 22C is a front view of volume 2200. The "inner 90 vol%" of volume 2200 corresponds to subvolume 2210 because subvolume 2210 consists of all points on geometric center 2220 of volume 2200, line segment 2230 (extending from geometric center 2220 to 90% of the distance along the trace of line segment 2240, which is the shortest distance from geometric center 2220 to outer boundary 2250 of volume 2200), and all other points on all other line segments extending from geometric center 2220 to 90% of the distance along the trace of outer boundary 2250 of volume 2200. FIG. 22D to FIG. 22F A similar illustration is provided, where subvolume 2210 is the inner 20 vol % of volume 2200 .
[0066] In some embodiments, after the aerogel precursor and foam are combined, at least 20 vol%, at least 30 vol%, at least 40 vol%, at least 50 vol%, at least 60 vol%, at least 70 vol%, at least 80 vol%, at least 90 vol%, at least 95 vol%, at least 98 vol%, at least 99 vol%, at least 99.9 vol%, or more of the pore volume of the foam is occupied by the aerogel precursor.
[0067] In some embodiments, establishing contact between the melamine formaldehyde foam and the liquid comprising a polymer aerogel precursor comprises spraying the liquid comprising a polymer aerogel precursor onto the melamine formaldehyde foam. In some embodiments, the liquid comprising a polymer aerogel precursor is sprayed onto the entire surface of the melamine formaldehyde foam. In some embodiments, the liquid comprising a polymer aerogel precursor is sprayed onto a portion of the surface of the melamine formaldehyde foam. In some embodiments, the liquid comprising a polymer aerogel precursor is sprayed onto the melamine formaldehyde foam in a continuous manner. In some embodiments, the liquid comprising a polymer aerogel precursor is sprayed onto the melamine formaldehyde foam in a discontinuous manner. In some embodiments, an amount of the liquid comprising a polymer aerogel precursor is sprayed onto the melamine formaldehyde foam such that the void space within the outer boundary of the melamine formaldehyde foam is partially filled with the liquid comprising a polymer aerogel precursor. In some embodiments, an amount of liquid comprising a polymer aerogel precursor is sprayed onto the melamine formaldehyde foam such that substantially all (e.g., at least 90%, at least 95%, at least 99%, or 100%) of the void space within the outer boundary of the melamine formaldehyde foam is filled with the liquid comprising a polymer aerogel precursor. In some embodiments, the liquid comprising a polymer aerogel precursor is sprayed onto the melamine formaldehyde foam such that a major portion of the void space within the outer boundary of the melamine formaldehyde foam is filled with the liquid comprising a polymer aerogel precursor.
[0068] In some embodiments, establishing contact between the melamine formaldehyde foam and the liquid comprising a polymer aerogel precursor comprises pouring the liquid comprising a polymer aerogel precursor onto the melamine formaldehyde foam. In some embodiments, the liquid comprising a polymer aerogel precursor is poured onto the entire surface of the melamine formaldehyde foam. In some embodiments, the liquid comprising a polymer aerogel precursor is poured onto a portion of the surface of the melamine formaldehyde foam. In some embodiments, the liquid comprising a polymer aerogel precursor is poured onto the melamine formaldehyde foam in a continuous manner. In some embodiments, the liquid comprising a polymer aerogel precursor is poured onto the melamine formaldehyde foam in a discontinuous manner. In some embodiments, an amount of the liquid comprising a polymer aerogel precursor is poured onto the melamine formaldehyde foam such that the void space within the outer boundary of the melamine formaldehyde foam is partially filled with the liquid comprising a polymer aerogel precursor. In some embodiments, an amount of liquid comprising a polymer aerogel precursor is poured onto the melamine formaldehyde foam such that substantially all (e.g., at least 90%, at least 95%, at least 99%, or 100%) of the void space within the outer boundary of the melamine formaldehyde foam is filled with the liquid comprising a polymer aerogel precursor. In some embodiments, the liquid comprising a polymer aerogel precursor is poured onto the melamine formaldehyde foam such that a major portion of the void space within the outer boundary of the melamine formaldehyde foam is filled with the liquid comprising a polymer aerogel precursor.
[0069] In some embodiments, establishing contact between the melamine formaldehyde foam and the liquid containing the polymer aerogel precursor comprises injecting the liquid containing the polymer aerogel precursor into the melamine formaldehyde foam. In some embodiments, the liquid containing the polymer aerogel precursor is injected into the melamine formaldehyde foam through one surface of the melamine formaldehyde foam. In some embodiments, the liquid containing the polymer aerogel precursor is injected into the melamine formaldehyde foam through more than one point on the same surface of the melamine formaldehyde foam. In some embodiments, the liquid containing the polymer aerogel precursor is injected into the melamine formaldehyde foam through more than one point on different surfaces of the melamine formaldehyde foam. In some embodiments, the liquid containing the polymer aerogel precursor is injected into the melamine formaldehyde foam in a continuous manner. In some embodiments, the liquid containing the polymer aerogel precursor is injected into the melamine formaldehyde foam in a discontinuous manner. In some embodiments, an amount of the liquid containing the polymer aerogel precursor is injected into the melamine formaldehyde foam such that the void space within the outer boundary of the melamine formaldehyde foam is partially filled with the polymer aerogel precursor. In some embodiments, an amount of liquid comprising a polymer aerogel precursor is injected into the melamine formaldehyde foam such that substantially all (e.g., at least 90%, at least 95%, at least 99%, or 100%) of the void space within the outer boundary of the melamine formaldehyde foam is filled with the liquid comprising a polymer aerogel precursor. In some embodiments, the liquid comprising a polymer aerogel precursor is injected into the melamine formaldehyde foam such that a major portion of the void space within the outer boundary of the melamine formaldehyde foam is filled with the liquid comprising a polymer aerogel precursor.
[0070] In some embodiments, establishing contact between the melamine formaldehyde foam and the liquid comprising a polymer aerogel precursor comprises immersing the melamine formaldehyde foam in the liquid comprising a polymer aerogel precursor. In some embodiments, the melamine formaldehyde foam is partially immersed in the liquid comprising a polymer aerogel precursor. In some embodiments, the melamine formaldehyde foam is completely immersed in the liquid comprising a polymer aerogel precursor. In some embodiments, the melamine formaldehyde foam is immersed in the liquid comprising a polymer aerogel precursor so that a major portion of the void space within the outer boundary of the melamine formaldehyde foam is filled with the liquid comprising a polymer aerogel precursor. In some embodiments, the melamine formaldehyde foam is immersed in the liquid comprising a polymer aerogel precursor for a period of time to allow the polymer aerogel precursor in the void space within the outer boundary of the melamine formaldehyde foam to gel.
[0071] In some embodiments, establishing contact between the melamine formaldehyde foam and the liquid comprising a polymer aerogel precursor comprises moving the melamine formaldehyde foam through a bath of the liquid comprising a polymer aerogel precursor such that the liquid comprising a polymer aerogel precursor is absorbed by the melamine formaldehyde foam. Fig. 20A An example of such an arrangement is shown, wherein contact is established between the melamine formaldehyde foam 2001 and the liquid containing a polymer aerogel precursor by moving the melamine formaldehyde foam 2001 in the direction of arrow 2002 and through a bath 2047 of liquid containing a polymer aerogel precursor, such that the liquid containing a polymer aerogel precursor is absorbed by the melamine formaldehyde foam. In some embodiments, the melamine formaldehyde foam is moved through the bath of liquid containing a polymer aerogel precursor in a continuous manner. In some embodiments, the melamine formaldehyde foam is moved through the bath of liquid containing a polymer aerogel precursor via a moving element (e.g., a conveyor belt). In some embodiments, the melamine formaldehyde foam is pushed through the bath of liquid containing a polymer aerogel precursor. In some embodiments, the melamine formaldehyde foam is fed through the bath of liquid containing a polymer aerogel precursor (e.g., via a powered roller). In some embodiments, the melamine formaldehyde foam is pulled through the bath of liquid containing a polymer aerogel precursor.
[0072] In some embodiments, the melamine formaldehyde foam is pulled through a bath of a liquid containing a polymer aerogel precursor in a continuous manner by sandwiching the melamine formaldehyde foam between layers of scrim material. In some embodiments, the scrim material is removed from the melamine formaldehyde foam after the polymer aerogel precursor is processed into a polymer aerogel. In some embodiments, the scrim material is removed from the melamine formaldehyde foam after the polymer aerogel precursor is processed into a polymer gel. In some embodiments, the scrim material is removed from the melamine formaldehyde foam while the polymer aerogel precursor is processed into a polymer aerogel. In some embodiments, the scrim material is not removed from the melamine formaldehyde foam before, during, or after processing the polymer aerogel precursor. In some embodiments, the scrim material is a fiber sheet. In some other embodiments, the scrim material is a mesh cloth. Without wishing to be bound by any particular theory, it is believed that pulling the melamine formaldehyde foam through a bath of liquid containing a polymer aerogel precursor prevents the foam from tearing, ripping, stretching or otherwise deforming by distributing the pulling forces across the scrim rather than exerting those forces on the foam itself.
[0073] In some embodiments, the melamine formaldehyde foam is moved through a bath of a liquid containing a polymer aerogel precursor and compressed while in contact with the liquid containing a polymer aerogel precursor such that the liquid containing a polymer aerogel precursor is drawn into the pores of the melamine formaldehyde foam as the foam is depressurized. Fig. 20BAn example of such an arrangement is shown, where foam 2001 moves through a bath 2047 of a polymer aerogel precursor in the direction of arrow 2002, such that the thickness of foam 2001 at position 2003 is thinner than the thickness of foam 2001 at position 2004. In some embodiments, the melamine formaldehyde foam is compressed between two rollers while in contact with a liquid comprising a polymer aerogel precursor. In some embodiments, the melamine formaldehyde foam is surface compressed while in contact with a liquid comprising a polymer aerogel precursor. In some embodiments, the melamine formaldehyde foam is compressed upon contact with a liquid comprising a polymer aerogel precursor to a thickness of less than or equal to 99%, less than or equal to 95%, less than or equal to 90%, less than or equal to 80%, less than or equal to 70%, less than or equal to 60%, less than or equal to 50%, less than or equal to 40%, less than or equal to 30%, less than or equal to 20%, less than or equal to 15%, less than or equal to 10%, less than or equal to 5%, less than or equal to 3%, less than or equal to 1% of the thickness of the foam just before compression (and / or, in some embodiments, to a thickness as small as 0.1%, as small as 0.01% or less). In some embodiments, the melamine formaldehyde foam is removed from the bath of the liquid comprising a polymer aerogel precursor after depressurization but before the polymer aerogel precursor forms a gel within the pores of the melamine formaldehyde foam. In some embodiments, after gel formation, at least 20 vol%, at least 30 vol%, at least 40 vol%, at least 50 vol%, at least 60 vol%, at least 70 vol%, at least 80 vol%, at least 90 vol%, at least 95 vol%, at least 98 vol%, at least 99 vol%, at least 99.9 vol% or more of the pore volume of the foam is occupied by gel. In some embodiments, the melamine formaldehyde foam is moved through a bath of liquid containing a polymer aerogel precursor via a moving element (e.g., a conveyor belt). In some embodiments, the melamine formaldehyde foam is fed through a bath of liquid containing a polymer aerogel precursor (e.g., via a series of powered rollers). In some embodiments, the melamine formaldehyde foam is pulled through a bath of liquid containing a polymer aerogel precursor.
[0074] In some embodiments, the melamine formaldehyde foam is contacted with a hydrophobe before the melamine formaldehyde foam contacts the liquid comprising the polyimide aerogel precursor. As used herein, a "hydrophobe" is a reactive chemical agent used to impart hydrophobicity to a material by changing the composition of functional groups on the surface of the material. A hydrophobe can improve the hydrophobicity of a material (e.g., a foam, such as an aerogel, or a material combination such as an aerogel and a foam). In some embodiments, the hydrophobe reacts with functional groups on the foam, functional groups on the aerogel, or functional groups on both the foam and the aerogel.
[0075] According to certain embodiments, the hydrophobe may react with the melamine formaldehyde foam, thereby imparting hydrophobic characteristics to the melamine formaldehyde foam. In some embodiments, the melamine formaldehyde foam is immersed in a liquid containing a hydrophobe before contacting the liquid containing the polyimide aerogel precursor. In some embodiments, the liquid containing the hydrophobe fills substantially all (e.g., at least 90%, at least 95%, at least 99% or 100%) of the void space within the outer boundary of the melamine formaldehyde foam. In some embodiments, the liquid containing the hydrophobe partially fills the void space within the outer boundary of the melamine formaldehyde foam. In some embodiments, only the outer surface of the outer boundary of the melamine formaldehyde foam is in contact with the hydrophobe. In some embodiments, the liquid containing the hydrophobe is sprayed onto the melamine formaldehyde foam before contacting the liquid containing the polyimide aerogel precursor. In some embodiments, the vapor containing the hydrophobe is blown onto the melamine formaldehyde foam before contacting the liquid containing the polyimide aerogel precursor. In some embodiments, the melamine formaldehyde foam is moved through a chamber having a vapor atmosphere containing a hydrophobe and then contacted with a liquid containing a polyimide aerogel precursor. In some embodiments, the melamine foam is contacted with the hydrophobe for a duration of greater than or equal to 1 second, greater than or equal to 3 seconds, greater than or equal to 5 seconds, greater than or equal to 10 seconds, greater than or equal to 30 seconds, greater than or equal to 1 minute, greater than or equal to 5 minutes, greater than or equal to 10 minutes, greater than or equal to 20 minutes, greater than or equal to 30 minutes, greater than or equal to 1 hour, greater than or equal to 2 hours, greater than or equal to 3 hours, greater than or equal to 6 hours, or greater than or equal to 12 hours (and / or, in some embodiments, up to 24 hours, up to 7 days, up to 30 days, or longer).
[0076] In some embodiments, the melamine formaldehyde foam is coated with a hydrophobe prior to contacting the polyimide aerogel precursor. In some embodiments, the melamine formaldehyde foam is reacted with a hydrophobe prior to contacting the polyimide aerogel precursor. In some embodiments, only a specific portion of the melamine formaldehyde foam is contacted with the hydrophobe. In some embodiments, the melamine formaldehyde foam is sprayed with a hydrophobe. In some embodiments, the melamine formaldehyde foam is immersed in a hydrophobe.
[0077] In some embodiments, the melamine formaldehyde foam is immersed in a liquid containing a hydrophobe. In some embodiments, the volume percentage of the hydrophobe in the liquid is less than or equal to 99.9%, less than or equal to 99.5%, less than or equal to 99%, less than or equal to 95%, less than or equal to 90%, less than or equal to 80%, less than or equal to 70%, less than or equal to 60%, less than or equal to 50%, less than or equal to 40%, less than or equal to 30%, less than or equal to 25%, less than or equal to 20%, less than or equal to 15%, less than or equal to 10%, less than or equal to 9%, less than or equal to 8% , less than or equal to 7%, less than or equal to 6%, less than or equal to 5%, less than or equal to 4%, less than or equal to 3%, less than or equal to 2%, less than or equal to 1%, less than or equal to 0.9%, less than or equal to 0.8%, less than or equal to 0.7%, less than or equal to 0.6%, less than or equal to 0.5%, less than or equal to 0.4%, or less than or equal to 0.3% (and / or, in some embodiments, as little as 0.2%, as little as 0.1%, as little as 0.05%, as little as 0.01%, or less). In certain embodiments, it may be advantageous to use a liquid that contains a hydrophobe in an amount of 0.01% to 0.5% or 0.1% to 0.5%.
[0078] In some embodiments, the melamine formaldehyde foam is dried by evaporation after contacting with the hydrophobe and before contacting with the polymer aerogel precursor. In some embodiments, the melamine formaldehyde foam is heated after contacting with the hydrophobe and before contacting with the polymer aerogel precursor to accelerate the drying of the foam. In some embodiments, the melamine formaldehyde foam is not dried after contacting with the hydrophobe and before contacting with the polymer aerogel precursor.
[0079] In some embodiments, the melamine formaldehyde foam is contacted with a hydrophobe after contacting the polymer aerogel precursor. In some embodiments, the melamine formaldehyde foam is contacted with a hydrophobe immediately after contacting the polymer aerogel precursor. In some embodiments, a portion of the melamine formaldehyde foam is contacted with a hydrophobe while a different portion of the same melamine formaldehyde foam is contacted with a polymer aerogel precursor.
[0080] In some embodiments, the gel / foam material combination is contacted with a hydrophobe. In some embodiments, the gel / foam material combination is immersed in a bath of a liquid containing a hydrophobe. In some embodiments, it may be particularly advantageous if the first bath of the transfer solvent also contains a hydrophobe. In some embodiments, the gel / foam material combination is contacted with the hydrophobe for a duration greater than or equal to 1 second, greater than or equal to 10 seconds, greater than or equal to 30 seconds, greater than or equal to 1 minute, greater than or equal to 5 minutes, greater than or equal to 10 minutes, greater than or equal to 20 minutes, greater than or equal to 30 minutes, greater than or equal to 45 minutes, greater than or equal to 1 hour, greater than or equal to 2 hours, greater than or equal to 3 hours, greater than or equal to 4 hours, greater than or equal to 5 hours, or greater than or equal to 6 hours (and / or, in some embodiments, up to 12 hours, up to 24 hours, up to 7 days, up to 30 days or more). In some embodiments, the gel / foam material combination is contacted with more than one hydrophobe.
[0081] In some embodiments, the aerogel / foam material combination is contacted with a hydrophobe. In some embodiments, the aerogel / foam material combination is contacted with the hydrophobe for a duration of greater than or equal to 1 second, greater than or equal to 10 seconds, greater than or equal to 30 seconds, greater than or equal to 1 minute, greater than or equal to 5 minutes, greater than or equal to 10 minutes, greater than or equal to 20 minutes, greater than or equal to 30 minutes, greater than or equal to 45 minutes, greater than or equal to 1 hour, greater than or equal to 2 hours, greater than or equal to 3 hours, greater than or equal to 4 hours, greater than or equal to 5 hours, or greater than or equal to 6 hours (and / or, in some embodiments, up to 12 hours, up to 24 hours, up to 7 days, up to 30 days or more). In some embodiments, the aerogel / foam material combination is contacted with more than one hydrophobe. In some embodiments, the aerogel / foam material combination is contacted with a liquid solution comprising a hydrophobe.
[0082] In some embodiments, the aerogel / foam material combination is contacted with a vapor containing a hydrophobe so that the exposed reactive sites on the melamine formaldehyde foam react with the hydrophobe. Fig.17In some embodiments, vapor 1749 contacts aerogel / foam material 1701 such that reaction sites 1704 and 1705 are exposed to vapor 1749. In some embodiments, the aerogel / foam material combination is contacted with the vapor containing a hydrophobe for a period of time greater than or equal to 1 second, greater than or equal to 10 seconds, greater than or equal to 30 seconds, greater than or equal to 1 minute, greater than or equal to 5 minutes, greater than or equal to 10 minutes, greater than or equal to 20 minutes, greater than or equal to 30 minutes, greater than or equal to 45 minutes, greater than or equal to 1 hour, greater than or equal to 2 hours, greater than or equal to 3 hours, greater than or equal to 4 hours, greater than or equal to 5 hours, or greater than or equal to 6 hours (and / or, in some embodiments, up to 12 hours, up to 24 hours, up to 7 days, up to 30 days, or more). In some embodiments, vapor containing a hydrophobe is blown onto the aerogel / foam material combination. In some embodiments, the aerogel / foam material combination is moved through a stagnant atmosphere of vapor containing a hydrophobe.
[0083] Any of a variety of hydrophobes can be used. In some embodiments, the hydrophobe includes hexamethyldisilazane, hexamethylenedisiloxane, dioctylamine, didodecylamine, hexylamine, dihexylamine, isocyanate, aldehyde, amine, alkylchlorosilane and / or a silane of formula HN(R 1 )(R 2 ), wherein: R 1 are each independently a first organic moiety; and R 2 are each independently H or a second organic moiety; provided that: neither the first nor the second organic moiety is H; and HR determined at about 25° C. and about 1 atm 1 and / or HR 2 The log P is not less than 1. In some embodiments, the HR determined at about 25° C. and about 1 atm 1 and HR 2 The log P is not less than 1. 1 or R 2 In some embodiments where neither is hydrogen, the HR determined at about 25° C. and about 1 atm 1 and HR 2 The log P of the hydrophobe is not less than 1. Without wishing to be bound by any particular theory, it is believed that the large hydrophobic groups on the hydrophobe can prevent water molecules from contacting the more hydrophilic portions of the polymer aerogel backbone (e.g., the polyimide aerogel backbone), thereby improving the overall hydrophobicity of the aerogel / foam material combination. In some embodiments, increasing the size of the hydrophobic functional groups on the hydrophobe increases the overall hydrophobicity of the material combination when compared to an aerogel / foam material combination contacted with a hydrophobe having smaller hydrophobic functional groups.
[0084] The "partition coefficient" (P) of a compound is the ratio of the concentration of the compound in a mixture of n-octan-1-ol and water at equilibrium. The "Log P" of a compound is the logarithm (Log) of the partition coefficient of the compound. The Log P of a compound is determined according to the following equation:
[0085] Log P = Log ((concentration of compound in n-octan-1-ol phase of mixture) / (concentration of compound in aqueous phase of mixture));
[0086] For example, when the compound is not ionized in n-octan-1-ol and water. Log P can be determined at about 25° C. and about 1 atm. Higher Log P values may indicate higher hydrophobicity. In some embodiments, the Log P of a hydrophobe may be greater than or equal to 1, greater than or equal to 1.5, greater than or equal to 2, greater than or equal to 2.5, greater than or equal to 3, greater than or equal to 3.5, or greater than or equal to 4 (and / or, in some embodiments, up to 5, up to 6, up to 8, up to 10 or more).
[0087] In some embodiments, after the aerogel / foam material combination is reacted with a suitable hydrophobe, the Log P of the aerogel / foam material combination increases. In some embodiments, after the aerogel / foam material combination is reacted with a suitable hydrophobe, the Log P of the aerogel / foam material combination after the reaction increases by greater than or equal to 0.5 points, greater than or equal to 1 point, greater than or equal to 1.5 points, greater than or equal to 2 points, greater than or equal to 2.5 points, or greater than or equal to 3 points. In some embodiments, the Log P of the aerogel / foam material combination after the reaction is greater than or equal to 1, greater than or equal to 2, greater than or equal to 2.5, greater than or equal to 3, greater than or equal to 3.5, or greater than or equal to 4 (and / or, in some embodiments, up to 5, up to 6, up to 8, up to 10 or more).
[0088] In some embodiments, the aerogel / foam material combinations described herein can have a Log P greater than or equal to 1, greater than or equal to 1.5, greater than or equal to 2, greater than or equal to 2.5, greater than or equal to 3, greater than or equal to 3.5, or greater than or equal to 4 (and / or, in some embodiments, up to 5, up to 6, up to 8, up to 10 or more).
[0089] In some embodiments, the melamine formaldehyde foam is formed from a precursor foam. In some embodiments, the precursor foam is thermally or mechanically treated to increase the density of the melamine formaldehyde foam relative to the precursor foam prior to contacting the polymer aerogel precursor. For example, Fig.18A system is schematically shown in which a foam 1801 (having a first thickness 1850) is placed between plates 1853 that compress the foam 1801 by applying a force to the major faces of the foam 1850. Upon completion of the process, a dense foam 1855 is produced, whose thickness 1856 is less than the thickness 1850. Without wishing to be bound by any particular theory, it is believed that increasing the density of the melamine formaldehyde foam prior to contacting with the polymer aerogel precursor produces an aerogel / foam material combination having increased mechanical strength and durability compared to an aerogel / foam material combination comprising undensified melamine formaldehyde foam. In some embodiments, increasing the density of the melamine formaldehyde foam prior to contacting with the polymer aerogel precursor increases the mechanical strength and durability of the aerogel / foam material combination without significantly increasing the thermal conductivity of the aerogel / foam material combination when compared to an aerogel / foam material combination comprising undensified melamine formaldehyde foam. In some embodiments, the density of the melamine formaldehyde foam increases by greater than or equal to 0.01 g / cc, greater than or equal to 0.02 g / cc, greater than or equal to 0.03 g / cc, greater than or equal to 0.04 g / cc, greater than or equal to 0.05 g / cc, greater than or equal to 0.06 g / cc, greater than or equal to 0.07 g / cc, greater than or equal to 0.08 g / cc, greater than or equal to 0.09 g / cc, greater than or equal to 0.1 g / cc, greater than or equal to 0.2 g / cc, greater than or equal to 0.3 g / cc, greater than or equal to 0.4 g / cc, greater than or equal to 0.5 g / cc, greater than or equal to 0.6 g / cc, greater than or equal to 0.7 g / cc, greater than or equal to 0.8 g / cc, greater than or equal to 0.9 g / cc, or greater than or equal to 1 g / cc (and / or, in some embodiments, up to 1.1 g / cc, up to 1.15 g / cc, up to 1.2 g / cc, or more).
[0090] In some embodiments, the melamine formaldehyde foam is heated to a temperature greater than or equal to 200° C. and less than or equal to 300° C. and compressed to a thickness greater than or equal to 15% and less than or equal to 90% of the thickness of the melamine formaldehyde foam just before compression prior to contacting the polymer aerogel precursor. In some embodiments, the melamine formaldehyde foam is compressed for a duration greater than or equal to 1 second, greater than or equal to 5 minutes, greater than or equal to 10 minutes, greater than or equal to 15 minutes, greater than or equal to 20 minutes, greater than or equal to 25 minutes, greater than or equal to 30 minutes, and / or less than or equal to 120 minutes, less than or equal to 60 minutes, less than or equal to 30 minutes, less than or equal to 25 minutes, less than or equal to 20 minutes, less than or equal to 15 minutes, less than or equal to 10 minutes, or less than or equal to 5 minutes.
[0091] In some embodiments, the melamine formaldehyde foam is compressed between two solid surfaces. For example, in some embodiments, the melamine formaldehyde foam is compressed between a solid plate and another surface. In some embodiments, the melamine formaldehyde foam is compressed between a roller and another surface. In some embodiments, the melamine formaldehyde foam is compressed between two or more solid plates. In some other embodiments, the melamine formaldehyde foam is compressed between two or more rollers. In some embodiments, the melamine formaldehyde foam is compressed to a thickness of less than or equal to 95%, less than or equal to 90%, less than or equal to 80%, less than or equal to 70%, less than or equal to 60%, less than or equal to 50%, less than or equal to 40%, less than or equal to 30%, less than or equal to 25%, less than or equal to 20%, less than or equal to 15%, less than or equal to 10%, and / or greater than or equal to 5%, greater than or equal to 10%, greater than or equal to 15%, greater than or equal to 20%, greater than or equal to 25%, greater than or equal to 30%, greater than or equal to 40%, greater than or equal to 50%, greater than or equal to 60%, greater than or equal to 70%, greater than or equal to 80%, or greater than or equal to 90% of the thickness of the melamine formaldehyde foam just before the compression. In some embodiments, the melamine formaldehyde foam is heated to a temperature of 100° C. or greater, 150° C. or greater, 200° C. or greater, 250° C. or greater, 300° C. or greater, or 350° C. or greater (and / or, in some embodiments, up to 400° C. or greater). In some embodiments, the melamine formaldehyde foam is compressed prior to being heated. In some other embodiments, the melamine formaldehyde foam is heated prior to being compressed. In further embodiments, the melamine formaldehyde foam is compressed while it is heated.
[0092] In some embodiments, the polymer aerogel precursor forms a polymer gel (e.g., a polyimide gel) on or in the pores of the melamine formaldehyde foam, thereby forming a material combination of the polymer gel and the melamine formaldehyde foam. The material combination of the gel and the foam is sometimes also referred to as a "gel / foam material combination". In certain embodiments, it may be particularly advantageous to use a polymer gel / melamine formaldehyde foam combination. In some embodiments, after the aerogel is formed, at least 20 vol%, at least 30 vol%, at least 40 vol%, at least 50 vol%, at least 60 vol%, at least 70 vol%, at least 80 vol%, at least 90 vol%, at least 95 vol%, at least 98 vol%, at least 99 vol%, at least 99.9 vol% or more of the pore volume of the foam is occupied by aerogel.
[0093] In some embodiments, the polymer aerogel precursor forms a polymer gel that substantially occupies all of the void space (e.g., at least 90%, at least 95%, at least 99%, or 100%) within the outer boundary of the melamine formaldehyde foam. In some embodiments, the polymer aerogel precursor forms a polymer gel partially within the void space within the outer boundary of the melamine formaldehyde foam. In some embodiments, the polymer aerogel precursor forms a polymer gel on or within the pores of the melamine formaldehyde foam, thereby forming a gel / foam material combination (e.g., including a polymer gel and melamine formaldehyde foam) while the material combination is located on a moving element (e.g., a conveyor belt). In some embodiments, the polymer aerogel precursor forms a polymer gel on or in the pores of the melamine formaldehyde foam within a time period of less than or equal to 1 minute, less than or equal to 2 minutes, less than or equal to 3 minutes, less than or equal to 5 minutes, less than or equal to 10 minutes, less than or equal to 15 minutes, less than or equal to 20 minutes, less than or equal to 30 minutes, less than or equal to 45 minutes, less than or equal to 60 minutes, less than or equal to 120 minutes, less than or equal to 180 minutes, less than or equal to 240 minutes, or less than or equal to 300 minutes. In some embodiments, the polymer aerogel precursor forms a polymer gel on or in the pores of the melamine formaldehyde foam within a time period of greater than or equal to 0.01 seconds, greater than or equal to 0.1 seconds, or greater than or equal to 1 second.
[0094] In some embodiments, the polymer aerogel precursor forms a polymer gel on or in the pores of the melamine formaldehyde foam in an environment at a temperature of greater than or equal to -25°C, greater than or equal to -10°C, greater than or equal to 0°C, greater than or equal to 10°C, greater than or equal to 25°C, greater than or equal to 50°C, greater than or equal to 75°C, or greater than or equal to 100°C. In some embodiments, the polymer aerogel precursor forms a polymer gel on or in the pores of the melamine formaldehyde foam in an environment at a temperature of less than or equal to 202°C, less than or equal to 150°C, less than or equal to 100°C, less than or equal to 90°C, less than or equal to 80°C, less than or equal to 70°C, less than or equal to 50°C, less than or equal to 40°C, less than or equal to 30°C, less than or equal to 20°C, less than or equal to 10°C, less than or equal to 0°C, or less than or equal to -10°C. In certain embodiments, the temperature of the environment in which the polymer aerogel precursor forms a polymer gel on or in the pores of the melamine formaldehyde foam is between the solidification point of the sol and the boiling point of the sol.
[0095] In some embodiments, at least a portion (e.g., at least 50 vol%, at least 75 vol%, at least 90 vol%, at least 95 vol%, at least 99 vol%, at least 99.9 vol%, or all) of the liquid in the pores of the gel / foam material combination is exchanged for a transfer solvent. In general, when used, the transfer solvent is different from the liquid in the pores of the gel / foam material combination. In some embodiments, the transfer solvent is selected because it is useful or necessary for the selected drying method for forming the aerogel. In some embodiments, the transfer solvent is selected because it will impart the desired effect to the final aerogel / foam material combination. In some embodiments, the gel is a solvent that is exchanged for an organic solvent. For example, in some embodiments, the pore fluid within the gel is substantially replaced by an organic solvent (e.g., by diffusing and soaking in a transfer organic solvent bath), after which the gel is subsequently dried by any suitable method to make an aerogel (e.g., described in more detail below).
[0096] In some embodiments, the liquid in the pores of the gel / foam material combination is exchanged for the transfer solvent in a continuous manner. For example, in some embodiments, the liquid in the pores of the gel / foam material combination is exchanged for the transfer solvent by moving the gel / foam material combination through a transfer solvent bath (e.g., using countercurrent flow). For example, Fig.21 Schematically depicted is a pump 2150 continuously pumping liquid through conduit 2159 into a bath 2160 in which a gel / foam material combination 2106 is positioned, which renews a transfer liquid (e.g., a transfer solvent) as liquid exchanged from the original gel (along with some transfer liquid) is transported out conduit 2169. In some embodiments, liquid in the pores of the gel / foam material combination is exchanged for a transfer solvent by moving the gel / foam material combination through a series of baths of transfer solvent. In some embodiments, the liquid in the pores of the gel / foam material combination is considered to be fully exchanged when the purity of the transfer solvent in the pores of the gel / foam material combination is greater than or equal to 10 wt%, greater than or equal to 15 wt%, greater than or equal to 30 wt%, greater than or equal to 50 wt%, greater than or equal to 60 wt%, greater than or equal to 70 wt%, greater than or equal to 80 wt%, greater than or equal to 90 wt%, greater than or equal to 95 wt%, greater than or equal to 99 wt%, greater than or equal to 99.5 wt%, greater than or equal to 99.95 wt%, or greater than or equal to 99.995 wt%. The purity of the transfer solvent in the pores of the material combination can be measured using well-known characterization methods such as UV spectroscopy or IR spectroscopy.
[0097] In some embodiments, the transfer solvent includes alcohol, ketone, nitrile, acetate, pyrrolidone, alkane, pentanone, dimethyl sulfoxide and / or liquid carbon dioxide. In some embodiments, the transfer solvent includes alcohol (e.g., methanol, ethanol, isopropanol and / or tert-butyl alcohol), ketone (e.g., acetone, methyl ethyl ketone, propyl methyl ketone and / or ethyl ethyl ketone), nitrile (e.g., acetonitrile), acetate (e.g., ethyl acetate), pyrrolidone (e.g., n-methyl-2-pyrrolidone), pentanone, alkane (e.g., hexane), dimethyl sulfoxide and / or liquid carbon dioxide. In certain embodiments, the use of tert-butyl alcohol as a transfer solvent may be particularly advantageous. In some embodiments, the transfer solvent contains a hydrophobe. In some embodiments, the transfer solvent is more compatible with the drying method than the liquid in the pores of the gel / foam material combination after the polyimide aerogel precursor is gelled. In some embodiments, the transfer solvent is used to purify the liquid in the pores of the material combination.
[0098] In some embodiments, the transfer solvent is frozen after the exchange. In some embodiments, the transfer solvent is frozen in a continuous manner. In some embodiments, the gel / foam material combination is moved through a liquid nitrogen bath to freeze the transfer solvent. In some embodiments, the gel / foam material combination is moved through a liquid nitrogen stream to freeze the transfer solvent. In some embodiments, the gel / foam material combination is moved through a cold dry air stream to freeze the transfer solvent. In some embodiments, the gel / foam material combination is moved through a carbon dioxide snow stream to freeze the transfer solvent. In some embodiments, the transfer solvent is frozen for a period of time that is less than or equal to 24 hours, less than or equal to 20 hours, less than or equal to 15 hours, less than or equal to 10 hours, less than or equal to 5 hours, less than or equal to 4 hours, less than or equal to 3 hours, less than or equal to 2 hours, less than or equal to 1 hour, less than or equal to 30 minutes, less than or equal to 20 minutes, less than or equal to 10 minutes, less than or equal to 5 minutes, less than or equal to 1 minute, less than or equal to 30 seconds, less than or equal to 5 seconds, or less than or equal to 1 second (and / or, in some embodiments, greater than or equal to 0.01 seconds, greater than or equal to 0.1 seconds, or greater than or equal to 1 second).
[0099] In some embodiments, the gel / foam material combination is dried to produce an aerogel / foam material combination. The formation of the aerogel may involve removing liquid from the gel (e.g., when used, transferring the solvent). In this context, "removal" does not necessarily require the removal of all liquids, and in some cases, a certain amount of residual liquid may remain in the aerogel. In certain embodiments, removing liquid from the gel to form an aerogel involves removing at least 95vol%, at least 98vol%, at least 98.5vol%, at least 99vol%, at least 99.9vol%, at least 99.99vol%, at least 99.999vol%, at least 99.9999vol%, or at least 99.99999vol% of liquid from the gel. In some embodiments, the liquid in the pores of the gel / foam material combination is removed by supercritical extraction. In some embodiments, the liquid in the pores of the gel / foam material combination is first at least partially replaced by carbon dioxide, and then the carbon dioxide is removed from the gel / foam material combination. In some embodiments, the liquid in the pores of the gel / foam material combination is first at least partially replaced with carbon dioxide, and then the carbon dioxide is removed from the gel / foam material combination. In some embodiments, the carbon dioxide is removed from the gel / foam material combination by supercritical extraction. In some embodiments, the carbon dioxide is removed from the gel / foam material combination by subcritical extraction.
[0100] Aerogel / foam combinations can be made by removing liquid from a gel in a manner that substantially retains the porosity and integrity of the complex nanostructured solid network of the gel / foam combination. For most gel / foam combinations, if the liquid in the gel evaporates, capillary stresses are generated as the gas-liquid interface retreats into and / or from the gel / foam combination, causing the solid network of the gel / foam combination to shrink and / or pull inward and collapse. The resulting material is a dry, relatively dense, low-porosity (typically <10% by volume) material commonly referred to as a xerogel-infused foam, or a solid formed by unhindered shrinkage drying of a gel-infused foam. However, the liquid in the gel / foam combination may instead be heated and pressurized beyond its critical point, a specific temperature and pressure at which the liquid will transform into a semi-liquid / semi-gas or supercritical fluid (exhibiting very little surface tension (if any)). Below the critical point, the liquid is in equilibrium with the vapor phase. However, as the system is heated and pressurized to the critical point, the molecules in the liquid develop more and more kinetic energy and move toward each other at increasingly faster rates, until eventually their kinetic energy exceeds the intermolecular adhesion forces that make the liquid cohesive. At the same time, the pressure in the vapor also increases, causing the molecules to move closer together on average, until the density of the vapor becomes close to and / or substantially as dense as the liquid phase. When the system reaches the critical point, the liquid and vapor phases become substantially indistinguishable and merge into a single phase that has a density and thermal conductivity comparable to that of a liquid, but is also capable of expanding and compressing in a manner similar to that of a gas. Although technically a gas, the term supercritical fluid may refer to a fluid that is close to but beyond its critical point, because such fluids, due to their density and kinetic energy, exhibit liquid-like properties that ideal gases do not typically possess, such as the ability to dissolve other substances. Since there are typically no phase boundaries beyond the critical point, supercritical fluids exhibit no surface tension and therefore no capillary forces, and can be removed from the gel / foam combination without causing the solid skeleton of the gel to collapse by isothermal decompression of the fluid. After the liquid is removed, the resulting dry, low-density, high-porosity material is an aerogel / foam combination.
[0101] The critical points of most substances are usually located at relatively high temperatures and pressures; therefore, supercritical drying usually involves heating the gel to elevated temperatures and pressures, and is therefore carried out in a pressure vessel. For example, if the gel / foam combination contains ethanol as its pore fluid, the ethanol can be supercritically extracted from the gel / foam combination by placing the gel / foam combination in a pressure vessel containing additional ethanol, slowly heating the vessel above the critical temperature of ethanol (241° C.), and allowing the autogenous vapor pressure of ethanol to pressurize the system above the critical pressure of ethanol (60.6 atm). Under these conditions, the vessel can then be quasi-isothermally depressurized so that the ethanol diffuses out of the pores of the gel / foam combination without recondensing into a liquid. Similarly, if the gel / foam combination contains a different solvent in its pores, the vessel may be heated and pressurized above the critical point of the solvent. However, the extraction of organic solvents from gel / foam combinations usually requires specialized equipment because organic solvents can be dangerously flammable and explosive at their critical points. Instead of supercritically extracting the organic solvent directly from the gel / foam material combination, the liquid in the pores of the gel / foam material combination can first be exchanged with a safer, non-flammable liquid (such as carbon dioxide), which is generally miscible with most organic solvents and has a relatively low critical point of 31.1°C and 72.9atm. In some embodiments, instead of first replacing the liquid in the pores of the gel / foam material combination with liquid CO2 and then supercritically extracting the CO2, the liquid in the gel / foam material combination can be extracted by flowing supercritical CO2 through the gel / foam material combination. This so-called supercritical CO2 drying process is a commonly used process in the manufacture of aerogel materials. According to some embodiments described herein, supercritical CO2 drying can be used to manufacture aerogel / foam material combinations.
[0102] In some embodiments, the liquid in the pores of the gel / foam material combination is removed by evaporation and / or boiling. In some embodiments, the transfer solvent in the pores of the gel / foam material combination is removed by evaporation and / or boiling. In some embodiments, the material combination can be made by removing liquid from the gel / foam material combination (drying by evaporation of the liquid). In some embodiments, the pore fluid exhibits a surface tension low enough to prevent damage to the gel / foam material combination upon evaporation: for example, less than or equal to 20 dynes / cm, less than or equal to 15 dynes / cm, less than or equal to 12 dynes / cm, or less than or equal to 10 dynes / cm, and / or greater than or equal to 0.1 dynes / cm, greater than or equal to 1 dyne / cm, or greater than or equal to 5 dynes / cm. In certain embodiments, the surface tension of the liquid is less than or equal to 20 dynes / cm, less than or equal to 15 dynes / cm, less than or equal to 12 dynes / cm, or less than or equal to 10 dynes / cm, and / or greater than or equal to 0.1 dynes / cm, greater than or equal to 1 dyne / cm, or greater than or equal to 5 dynes / cm. Combinations of these ranges are also possible (eg, greater than or equal to 5 dynes / cm and less than or equal to 25 dynes / cm). Other ranges are also possible.
[0103] In some embodiments, the pore liquid comprises carbon atoms, fluorine atoms, and oxygen atoms. Available Novec TM Branded solvents may be particularly suitable. In some embodiments, the pore liquid includes 1-methoxyheptafluoropropane (e.g., Novec 7000), methoxynonafluorobutane (e.g., Novec 7100), ethoxynonafluorobutane (e.g., Novec 7200), 3-methoxy-4-trifluoromethyldecafluoropentane (e.g., Novec 7300), 2-trifluoromethyl-3-ethoxydodecafluorohexane (e.g., Novec 7500), 1,1,1,2,3,3-hexafluoro-4-(1,1,2,3,3,3-hexafluoropropoxy)-pentane (e.g., Novec 7600), 2,3,3,4,4-pentafluorotetrahydro-5-methoxy-2,5-bis[1,2,2,2-tetrafluoro-1-(trifluoromethyl)ethyl]-furan ...700), 2,3,3,4,4-pentafluorotetrahydro-5-methoxy-2,5-bis[1,2,2,2-tetrafluoro-1-(trifluoromethyl)ethyl]-furan (e.g., Novec 7800), 2,3,3,4,4-pentafluorotetrahydro-5-methoxy-2,5-bis[1,2,2,2-tetrafluoro-1-(trifluoromethyl)ethyl]-furan (e.g., Novec 7900), 2,3,3,4,4-pentafluorotetrahydro-5-methoxy-2,5-bis[1,2,2,2-tetra 7700), fluorinated ketones such as CF3CF2C(=O)CF(CF3)2 dodecafluoro-2-methylpentan-3-one (e.g., Novec 1230 / 649), tetradecafluoro-2-methylhexan-3-one / tetradecafluoro-2,4-dimethylpentan-3-one (e.g., Novec 774), fluorinated ethers, tetradecafluorohexane / perfluoropentane / perfluorobutane (e.g., Fluorinert FC-72), fluorinated hydrocarbons such as 2,3-dihydrodecafluoropentane (e.g., XF) or any other suitable fluorinated organic solvent. In some embodiments, it may be particularly advantageous if the pore fluid selected for evaporative drying is methoxy nonafluorobutane (e.g., Novec 7100). In some embodiments, it may be particularly advantageous if the pore fluid selected for evaporative drying is ethoxy nonafluorobutane (e.g., Novec 7200).
[0104] In some embodiments, the pore liquid is evaporated at room temperature. In some embodiments, it may be particularly advantageous if the pore liquid is evaporated in an atmosphere of dry air (i.e., substantially anhydrous), nitrogen, and / or another substantially anhydrous inert gas. In some embodiments, it may be particularly advantageous if the pore fluid selected for evaporative drying is carbon dioxide at a temperature below its critical temperature and pressure (approximately 31.1° C. and 72.8 atm (1071 psi)). In one such embodiment, the gel / foam material combination is evaporated from liquid carbon dioxide at a temperature of approximately 28° C. and a pressure of approximately 68.0 atm (1000 psi).
[0105] In some embodiments, the aerogel / foam material combination can be made by the gel / foam material combination by the sublimation of the frozen pore fluid rather than the evaporation of the liquid phase pore fluid. The pore fluid can be properly frozen and sublimated in the case of little or no capillary force, thereby producing a gel / foam material combination containing a frozen pore fluid. That is, instead of removing the solvent by evaporation from the liquid state, the solvent can be sublimated from the solid state (already frozen), thereby minimizing the capillary force that may be generated by evaporation. In some embodiments, the sublimation of the frozen pore fluid is carried out under vacuum or partial vacuum conditions (e.g., freeze drying). In some embodiments, the liquid in the pores of the gel / foam material combination is removed by vacuum freeze drying. In some embodiments, the transfer solvent in the pores of the gel / foam material combination is removed by vacuum freeze drying. In some embodiments, the sublimation of the frozen pore fluid is carried out at atmospheric pressure. In some embodiments, the liquid in the pores of the gel / foam material combination is removed by freeze drying at atmospheric pressure or above atmospheric pressure. In some embodiments, the transfer solvent in the pores of the gel / foam material combination is removed by freeze drying at atmospheric pressure or above atmospheric pressure. In some embodiments, the method includes providing a gel / foam material combination having a solvent located within the pores of the gel / foam material combination; freezing the solvent within the pores of the gel / foam material combination; and subliming the solvent (e.g., under ambient conditions) to remove the solvent from the pores of the gel / foam material combination; thereby producing an aerogel / foam material combination. In some embodiments, the sublimation of the solvent is carried out in air, nitrogen, and / or another inert gas. In some such embodiments, the gas is substantially free of water (e.g., it contains water in an amount of 0 wt% to 1 wt%, 0 wt% to 0.1 wt%, 0 wt% to 0.01 wt%, 0 wt% to 0.001 wt%, 0 wt% to 0.0001 wt%, 0 wt% to 0.00001 wt%, 0 wt% to 0.000001 wt%, 0 wt% to 0.0000001 wt%, or 0 wt%). In some embodiments, it may be particularly advantageous if the pore fluid selected for the process is tert-butyl alcohol. For example, examples of techniques that can be used to dry aerogels (involving sublimation) are described in International Patent Application Publication No. WO 2016 / 127084, published on August 11, 2016 and entitled “Systems and Methods for Producing Aerogel Materials,” which is incorporated herein by reference in its entirety for all purposes.
[0106] In some embodiments, liquid in the pores of the gel / foam material combination is removed in a continuous manner. In some embodiments, the transfer solvent in the pores of the gel / foam material combination is removed in a continuous manner. In some embodiments, the gel / foam material combination is moved on a moving object (e.g., a conveyor belt) through a chamber (e.g., a chamber controlled to a specific temperature and pressure) in which liquid in the pores of the gel / foam material combination is removed.
[0107] In some embodiments, the temperature of the environment (e.g., in a room) in which the liquid is removed from the gel is controlled to be less than or equal to 25°C, less than or equal to 20°C, less than or equal to 15°C, less than or equal to 10°C, less than or equal to 5°C, less than or equal to 0°C, less than or equal to -5°C, less than or equal to -10°C, less than or equal to -15°C, less than or equal to -20°C, less than or equal to -25°C, or less than or equal to -30°C. In some embodiments (e.g., in certain embodiments using freeze drying to remove the solvent), the temperature of the environment (e.g., in a room) in which the fluid is removed can be below the freezing point of the fluid in the gel. In some embodiments (e.g., in certain embodiments using supercritical drying to remove the solvent), the temperature of the environment (e.g., in a room) in which the liquid is removed can be above the critical point of the liquid in the gel. In some embodiments (e.g., in certain embodiments using ambient atmospheric drying to remove the solvent), the temperature of the environment in which the liquid is removed can be the temperature of the surrounding environment (e.g., between 15°C and 30°C, or between 20°C and 25°C).
[0108] In some embodiments, the pressure of the environment in which the liquid is removed from the gel is the ambient pressure. For example, in some embodiments, the pressure of the environment in which the liquid is removed from the gel is 0.9 atmospheres to 1.1 atmospheres (absolute pressure). In some embodiments, the pressure of the environment in which the liquid is removed from the gel (e.g., in a room) is higher than the ambient pressure. In some embodiments, the pressure of the environment in which the liquid is removed from the gel (e.g., in a room) is lower than the ambient pressure.
[0109] In some embodiments, the time period over which liquid is removed from the gel / foam material combination to form the aerogel (e.g., the time period in the chamber) is greater than or equal to 1 second, greater than or equal to 10 seconds, greater than or equal to 30 seconds, greater than or equal to 1 minute, greater than or equal to 2 minutes, greater than or equal to 3 minutes, greater than or equal to 5 minutes, greater than or equal to 10 minutes, greater than or equal to 20 minutes, greater than or equal to 30 minutes, greater than or equal to 1 hour, greater than or equal to 2 hours, greater than or equal to 3 hours, greater than or equal to 4 hours, greater than or equal to 5 hours, greater than or equal to 6 hours, greater than or equal to 7 hours, greater than or equal to 8 hours, greater than or equal to 9 hours, or greater than or equal to 10 hours (and / or, in some embodiments, up to 24 hours, up to 48 hours, up to 7 days, up to 21 days, or longer).
[0110] In some embodiments, evaporation of the liquid to form an aerogel can occur under atmospheric or ambient conditions (e.g., with or without an airflow flowing along the surface of the gel), and thus does not require the use of a pressure vessel to remove the liquid. Ambient conditions can include ambient pressure conditions and ambient temperature conditions, including temperatures close to room temperature, such as about 0-50°C. One of ordinary skill in the art will appreciate that ambient pressure corresponds to the pressure of the surrounding environment, within the normal range of variation caused by altitude and / or air pressure fluctuations in normal operation under various weather conditions and installation locations. Ambient pressure conditions may be different from gauge pressure conditions, in which pressure (e.g., in a vacuum chamber, pressure vessel, or other enclosed space where pressure can be controlled) is described as pressure relative to ambient pressure (e.g., pressure measurements from a pressure gauge or sensor). Since such manufacturing processes according to certain embodiments of the present disclosure do not require a pressure vessel, the size of the resulting aerogel is not limited by the size of the pressure vessel chamber. In some embodiments, evaporation of liquid from the gel can produce an aerogel material within hours or minutes. Because such manufacturing processes according to certain embodiments of the present disclosure are relatively fast, aerogel materials such as plates, panels, blankets, and films can be manufactured in a continuous manner rather than in a batch manner as is typically done with supercritical drying or freeze drying. Depending on the type of liquid evaporated from the gel, such aerogels may also be manufactured without the risk of flammability or combustion.
[0111] In some embodiments, liquid can be removed from the gel simply by exposing the gel to the surrounding atmosphere (with or without airflow). In some embodiments, the liquid is removed under airflow. In some embodiments, it may be particularly advantageous if the gas is substantially dry. In some embodiments, the gas comprises dry air. In some embodiments, the gas comprises nitrogen. In some embodiments, the gas comprises carbon dioxide. In some embodiments, the flow rate of the gas is at least 10, at least 100, at least 1000, or at least 10,000 (and / or up to 100,000, up to 1,000,000 or more) standard liters (SLM) / minute / square meter of exposed gel encapsulation surface area. In some embodiments, liquid is removed at a rate of at least 10, at least 50, at least 100, at least 150, at least 200, at least 500, or at least 1000 grams / hour / square meter of exposed gel encapsulation surface area.
[0112] Examples of techniques that can be used to evaporate and dry aerogels are described, for example, in International Patent Application Publication No. WO 2016 / 161123, published on October 6, 2016 and entitled “Aerogel Materials and Methods for Producing Them,” which is incorporated herein by reference in its entirety for all purposes.
[0113] In some embodiments, a solvent is used. The solvent can be used in the original gel formulation or as a transfer solvent (i.e., a solvent that replaces the solvent already present in the gel). Any of a variety of suitable solvents can be used. In some embodiments, the solvent includes dimethyl sulfoxide; diethyl sulfoxide; N,N-dimethylformamide; N,N-diethylformamide; N,N-dimethylacetamide; N,N-diethylacetamide; N-methyl-2-pyrrolidone; 1-methyl-2-pyrrolidone; N-cyclohexyl-2-imidazolidinone; diethylene glycol dimethoxy ether; o-dichlorobenzene; phenols; cresol; xylenol; catechol; butyrolactone; acetone; methyl ethyl ketone; ethyl ethyl ketone; methyl propyl ketone; acetonitrile; ethyl acetate; and / or hexamethylphosphoramide. In some embodiments, it may be particularly advantageous if the solvent comprises N-methyl-2-pyrrolidone.
[0114] In some embodiments where drying of the gel to form an aerogel involves evaporative drying, it may be particularly advantageous to use a low surface tension solvent as the transfer solvent. In certain embodiments where supercritical drying of the gel is used to produce the aerogel, it may be particularly advantageous to use CO2, ethanol, methanol, acetone, or acetonitrile as the transfer solvent. In some embodiments where drying of the gel to form an aerogel involves atmospheric pressure freeze drying, it may be particularly advantageous to use tert-butyl alcohol, water, or other freeze drying solvents as the transfer solvent (in some cases, the use of tert-butyl alcohol is particularly advantageous).
[0115] In some embodiments, aerogels are formed from gels using multiple solvent exchange processes.
[0116] As described above, the gel in the gel / foam material combination can be formed by gelation. In certain embodiments, gelation can include polymerization and / or crosslinking (and often both) of aerogel precursor materials. The selection of prepolymer materials and crosslinking agents often depends on the type of aerogel material being formed. Examples of different aerogel materials are provided below.
[0117] In some embodiments, melamine formaldehyde foam constitutes a significant portion of the aerogel / foam material combination. For example, in some embodiments, greater than or equal to 1 wt%, greater than or equal to 2 wt%, greater than or equal to 3 wt%, greater than or equal to 5 wt%, greater than or equal to 10 wt%, greater than or equal to 15 wt%, greater than or equal to 20 wt%, greater than or equal to 25 wt%, greater than or equal to 30 wt%, greater than or equal to 35 wt%, greater than or equal to 40 wt%, greater than or equal to 45 wt%, greater than or equal to 50 wt%, greater than or equal to 55 wt%, greater than or equal to 60 wt%, greater than or equal to 65 wt%, greater than or equal to 70 wt%, greater than or equal to 75 wt%, greater than or equal to 80 wt%, greater than or equal to 85 wt%, greater than or equal to 90 wt%, or greater than or equal to 95 wt% of the aerogel / foam material combination is composed of foam (e.g., melamine formaldehyde foam). In some embodiments, less than or equal to 95 wt%, less than or equal to 90 wt%, less than or equal to 85 wt%, less than or equal to 90 wt%, less than or equal to 85 wt%, less than or equal to 80 wt%, less than or equal to 75 wt%, less than or equal to 70 wt%, less than or equal to 65 wt%, less than or equal to 60 wt%, less than or equal to 55 wt%, less than or equal to 50 wt%, less than or equal to 45 wt%, less than or equal to 40 wt%, less than or equal to 35 wt%, less than or equal to 30 wt%, less than or equal to 25 wt%, less than or equal to 20 wt%, less than or equal to 15 wt%, or less than or equal to 10 wt% of the aerogel / foam material combination is composed of foam (e.g., melamine formaldehyde foam). Combinations of the above-mentioned ranges are also possible (e.g., greater than or equal to 1 wt% and less than or equal to 95 wt%). Other ranges are also possible.
[0118] In some embodiments, a substantial portion of the aerogel / foam material combination is comprised of polymer aerogel (e.g., polyimide aerogel). For example, in some embodiments, greater than or equal to 1 wt%, greater than or equal to 2 wt%, greater than or equal to 3 wt%, greater than or equal to 5 wt%, greater than or equal to 10 wt%, greater than or equal to 15 wt%, greater than or equal to 20 wt%, greater than or equal to 25 wt%, greater than or equal to 30 wt%, greater than or equal to 35 wt%, greater than or equal to 40 wt%, greater than or equal to 45 wt%, greater than or equal to 50 wt%, greater than or equal to 55 wt%, greater than or equal to 60 wt%, greater than or equal to 65 wt%, greater than or equal to 70 wt%, greater than or equal to 75 wt%, greater than or equal to 80 wt%, greater than or equal to 85 wt%, greater than or equal to 90 wt%, or greater than or equal to 95 wt% of the aerogel / foam material combination is comprised of polymer aerogel (e.g., polyimide aerogel). In some embodiments, less than or equal to 95 wt%, less than or equal to 90 wt%, less than or equal to 85 wt%, less than or equal to 90 wt%, less than or equal to 85 wt%, less than or equal to 80 wt%, less than or equal to 75 wt%, less than or equal to 70 wt%, less than or equal to 65 wt%, less than or equal to 60 wt%, less than or equal to 55 wt%, less than or equal to 50 wt%, less than or equal to 45 wt%, less than or equal to 40 wt%, less than or equal to 35 wt%, less than or equal to 30 wt%, less than or equal to 25 wt%, less than or equal to 20 wt%, less than or equal to 15 wt%, less than or equal to 10 wt%, less than or equal to 5 wt%, less than or equal to 3 wt%, less than or equal to 2 wt%, or less than or equal to 1 wt% of the aerogel / foam material combination is composed of polymer aerogel (e.g., polyimide aerogel). Combinations of the above-mentioned ranges are also possible (e.g., greater than or equal to 1 wt% and less than or equal to 95 wt%). Other ranges are also possible.
[0119] The polymer aerogel and melamine formaldehyde foam in the aerogel / foam material combination can be present in any of a variety of suitable ratios. In some embodiments, the mass ratio of polymer aerogel to melamine formaldehyde foam in the aerogel / foam material combination is at least 0.1:1, at least 0.2:1, at least 0.3:1, at least 0.5:1, at least 0.7:1, at least 1:1, at least 1:2, at least 1:3, at least 1:4, at least 1:5, at least 1:10, at least 1:15, at least 1:20, at least 1:100, at least 1:1000, or at least 1:10,000. In some embodiments, the mass ratio of polymer aerogel to melamine formaldehyde foam in the aerogel / foam material combination is less than or equal to 1:10,000, less than or equal to 1:1000, less than or equal to 1:100, less than or equal to 1:20, less than or equal to 1:15, less than or equal to 1:10, less than or equal to 1:5, less than or equal to 1:4, less than or equal to 1:3, less than or equal to 1:2, less than or equal to 1:1, less than or equal to 0.7:1, less than or equal to 0.5:1, less than or equal to 0.3:1, less than or equal to 0.2:1, less than or equal to 0.1:1, or less. Combinations of the above-mentioned ranges are also possible (e.g., at least 0.1:1 and less than or equal to 1:10,000). Other ranges are also possible.
[0120] In some embodiments, a relatively high percentage of the aerogel in the aerogel / foam material combination falls within the outer boundary of the foam in the aerogel / foam material combination. In some embodiments, a relatively high percentage of the foam in the aerogel / foam material combination falls within the outer boundary of the aerogel in the aerogel / foam material combination. In some embodiments, at least 15 vol%, at least 25 vol%, at least 50 vol%, at least 75 vol%, at least 85 vol%, at least 90 vol%, at least 95 vol%, at least 99 vol%, or the entire volume within the outer boundary of the foam of the aerogel / foam material combination is located within the outer boundary of the aerogel of the aerogel / foam material combination. In certain embodiments, at least 15 vol%, at least 25 vol%, at least 50 vol%, at least 75 vol%, at least 85 vol%, at least 90 vol%, at least 95 vol%, at least 99 vol%, or the entire volume within the outer boundary of the aerogel of the aerogel / foam material combination is located within the outer boundary of the foam of the aerogel / foam material combination.
[0121] In some embodiments, a relatively high percentage of the three-dimensional convex hull of the aerogel in the aerogel / foam material combination falls within the three-dimensional convex hull of the foam in the aerogel / foam material combination. In some embodiments, a relatively high percentage of the three-dimensional convex hull of the foam in the aerogel / foam material combination falls within the three-dimensional convex hull of the aerogel in the aerogel / foam material combination. The phrase "three-dimensional convex hull" has its usual meaning in geometry and refers to the smallest three-dimensional convex set containing all points in a given set of points. The three-dimensional convex hull is sometimes also called a three-dimensional convex envelope or a three-dimensional convex closure in the field of geometry, and it can be visualized (relative to a set of points) as a shape surrounded by a deformable sheet, which is arranged so that it completely surrounds the three-dimensional description of the point. In some embodiments, at least 15 vol%, at least 25 vol%, at least 50 vol%, at least 75 vol%, at least 85 vol%, at least 90 vol%, at least 95 vol%, at least 99 vol%, or all of the three-dimensional convex hull of the foam of the aerogel / foam material combination is located within the three-dimensional convex hull of the aerogel of the aerogel / foam material combination. In certain embodiments, at least 15 vol%, at least 25 vol%, at least 50 vol%, at least 75 vol%, at least 85 vol%, at least 90 vol%, at least 95 vol%, at least 99 vol%, or all of the three-dimensional convex hull of the aerogel of the aerogel / foam material combination is located within the three-dimensional convex hull of the foam of the aerogel / foam material combination.
[0122] In some embodiments, the aerogel / foam combinations described herein are capable of functioning in high temperature applications. The performance of the aerogel / foam combinations at high temperatures can be tested by analyzing the thermal performance of the aerogel / foam combinations when they are subjected to what is referred to herein as a "standard heating cycle." As used herein, a "standard heating cycle" involves transferring an object from (1) a 25°C steel plate in an air environment at 25°C and 1 atm pressure, where the temperature of the object is uniformly 25°C (also referred to herein as the "starting low temperature condition"), to (2) an air environment above the steel plate for 60 minutes, where the temperatures of both the steel plate and the air are at a specified elevated temperature, and the air environment is large enough so that its size does not affect the heat transfer rate, and then back to (3) the starting low temperature condition until the object cools to a uniform temperature of 25°C. Fig. 9 This process is schematically shown for an aerogel / foam combination. Fig. 9 , the aerogel / foam material combination 930 is transferred from a 25°C steel plate in an air environment at 25°C and 1 atm pressure (left) to an air environment above the steel plate in an oven 935 for 60 minutes (middle), and then returned to the starting low temperature conditions until the aerogel / foam material combination 935 cools to a uniform temperature of 25°C (right).
[0123] In some embodiments, the aerogel / foam material combinations described herein can withstand dimensional changes at 200°C, which is a temperature that indicates the upper limit of the operating temperature range for many high temperature applications (such as under-the-hood applications) and is also the temperature point at which natural polymer aerogels (such as polyimide aerogels) typically begin to experience significant dimensional changes due to temperature. For example, in some embodiments, the aerogel / foam material combinations described herein can be subjected to a standard heating cycle in which the elevated temperature is 200°C (or 250°C, 300°C, or 350°C), and the dimensional changes of the aerogel / foam material combination do not exceed 10% (or, in some embodiments, do not exceed 5%, do not exceed 2%, do not exceed 1%, or do not exceed 0.1%).
[0124] In some embodiments, the aerogel / foam material combination has material properties required for engineering applications. In some embodiments, the aerogel / foam material combination is capable of operating at a temperature of at least 100°C, at least 200°C, at least 250°C, at least 300°C, at least 325°C, and / or at least 350°C. In some embodiments, the aerogel / foam material combination does not ignite in air at any temperature below 100°C, at any temperature below 200°C, at any temperature below 250°C, at any temperature below 300°C, at any temperature below 325°C, or at any temperature below 350°C. In some embodiments, for at least one dimension of the aerogel / foam material combination, at any temperature below 100°C, at any temperature below 200°C, at any temperature below 250°C, at any temperature below 300°C, at any temperature below 325°C, or at any temperature below 350°C, the dimension does not change by more than 20%, by more than 10%, by more than 5%, or by more than 2%.
[0125] In some embodiments, when the aerogel / foam material combination is subjected to a standard heating cycle in which the elevated temperature is 200°C (or the temperature is 250°C, 300°C, or 350°C), at least one (or at least two, or all three) dimensions of the aerogel / foam material combination falls within 50%, within 30%, within 20%, within 10%, within 5%, or within 3% (and / or, in some embodiments, falls to within 1%, within 0.1%, within 0.01%, or less) of the size of the aerogel / foam material combination prior to the standard heating cycle.
[0126] In some embodiments, the aerogel / foam material combination experiences an irreversible one-time linear shrinkage of less than or equal to 20%, less than or equal to 15%, less than or equal to 10%, or less than or equal to 5% (and / or as low as 0%) when exposed to flame for two cycles.
[0127] In some embodiments, when the aerogel / foam material combination is first exposed to its maximum operating temperature, the aerogel / foam material combination undergoes an irreversible one-time linear shrinkage of less than or equal to 20%, less than or equal to 15%, less than or equal to 10%, or less than or equal to 5% (and / or as little as 0%). In some embodiments, when the aerogel / foam material combination is subjected to a standard heating cycle with an elevated temperature of 200° C. (or an elevated temperature of 250° C., 300° C., 325° C., 350° C., or its maximum operating temperature), the aerogel / foam material combination undergoes an irreversible one-time linear shrinkage of less than or equal to 20%, less than or equal to 15%, less than or equal to 10%, or less than or equal to 5% (and / or as little as 0%) in at least one dimension (or at least two dimensions, or all three dimensions) relative to the dimensions before the standard heating cycle. In some embodiments, when the aerogel / foam material combination is subjected to two standard heating cycles with an elevated temperature of 200°C (or an elevated temperature of 250°C, 300°C, 325°C, 350°C, or its maximum operating temperature), the aerogel / foam material combination undergoes an irreversible one-time linear shrinkage of less than or equal to 20%, less than or equal to 15%, less than or equal to 10%, or less than or equal to 5% (and / or as little as 0%) in at least one dimension (or at least two dimensions, or all three dimensions) relative to the dimensions before the standard heating cycle. It is well known that objects in three-dimensional space have three orthogonal dimensions of length, width, and height. Linear shrinkage generally corresponds to a percentage change in one of the three orthogonal dimensions after treating an object under given conditions, comparing the same dimensional axis before and after the treatment.
[0128] In some embodiments, the aerogel / foam combination has a BET surface area greater than or equal to 10 m2 when subjected to a standard heating cycle with a 200°C ramp (or 250°C, 300°C, 325°C, 350°C, or their highest operating temperatures). 2 / g, greater than or equal to 20m 2 / g, greater than or equal to 40m 2 / g, greater than or equal to 60m 2 / g, greater than or equal to 80m 2 / g, greater than or equal to 100m 2 / g, greater than or equal to 150m 2 / g, greater than or equal to 200m 2 / g, greater than or equal to 250m 2 / g, greater than or equal to 300m 2 / g, greater than or equal to 350m 2 / g, greater than or equal to 400m 2 / g, greater than or equal to 600m 2 / g, or greater than or equal to 800m 2 / g (and / or, in some embodiments, up to 2,000 m 2 / g, up to 4,000m 2 / g, up to 8,000m 2 / g or greater).
[0129] In some embodiments, the flatness of the aerogel / foam material combination changes from its initial flatness by less than or equal to 10%, less than or equal to 9%, less than or equal to 8%, less than or equal to 7%, less than or equal to 6%, less than or equal to 5%, less than or equal to 4%, less than or equal to 3%, less than or equal to 2%, or less than or equal to 1% (and / or, in some embodiments, as little as 0%) when the aerogel / foam material combination is subjected to a standard heating cycle having an elevated temperature of 200°C (or 250°C, 300°C, 325°C, 350°C, or their maximum operating temperatures).
[0130] In some embodiments, when the aerogel / foam material combination is subjected to a standard heating cycle having an elevated temperature of 200°C (or 250°C, 300°C, 325°C, 350°C, or their maximum operating temperatures), the change in thickness of the aerogel / foam material combination relative to its initial thickness is less than or equal to 10%, less than or equal to 9%, less than or equal to 8%, less than or equal to 7%, less than or equal to 6%, less than or equal to 5%, less than or equal to 4%, less than or equal to 3%, less than or equal to 2%, or less than or equal to 1% (and / or, in some embodiments, as little as 0%).
[0131] As used herein, the phrase "maximum operating temperature" refers to the highest temperature at which an article is designed to operate for a long period of time while its mechanical and thermal properties remain acceptable stability. The maximum operating temperature is generally the temperature above which the article undergoes severe chemical and / or mechanical degradation. Examples of chemical degradation include denaturation, decomposition, phase change, and ignition. Examples of mechanical degradation include mechanical distortion, crushing, and the like. In some embodiments, the maximum operating temperature is set by a surface area loss of greater than or equal to 90%, greater than or equal to 80%, greater than or equal to 70%, greater than or equal to 60%, greater than or equal to 50%, greater than or equal to 40%, greater than or equal to 30%, greater than or equal to 20%, greater than or equal to 10%, greater than or equal to 5%, or greater than or equal to 1%. In some embodiments, it may be particularly advantageous if the maximum operating temperature is set by a surface area loss of greater than or equal to 40%.
[0132] In some embodiments, the mechanical degradation temperature refers to a temperature above which the article will break. In some embodiments, the ignition temperature refers to a temperature above which the article will ignite (i.e., catch fire) in air. In some embodiments, the chemical degradation temperature refers to a temperature above which the article continues to lose mass even if it reaches thermal equilibrium.
[0133] In some embodiments, the aerogel / foam material combination experiences an irreversible one-time linear shrinkage of less than or equal to 20%, less than or equal to 15%, less than or equal to 10%, or less than or equal to 5% when exposed to a 1.5" Bunsen burner flame. According to this test, the irreversible one-time linear shrinkage can be determined by first taking the aerogel / foam material combination at a temperature of 25°C, exposing the aerogel / foam material combination to a 1.5" Bunsen burner flame, transferring the aerogel / foam material combination back to an air environment at 25°C and 1 atm pressure and allowing it to cool until the temperature of the aerogel / foam material combination reaches 25°C, measuring the size of the aerogel / foam material combination, exposing the aerogel / foam material combination to the same flame again in the same manner, transferring the aerogel / foam material combination back to an air environment at 25°C and 1 atm pressure and allowing it to cool until the temperature of the aerogel / foam material combination reaches 25°C, measuring the size of the aerogel / foam material combination, and comparing the size of the aerogel / foam material combination after the second exposure to the flame with the size measured after the initial exposure to the flame. In some embodiments, the size of the aerogel / foam material combination after the second flame exposure is within 5%, within 4%, within 3%, within 2%, or within 1% of the size of the aerogel / foam material combination after the first flame exposure.
[0134] In some embodiments, the aerogel / foam combination is non-flammable. Non-flammability generally refers to the ability of the aerogel / foam combination to meet combustion certification standards. In some embodiments, the aerogel / foam combination meets the standards for flame time, drip flame time, and / or burn length specified in Section 25.853a of the Federal Aviation Regulations of the United States. In some embodiments, the aerogel / foam combination meets the A1, A2, and / or B fire performance standards of the European classification standard EN13501-1.
[0135] In some embodiments, the aerogel / foam material combination exhibits low flammability when exposed to flame. In some embodiments, the aerogel / foam material combination is non-flammable when subjected to a vertical flame test above a Bunsen burner burning propane.
[0136] In certain embodiments, the aerogel / foam material combination can pass a vertical burn test based on the procedure described in Section 25.853 of the Federal Aviation Regulations (FAR) for aviation interior burn requirements, modified as follows: the sample used for the test is 2.5 inches wide by 3.5 inches high by 0.25 inches thick; the sample is prepared under conditions of 50% relative humidity and 70°F (21.1°C); the flame source is a Bunsen burner using propane fuel, adjusted to a 1.5 inch flame height; the sample is suspended with the shorter 2.5 inch edge 0.75 inches from the top of the Bunsen burner flame so that the 3.5 inch edge is vertical (i.e., parallel to gravity); the flame is applied to the sample for a period of 1 minute and then removed. In some embodiments, when tested in this manner, the sample will self-extinguish in less than or equal to 1 second after the flame is removed. In some embodiments, the material combination sample will not significantly burn or sustain a flame at any time, but will char in the presence of the flame.
[0137] In certain embodiments, the aerogel / foam combination may have water resistant properties.
[0138] In some embodiments, the aerogel / foam material combination can exhibit hydrophobicity. The term hydrophobicity refers to the lack and / or partial lack of attraction between the material and water masses. The hydrophobicity of the bulk material generally refers to this property applied to the outer surface of the bulk material. In some cases, the apparent hydrophobicity of the outer surface (e.g., a textured outer surface) may be higher than the hydrophobicity of the bulk material.
[0139] The hydrophobicity of the aerogel / foam material combination can be expressed in terms of liquid water absorption. The term liquid water absorption refers to the ability of a material or composition to absorb, adsorb or otherwise retain water as a result of contact with liquid water. Liquid water absorption can be expressed in one of several ways, for example, as a fraction or percentage of the open pore volume or envelope volume of the aerogel, or as a fraction or percentage relative to the mass of the unwetted aerogel. Reported liquid water absorption is understood to be a measurement made under specific conditions. A material having superior or improved liquid water absorption relative to a different material is understood to have a lower liquid water absorption.
[0140] It may be helpful to measure the water absorption of the aerogel / foam combination. This can be accomplished by immersing the aerogel / foam combination in water. For illustration, Figure 5B The aerogel / foam material combination 506 is schematically shown immersed in water 517. The immersed aerogel / foam material combination 506 may then absorb (or not absorb) water for a period of time (e.g., 24 hours). A mesh cloth 518 may be used to keep the aerogel / foam material combination immersed in water for the duration. After immersion, the aerogel / foam material combination can be recovered, such as Figure 5BShown is a recovered aerogel / foam material combination 506. The recovered aerogel / foam material combination can then be compared (eg, weight comparison) to the aerogel / foam material combination 506 prior to immersion. In some embodiments, when the aerogel / foam material combination is immersed in water at 25° C. for 24 hours, the aerogel / foam material combination absorbs a mass of water within its outer boundary that is less than or equal to 200 wt%, less than or equal to 150 wt%, less than or equal to 100 wt%, less than or equal to 90 wt%, less than or equal to 80 wt%, less than or equal to 70 wt%, less than or equal to 60 wt%, less than or equal to 50 wt%, less than or equal to 40 wt%, less than or equal to 30 wt%, less than or equal to 20 wt%, less than or equal to 10 wt%, less than or equal to 5 wt%, less than or equal to 4 wt%, less than or equal to 3 wt%, less than or equal to 2 wt%, less than or equal to 1 wt%, or less than or equal to 0.1 wt% (and / or, in some embodiments, as little as 0.01 wt%, as little as 0.001 wt%, as little as 0.0001 wt% or less) relative to the dry mass of the aerogel / foam material combination before the aerogel / foam material combination was immersed in the water. In some embodiments, the aerogel / foam combination exhibits any of these properties after being subjected to a standard heating cycle wherein the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0141] In some embodiments, when measured according to standard ASTM C1511, the liquid water absorption rate of the aerogel / foam material combination can be less than or equal to 200 wt%, less than or equal to 150 wt%, less than or equal to 100 wt%, less than or equal to 80 wt%, less than or equal to 70 wt%, less than or equal to 60 wt%, less than or equal to 50 wt%, less than or equal to 40 wt%, less than or equal to 30 wt%, less than or equal to 20 wt%, less than or equal to 10 wt%, less than or equal to 5 wt%, less than or equal to 4 wt%, less than or equal to 3 wt%, less than or equal to 2 wt%, less than or equal to 1 wt%, or less than or equal to 0.1 wt% (and / or, in some embodiments, as little as 0.01 wt%, as little as 0.001 wt%, less than 0.0001 wt% or less). In some embodiments, the aerogel / foam combination exhibits any of these properties after being subjected to a standard heating cycle wherein the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0142] In some embodiments, when measured according to standard ASTM C1763, the liquid water absorption rate of the aerogel / foam material combination can be less than or equal to 200 wt%, less than or equal to 150 wt%, less than or equal to 100 wt%, less than or equal to 80 wt%, less than or equal to 70 wt%, less than or equal to 60 wt%, less than or equal to 50 wt%, less than or equal to 40 wt%, less than or equal to 30 wt%, less than or equal to 20 wt%, less than or equal to 10 wt%, less than or equal to 5 wt%, less than or equal to 4 wt%, less than or equal to 3 wt%, less than or equal to 2 wt%, less than or equal to 1 wt%, or less than or equal to 0.1 wt% (and / or, in some embodiments, as little as 0.01 wt%, as little as 0.001 wt%, less than 0.0001 wt% or less). In some embodiments, the aerogel / foam combination exhibits any of these properties after being subjected to a standard heating cycle wherein the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0143] In some embodiments, the liquid water absorption rate of the aerogel / foam material combination can be less than or equal to 200 wt%, less than or equal to 150 wt%, less than or equal to 100 wt%, less than or equal to 80 wt%, less than or equal to 70 wt%, less than or equal to 60 wt%, less than or equal to 50 wt%, less than or equal to 40 wt%, less than or equal to 30 wt%, less than or equal to 20 wt%, less than or equal to 10 wt%, less than or equal to 5 wt%, less than or equal to 4 wt%, less than or equal to 3 wt%, less than or equal to 2 wt%, less than or equal to 1 wt%, or less than or equal to 0.1 wt% (and / or, in some embodiments, as little as 0.01 wt%, as little as 0.001 wt%, less than 0.0001 wt% or less), relative to the weight of the aerogel / foam material combination before contact with liquid water, when measured according to standard EN 1609. In some embodiments, the aerogel / foam combination exhibits any of these properties after being subjected to a standard heating cycle wherein the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0144] The hydrophobicity of a material combination may also be expressed in terms of water vapor absorption. The term water vapor absorption refers to the ability of a material or composition to absorb, adsorb, or otherwise retain water as a result of contact with water in the vapor state. Water vapor absorption may be expressed as a fraction or percentage of water retained relative to the mass of the article prior to exposure to water vapor. Reported water vapor absorption is understood to be a measurement made under specific conditions. An article having superior or improved water vapor absorption relative to a different material is understood to have lower water vapor absorption or retention. In some embodiments, when measured in accordance with standard ASTM C1104, the water vapor absorption rate of the aerogel / foam material combination can be less than or equal to 100 wt%, less than or equal to 80 wt%, less than or equal to 70 wt%, less than or equal to 60 wt%, less than or equal to 50 wt%, less than or equal to 40 wt%, less than or equal to 30 wt%, less than or equal to 20 wt%, less than or equal to 10 wt%, less than or equal to 5 wt%, less than or equal to 4 wt%, less than or equal to 3 wt%, less than or equal to 2 wt%, less than or equal to 1 wt%, or less than or equal to 0.1 wt% (and / or, in some embodiments, as little as 0.01 wt%, as little as 0.001 wt%, as little as 0.0001 wt% or less). In some embodiments, the aerogel / foam combination exhibits any of these properties after being subjected to a standard heating cycle wherein the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0145] The hydrophobicity of a material combination can also be expressed in terms of the water contact angle. The term water contact angle refers to the equilibrium contact angle of a drop of water in contact with the outer surface of a material. Materials that have superior or improved hydrophobicity relative to a different material generally have higher water contact angles. For example, in Figure 5A, the foam / aerogel material combination 506 has a water droplet 514 on its surface, and a contact angle 515 is shown. In some embodiments, the water contact angle of the aerogel / foam material combination can be greater than 90°, greater than 100°, greater than 110°, greater than 120°, greater than 130°, greater than 140°, greater than 150°, greater than 160°, greater than 170° (and / or, in some embodiments, up to 175°, up to 178°, up to 179°, up to 179.9° or more) when measured according to standard ASTM D7490. In some embodiments, it is particularly advantageous that the aerogel / foam material combination exhibits a contact angle with water of greater than 90°, greater than 100°, greater than 110°, greater than 120°, greater than 130°, greater than 140°, greater than 150°, greater than 160°, greater than 170° (and / or, in some embodiments, up to 175°, up to 178°, up to 179°, up to 179.9° or more) when measured in accordance with standard ASTM D7490 in an ambient air environment at 1 atm and 25°C. In some embodiments, the aerogel / foam material combination exhibits any of these properties after undergoing a standard heating cycle in which the elevated temperature is 200°C (or 250°C, 300°C or 350°C).
[0146] In some embodiments, the aerogel / foam combination is surfactant-resistant. In some embodiments, the aerogel / foam combination is washable. In some embodiments, the aerogel / foam combination has a relatively low detergent absorption rate. The detergent absorption rate can be determined according to the following test. 0.97g sodium dodecyl sulfate is added to 1 liter of analytical reagent grade deionized (DI) water and dissolved to make a detergent solution. 50mL of detergent solution is added to a cylindrical vial 1.5 inches high by 3 inches wide. A sample of the aerogel / foam combination of 1cm x 1cm x 2mm is prepared and added to the vial. The mesh cloth is pressed into the vial so that the sample remains completely immersed for 24 hours at 20°C. The sample is then removed from the detergent solution and the surface liquid is removed mechanically. The sample is then weighed.
[0147] The difference between the mass of the sample before and after the test is the detergent absorption rate, and is generally expressed as a percentage of the mass increase relative to the original mass of the sample. In some embodiments, according to this test, the aerogel / foam material combination exhibits a detergent absorption rate of less than or equal to 300%, less than or equal to 200%, less than or equal to 100%, less than or equal to 50%, less than or equal to 10%, less than or equal to 5%, less than or equal to 1% (and / or, as little as 0.1%, as little as 0.01%, as little as 0.001% or less).
[0148] In certain embodiments, the aerogel / foam material combination may have a desired bulk density. The bulk density of the aerogel / foam material combination can be determined by dimensional analysis. For example, the bulk density can be measured by first carefully processing the sample into a regular shape (e.g., a block or rod). The length, width, and thickness (or length and diameter) can be measured using a caliper (accuracy ± 0.001 inches). These measurements can then be used to calculate the sample volume by multiplying the length*width*height if it is a block, or the height*radius squared*pi if it is a disc. The mass can be measured using a digital analytical balance with an accuracy of 0.001g. The bulk density can then be calculated as density=mass / volume. In some embodiments, the bulk density of the aerogel / foam material combination can be greater than or equal to 0.01 g / cc, greater than or equal to 0.05 g / cc, greater than or equal to 0.1 g / cc, greater than or equal to 0.2 g / cc, greater than or equal to 0.3 g / cc, greater than or equal to 0.4 g / cc, greater than or equal to 0.5 g / cc, greater than or equal to 0.6 g / cc, greater than or equal to 0.7 g / cc, or less than or equal to 0.8 g / cc (and / or, in some embodiments, as little as 0.1 g / cc, as little as 0.01 g / cc, or less). In certain embodiments, the bulk density of the material combination can be between 0.01 g / cc and 0.8 g / cc (including the endpoints). In some embodiments, it may be particularly advantageous if the material combination exhibits a bulk density greater than or equal to 0.01 g / cc and less than or equal to 0.5 g / cc. In some embodiments, the aerogel / foam combination exhibits any of these properties after being subjected to a standard heating cycle wherein the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0149] The aerogel / foam combination may exhibit any of a variety of suitable skeletal densities. One of ordinary skill in the art will appreciate that skeletal density refers to the density of the solid components of the aerogel / foam combination, rather than the bulk density of the aerogel / foam combination (which includes the volume of its pores). Skeletal density can be measured by measuring the skeletal volume of a sample using a pycnometer (e.g., a Micromeritics AccuPyc II 1340 gas pycnometer using helium as a working gas). Prior to measurement, the sample can be dried under a stream of nitrogen or helium to remove moisture or other solvents from the pores of the aerogel / foam combination. Skeletal volume measurements can be obtained by taking the average of 100 measurements. A digital analytical balance with an accuracy of 0.001 g can be used to measure mass. Skeletal density can be calculated as skeletal density = mass / skeletal volume. In some embodiments, the aerogel / foam combination has a skeletal density greater than or equal to 1 g / cc, greater than or equal to 1.2 g / cc, greater than or equal to 1.3 g / cc, greater than or equal to 1.4 g / cc, greater than or equal to 1.5 g / cc, greater than or equal to 1.6 g / cc, greater than or equal to 1.7 g / cc, greater than or equal to 1.8 g / cc, greater than or equal to 1.9 g / cc, greater than or equal to 2.0 g / cc, greater than or equal to 2.1 g / cc, greater than or equal to 2.2 g / cc, greater than or equal to 2.3 g / cc. In some embodiments, the aerogel / foam material combination exhibits any of these properties after being subjected to a standard heating cycle in which the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0150] The aerogel / foam combination may exhibit any of a variety of suitable pore structures. The pore width distribution, pore area distribution, and average pore size may be calculated from the nitrogen desorption isotherm using the Barrett-Joyner-Halenda (BJH) method within the ranges typically used to measure pore width and pore area distribution. In some embodiments, the aerogel / foam combination includes pores less than or equal to 100 microns, less than or equal to 10 microns, less than or equal to 1 micron, less than or equal to 500 nm, less than or equal to 250 nm, less than or equal to 100 nm, less than or equal to 50 nm, less than or equal to 25 nm, less than or equal to 20 nm, less than or equal to 15 nm, and / or less than or equal to 10 nm. In some embodiments, the aerogel / foam material combination includes pores greater than or equal to 10 nm, greater than or equal to 15 nm, greater than or equal to 20 nm, greater than or equal to 25 nm, greater than or equal to 50 nm, greater than or equal to 100 nm, greater than or equal to 250 nm, greater than or equal to 500 nm, greater than or equal to 1 micron, greater than or equal to 10 microns and / or greater than or equal to 100 microns.
[0151] The average pore width, e.g., average pore size (assuming cylindrical pores) can be calculated using pore width = 4*(total specific volume) / (specific surface area), where the total specific volume and specific surface area can also be calculated using BJH analysis of the desorption isotherm. In some embodiments, the aerogel / foam combination has an average pore width of less than or equal to 1 mm, less than or equal to 100 μm, less than or equal to 10 μm, less than or equal to 1 μm, less than or equal to 500 nm, less than or equal to 250 nm, less than or equal to 100 nm, less than or equal to 50 nm, less than or equal to 25 nm, less than or equal to 20 nm, less than or equal to 15 nm, and / or less than or equal to 10 nm (and / or, in some embodiments, greater than or equal to 5 nm, greater than or equal to 10 nm, greater than or equal to 15 nm, greater than or equal to 20 nm, greater than or equal to 25 nm, greater than or equal to 50 nm, greater than or equal to 100 nm, greater than or equal to 250 nm, greater than or equal to 500 nm, greater than or equal to 1 micron, greater than or equal to 10 microns, and / or greater than or equal to 100 microns). In some embodiments, the aerogel / foam combination exhibits a BJH average pore size greater than or equal to 2 nm and less than or equal to 50 nm when measured using nitrogen adsorption. In some embodiments, the aerogel / foam material combination exhibits a BJH average pore size greater than or equal to 10 nm and less than or equal to 25 nm when measured using nitrogen adsorption. In certain embodiments, it may be particularly advantageous if the average pore width of the aerogel / foam material combination is less than or equal to 50 nm. In some embodiments, it may be particularly advantageous if the average pore width of the aerogel / foam material combination is less than or equal to 20 nm. In some embodiments, the aerogel / foam material combination exhibits any of these properties after undergoing a standard heating cycle in which the elevated temperature is 200°C (or 250°C, 300°C, or 350°C).
[0152] In some embodiments, the pore width distribution of the aerogel / foam material combination can be unimodal (i.e., exhibit a single maximum). In some embodiments, the pore width distribution maximum is found to be less than or equal to 1 mm, less than or equal to 100 μm, less than or equal to 10 μm, less than or equal to 1 μm, less than or equal to 500 nm, less than or equal to 250 nm, less than or equal to 100 nm, less than or equal to 50 nm, less than or equal to 25 nm, less than or equal to 20 nm, less than or equal to 15 nm, and / or less than or equal to 10 nm (and / or, in some embodiments, greater than or equal to 5 nm, greater than or equal to 10 nm, greater than or equal to 15 nm, greater than or equal to 20 nm, greater than or equal to 25 nm, greater than or equal to 50 nm, greater than or equal to 100 nm, greater than or equal to 250 nm, greater than or equal to 500 nm, greater than or equal to 1 micrometer, greater than or equal to 10 micrometers, and / or greater than or equal to 100 micrometers). In some embodiments, the aerogel / foam material combination comprises a unimodal pore size distribution. In some embodiments, the aerogel / foam combination exhibits any of these properties after being subjected to a standard heating cycle wherein the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0153] In some embodiments, the pore width distribution of the aerogel / foam material combination can be bimodal, or at least bimodal. In some embodiments, the aerogel / foam material combination can have two different pore populations, one pore population having an average pore size less than or equal to a certain critical pore width, and another pore population having an average pore size greater than a certain critical pore width. In some embodiments, the critical pore width is less than or equal to 1 mm, less than or equal to 100 μm, less than or equal to 10 μm, less than or equal to 1 μm, less than or equal to 500 nm, less than or equal to 250 nm, less than or equal to 100 nm, less than or equal to 50 nm, less than or equal to 25 nm, less than or equal to 20 nm, less than or equal to 15 nm, and / or less than or equal to 10 nm (and / or, in some embodiments, greater than or equal to 5 nm, greater than or equal to 10 nm, greater than or equal to 15 nm, greater than or equal to 20 nm, greater than or equal to 25 nm, greater than or equal to 50 nm, greater than or equal to 100 nm, greater than or equal to 250 nm, greater than or equal to 500 nm, greater than or equal to 1 micron, greater than or equal to 10 microns, and / or greater than or equal to 100 microns). In some embodiments, the aerogel / foam material combination comprises a bimodal pore size distribution. In some embodiments, the aerogel / foam combination exhibits any of these properties after being subjected to a standard heating cycle wherein the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0154] In some embodiments, the aerogel / foam combination exhibits a relative humidity of greater than or equal to 0.05 cm 3 / g and less than or equal to 5cm 3 / g BJH pore volume. In some embodiments, the aerogel / foam material combination exhibits a BJH pore volume greater than or equal to 0.05 g / cm 3 , greater than or equal to 1g / cm 3 , greater than or equal to 2g / cm 3 , greater than or equal to 3g / cm 3 , greater than or equal to 4g / cm 3 , and / or less than or equal to 5g / cm 3 In some embodiments, the aerogel / foam material combination exhibits any of these properties after being subjected to a standard heating cycle in which the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0155] In some embodiments, the aerogel / foam material combination can exhibit an internal specific surface area. As used herein, internal surface area and specific surface area have the same meaning and describe the same phenomenon. These values may also be referred to as BET surface area. The internal specific surface area of the aerogel / foam material combination can be determined using nitrogen adsorption porosimetry and using the Brunauer-Emmett-Teller (BET) model to derive surface area values. For example, nitrogen adsorption porosimetry can be performed using a Micromeritics Tristar II 3020 surface area and porosity analyzer. Prior to performing the porosity analysis, the sample can be subjected to a vacuum treatment of about 100 Torr for 24 hours to remove water or other solvents adsorbed in the sample pores. The porosimeter can provide an adsorption isotherm and a desorption isotherm, which include the amount of analyte gas adsorbed or desorbed as a function of partial pressure. The specific surface area can be calculated from the adsorption isotherm using the BET method within a range typically used to measure surface area. In some embodiments, the BET surface area of the aerogel / foam material combination is greater than or equal to 5 m 2 / g, greater than or equal to 50m 2 / g, greater than or equal to 100m 2 / g, greater than or equal to 200m 2 / g, greater than or equal to 300m 2 / g, greater than or equal to 400m 2 / g, greater than or equal to 500m 2 / g, greater than or equal to 600m 2 / g, greater than or equal to 700m 2 / g, greater than or equal to 800m 2 / g, greater than or equal to 1000m 2 / g, greater than or equal to 2000m 2 / g, greater than or equal to 3000m 2 / g, and / or less than or equal to 1500m 2 / g, or less than or equal to 4000m 2 In some embodiments, the BET surface area of the aerogel / foam material combination is greater than or equal to 5 m 2 / g and less than or equal to 4000m 2 / g. In some embodiments, if the aerogel / foam material combination exhibits a gravitational field greater than or equal to 100 m 2 / g and less than or equal to 800m 2 A BET surface area of 200 m / g may be particularly advantageous. Aerogel / foam combinations may have BET surface area values outside these ranges. In certain embodiments, an aerogel / foam combination exhibits a BET surface area greater than or equal to 200 m / g. 2 / g and less than or equal to 400m 2 In some embodiments, the aerogel / foam combination exhibits any of these properties after being subjected to a standard heating cycle in which the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0156] In many applications, dusting of the aerogel / foam material combination may be disadvantageous. Without wishing to be bound by any particular theory, it is believed that dusting of the aerogel / foam material combination is caused by low fracture toughness of the material combination, and that the dust is composed of small fragments of the material combination that are fractured due to shear, tensile and / or bending stresses. In some embodiments, dusting of the aerogel in the aerogel / foam material combination may be caused by low fracture toughness of the aerogel. The degree of dusting of the aerogel / foam material combination can be determined using e.g. FIG. 10A to FIG. 10B The apparatus shown is determined as follows. The apparatus comprises a track on which are mounted two parallel clamps ( FIG. 10A to FIG. 10B 1008 and 1009 in the drawings). The clamp is attached to a linear actuator ( FIG. 10A to FIG. 10B Each fixture includes a 1 cm notch into which the aerogel / foam combination sample can be placed. For testing a particular aerogel / foam combination, a representative sample of 2.5 inches x 3.5 inches x 2 mm thick is cut. The sample mass is measured and recorded. The sample is clamped between the two clamps of the track so that the sample of 1 cm in length (see FIG. 10A to FIG. 10B The dimensions 1010 in the figure are located between each clamp. The clamps are positioned so that the sample is not initially stretched or compressed along the length of the track (see Fig. 10A). This position is referred to as the unbent position. The linear actuator then moves the clamps toward each other by a distance of 0.5 inches each, so that the ends of the aerogel / foam combination sample are now 2.5 inches apart (see Fig. 10B The size of 1011, with Fig. 10A 1011 in). This is considered the bent position. The linear actuator then moves the fixture back to the unbent position. This is considered one bending cycle. During the test, each bending cycle was performed in 1 second, and for the dust test, the sample was bent 1000 times. The mass of the sample was measured again after the dust test. The difference in the mass of the sample before and after the dust test is the amount of mass lost due to the dust. In some embodiments, after the dust test, the mass change of the aerogel / foam material combination sample is less than or equal to 50%, less than or equal to 25%, less than or equal to 10%, less than or equal to 5%, less than or equal to 2% (and / or, in some embodiments, as little as 0.1%, or as little as 0%). In some embodiments, the aerogel / foam material combination exhibits any of these properties after undergoing a standard heating cycle in which the elevated temperature is 200°C (or 250°C, 300°C, or 350°C)).
[0157] In some embodiments, a sample of an aerogel / foam combination having dimensions of 4 inches x 6 inches x 2 mm and having a longitudinal axis can be deformed without wrinkling such that the longitudinal axis forms a radius of curvature less than or equal to 1 inch, less than or equal to 1 mm, less than or equal to 2 mm, or less than 1 mm. 1 / 2 inches, less than or equal to 1 / 4 inch, less than or equal to 1 / 8 inch, less than or equal to 1 / 16 inch, less than or equal to 1 / 32 inch, less than or equal to 1 / 64 inch, or less than or equal to 1 / 256 inch (and / or as small as 1 / 512 inch or less). Fig.11 An example of this is shown in Figure 1, where an aerogel / foam combination 1106 has been deformed without wrinkling, having a radius of curvature 1140. In some embodiments, if an aerogel / foam combination sample having dimensions of 4 inches x 6 inches x 2 mm and a face area defined by the 4 inch and 6 inch dimensions is able to form a radius of curvature less than or equal to 1140 when bent perpendicular to the 4 inch dimension, 1 A radius of curvature of 1 / 4 inch may be particularly advantageous. In some embodiments, the aerogel / foam combination exhibits any of these properties after being subjected to a standard heating cycle in which the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0158] In some embodiments, the aerogel / foam combination has a compression modulus (also known as Young's modulus, which in some embodiments is approximately equal to the bulk modulus) and a yield strength, which can be determined using a standard uniaxial compression test. The compression modulus and yield strength can be measured using the method outlined in the standard ASTM D1621-10 "Standard Test Method for Compression Properties of Rigid Foam Plastics" written as follows, but the sample is compressed at a crosshead displacement rate of 1.3 mm / s (as specified in the standard ASTM D695) instead of 2.5 mm / s. In certain embodiments, the compression modulus of the aerogel / foam combination is greater than or equal to 100 kPa, greater than or equal to 500 kPa, greater than or equal to 1 MPa, greater than or equal to 10 MPa, greater than or equal to 50 MPa, greater than or equal to 100 MPa, and / or less than or equal to 100 MPa, less than or equal to 50 MPa, less than or equal to 10 MPa, less than or equal to 1 MPa, less than or equal to 500 kPa, less than or equal to 100 kPa, or less than or equal to 50 kPa. The compression modulus of the aerogel / foam material combination may be a combination of the above ranges or values outside these ranges. In some embodiments, it may be particularly advantageous if the aerogel / foam material combination exhibits a compression modulus greater than or equal to 1 MPa. In some embodiments, the aerogel / foam material combination exhibits any of these properties after undergoing a standard heating cycle in which the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0159] The aerogel / foam material combination may exhibit any of a variety of suitable compressive yield strengths. In certain embodiments, the compressive yield strength of the aerogel / foam material combination is greater than or equal to 40 kPa, greater than or equal to 100 kPa, greater than or equal to 500 kPa, greater than or equal to 1 MPa, greater than or equal to 5 MPa, greater than or equal to 10 MPa, greater than or equal to 50 MPa, greater than or equal to 100 MPa, greater than or equal to 500 MPa, and / or less than or equal to 500 MPa, less than or equal to 100 MPa, less than or equal to 50 MPa, less than or equal to 10 MPa, less than or equal to 5 MPa, less than or equal to 1 MPa, less than or equal to 1 MPa, less than or equal to 500 kPa, less than or equal to 100 kPa, or less than or equal to 50 kPa. The compressive yield strength of the aerogel / foam material combination may be a combination of the above ranges or values outside these ranges. In some embodiments, it may be particularly advantageous if the aerogel / foam material combination exhibits a compressive yield strength greater than or equal to 300 kPa. In some embodiments, the aerogel / foam combination exhibits any of these properties after being subjected to a standard heating cycle wherein the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0160] In some embodiments, the aerogel / foam material combination has a flexural modulus and a flexural yield strength that can be determined using standard mechanical test methods. The flexural modulus and yield strength can be measured using the methods outlined in the standard ASTM D790-10 "Flexural properties of non-reinforced and reinforced plastics and electrical insulating materials" written as follows, but the specimen span is equal to a fixed value of 45 mm, rather than varying according to the ratio of the specimen thickness. The specimen length is at least 10 mm greater than the span. The specimen depth ranges from 5 mm to 7 mm. The specimen width ranges from 15 mm to 20 mm. In certain embodiments, the flexural modulus of the aerogel / foam combination as measured by the method may be at least 0.00689 MPa, at least 0.01 MPa, at least 0.02 MPa, at least 0.03 MPa, at least 0.04 MPa, at least 0.05 MPa, at least 0.06 MPa, at least 0.07 MPa, at least 0.08 MPa, at least 0.09 MPa, at least 0.1 MPa, at least 0.2 MPa, at least 0.3 MPa, at least 0.4 MPa, at least 0.5 MPa, at least 0.6 In some embodiments, the aerogel / foam combination exhibits a flexural modulus of at least 1 MPa, at least 0.7 MPa, at least 0.8 MPa, at least 0.9 MPa, at least 1 MPa, at least 2 MPa, at least 5 MPa, at least 10 MPa, at least 20 MPa, at least 50 MPa, at least 100 MPa, at least 200 MPa, at least 300 MPa, and / or less than or equal to 1 GPa, less than or equal to 500 MPa, less than or equal to 300 MPa, less than or equal to 200 MPa, less than or equal to 100 MPa, less than or equal to 50 MPa, and / or less than or equal to 20 MPa. In some embodiments, it may be particularly advantageous if the aerogel / foam combination exhibits a flexural modulus of greater than or equal to 1 MPa. The flexural modulus of the aerogel / foam combination may be measured in accordance with ASTM D790-10, but with a sample span equal to a fixed value of 45 mm. In some embodiments, the aerogel / foam combination exhibits any of these properties after being subjected to a standard heating cycle wherein the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0161] In some embodiments, the flexural strength of the aerogel / foam combination is greater than or equal to 0.00689 MPa, at least 0.01 MPa, at least 0.02 MPa, at least 0.03 MPa, at least 0.04 MPa, at least 0.05 MPa, at least 0.06 MPa, at least 0.07 MPa, at least 0.08 MPa, at least 0.09 MPa, at least 0.1 MPa, at least 0.2 MPa, greater than or equal to 0.5 MPa, greater than or equal to 1 MPa, greater than or equal to 1.5 MPa, greater than or equal to 2 MPa, greater than or equal to 2.5 MPa, greater than or equal to 3 MPa, greater than or equal to 3.5 MPa, or greater than or equal to 4 MPa, at least 5 MPa, at least 10 MPa, at least 20 MPa, at least 50 MPa, at least 100 MPa, at least 200 MPa, at least 300 MPa, and / or less than or equal to 1 GPa. In some embodiments, it may be particularly advantageous if the material combination exhibits a flexural strength greater than or equal to 0.5 MPa. The flexural strength of the aerogel / foam material combination can be measured in accordance with ASTM D790-10, but with a sample span equal to a fixed value of 45 mm. In some embodiments, the aerogel / foam material combination exhibits any of these properties after undergoing a standard heating cycle in which the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0162] Figure 7 An apparatus for measuring the flexural strength and modulus of an aerogel / foam material combination is depicted. The aerogel / foam material combination 706 is placed between plates 726, and a stage 728 can be moved downward to apply a force to the aerogel / foam material combination 706 that can be used to quantify the flexural strength and / or modulus of the material.
[0163] In some embodiments, the aerogel / foam combination can withstand flexural strains greater than or equal to 1%, greater than or equal to 5%, greater than or equal to 10%, greater than or equal to 20%, greater than or equal to 30%, greater than or equal to 40%, greater than or equal to 50%, greater than or equal to 60%, greater than or equal to 70%, or greater than or equal to 80% (and / or, in some embodiments, up to 99.5% or more) without breaking. In some embodiments, the aerogel / foam combination exhibits any of these properties after undergoing a standard heating cycle in which the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0164] In some embodiments, the aerogel / foam material combination has a dielectric constant and a loss tangent, which can be determined using standard test methods. The dielectric constant and loss tangent can be measured using the methods outlined in the standard ASTM D2520-13 "Complex permittivity (dielectric constant) of solid electrical insulating materials at microwave frequencies and temperatures up to 1650°C". In some embodiments, the aerogel / foam material combination exhibits an average dielectric constant of less than or equal to 100, less than or equal to 10, less than or equal to 5, less than or equal to 2, less than or equal to 1.75, less than or equal to 1.5, less than or equal to 1.4, or less than or equal to 1.25 (and / or, in some embodiments, as little as 1.0) in the range of 0-50 GHz. In some embodiments, it may be particularly advantageous if the aerogel / foam material combination exhibits an average dielectric constant of less than or equal to 1.4 in the range of 0-50 GHz. In certain embodiments, the material combination exhibits an average loss tangent less than or equal to 1, less than or equal to 0.1, less than or equal to 0.01, less than or equal to 0.001, or less than or equal to 0.0001 in the range of 0-50 GHz. In certain embodiments, it may be particularly advantageous if the aerogel / foam material combination exhibits an average loss tangent less than or equal to 0.01 in the range of 0-50 GHz. In some embodiments, the aerogel / foam material combination exhibits any of these properties after undergoing a standard heating cycle in which the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0165] In some embodiments, the aerogel / foam material combination has a relatively low thermal conductivity.The thermal conductivity of the aerogel / foam material combination can be measured using a calibrated hot plate (CHP) apparatus. Figure 6 A CHP device is schematically shown. In the figure, an aerogel / foam material combination 622 is placed between a hot surface 621 and a cold surface 624. A reference material 623 is adjacent to the aerogel / foam material combination 622, and a heating element 620 can provide heat to the device. A processor 625 can collect heat and / or temperature data from the device to determine the thermal conductivity of the aerogel / foam material combination. More details about this measurement technique are described below.
[0166] The CHP method is based on the principles of the standard ASTM E1225 "Standard Test Method for Thermal Conductivity of Solids by the Guarded-Comparative-Longitudinal Heat Flow Technique". An apparatus in which an aerogel / foam material combination and / or other sample material (whose mass, thickness, length and width have been measured as explained in the procedure for measuring bulk density) is placed in series between a hot surface and a cold surface with a standard reference material (e.g., NIST SRM 1453 EPS board) having a precisely known thermal conductivity, density and thickness. The hot side of the system includes an aluminum block (4 inches x 4 inches x 1 inch) in which three cartridge heaters are embedded. The cartridge heaters are controlled by a temperature controller operating in an on / off mode. The set point feedback temperature of the controller is measured by a K-type thermocouple (referred to as TC_H) at the center of the top surface of the aluminum block (at the interface between the block and the sample material). A second identical thermocouple is placed directly next to the thermocouple (referred to as TC_1). The sample material is placed on top of the aluminum block with the thermocouple close to its center. A third identical thermocouple (TC_2) is placed directly above the other thermocouples at the interface between the sample material and the reference material. The reference material is then placed on top of the sample material covering the thermocouples. A fourth identical thermocouple (TC_3) is placed on top of the reference material, aligned with the other three thermocouples. On top of this pile of material, a 6-inch diameter stainless steel cup filled with ice water is placed to provide an isothermal cold surface. The heater is powered and regulated by the temperature controller to maintain a constant temperature of approximately 37.5°C on the hot side of the system. After ensuring that all components are properly in place, the system is turned on and allowed to reach equilibrium. At this point, the temperatures at TC_1, TC_2, and TC_3 are recorded. This recording is repeated every 15 minutes for at least one hour. From each set of temperature measurements (a set is three temperatures measured simultaneously), the unknown thermal conductivity can be calculated as follows. By assuming one-dimensional conduction (i.e., neglecting edge losses and conduction perpendicular to the lines where TC_1, TC_2, and TC_3 lie), it can be said that the heat flux through each material is defined as the temperature difference across the material divided by the thermal resistance per unit area of the material (where thermal resistance per unit area is defined as R" = t / k, where t is the thickness (meters) and k is the thermal conductivity (W / m·K)). The thickness t is measured while subjecting the sample material to a pressure equal to the pressure to which the sample material is subjected during the CHP thermal conductivity test. For example, the thickness of the sample material can be measured by clamping the sample material between a fixed rigid surface and a movable rigid plate parallel to the rigid surface, and applying a known pressure to the material sample by applying a known force to the rigid plate. The thickness t_1 of the material pile can be measured using any suitable device, such as a micrometer or a depth gauge. The material sample is then removed from the material pile and the thickness t_2 of the rigid plate is measured under the same force as previously specified. Therefore, the thickness of the material sample at the specified pressure can be calculated by subtracting t_2 from t_1.The preferred range of material sample thickness for this thermal conductivity measurement is between 2 and 10 mm. Using material sample thickness outside of this range may introduce a degree of uncertainty and / or error in the thermal conductivity calculation, rendering the measurement no longer accurate and / or reliable. By setting the heat flux through the sample material equal to the heat flux through the reference material, the thermal conductivity of the sample material (the only unknown in the equation) can be solved. This calculation is performed for each temperature set and the average is reported as the sample thermal conductivity. The thermocouples used can be individually calibrated for the platinum RTD and assigned unique corrections for zero offset and slope, resulting in a measurement uncertainty of ±0.25°C instead of ±2.2°C.
[0167] In certain embodiments, the thermal conductivity of the aerogel / foam material combination at 25°C as measured by the CHP method (described above) may be less than or equal to 100 mW / m·K, less than or equal to 75 mW / m·K, less than or equal to 50 mW / m·K, less than or equal to 35 mW / m·K, less than or equal to 25 mW / m·K, less than or equal to 23 mW / m·K, less than or equal to 20 mW / m·K, less than or equal to 15 mW / m·K, or less than or equal to 12 mW / m·K, and / or greater than or equal to 0.1 mW / m·K, greater than or equal to 1 mW / m·K, greater than or equal to 2 mW / m·K, greater than or equal to 5 mW / m·K, or greater than or equal to 15 mW / m·K. In some embodiments, it may be particularly advantageous if the aerogel / foam material combination exhibits a thermal conductivity of less than or equal to 30 mW / m·K, or less than or equal to 25 mW / m·K at 25° C. In some embodiments, the aerogel / foam material combination exhibits any of these properties after being subjected to a standard heating cycle in which the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0168] In some embodiments, the aerogel / foam material combination exhibits a lower thermal conductivity than a polymer aerogel (e.g., a polyimide aerogel) when measured separately from the melamine formaldehyde foam. In certain embodiments, the aerogel / foam material combination exhibits a lower thermal conductivity than a melamine formaldehyde foam when measured separately from the polymer aerogel (e.g., a polyimide aerogel). In some embodiments, the aerogel / foam material combination exhibits a thermal conductivity that is at least 1%, at least 2%, at least 5%, at least 10%, at least 15%, at least 20%, at least 25%, at least 30%, at least 35%, at least 40%, at least 45%, at least 50%, at least 55%, or at least 60% lower than the thermal conductivity of the polymer aerogel when measured separately from the melamine formaldehyde foam; and the aerogel / foam material combination exhibits a thermal conductivity that is at least 1%, at least 2%, at least 5%, at least 10%, at least 15%, at least 20%, at least 25%, at least 30%, at least 35%, at least 40%, at least 45%, at least 50%, at least 55%, or at least 60% lower (and / or, in some embodiments, up to 80%, 90% lower, or less) than the thermal conductivity of melamine formaldehyde foam when measured separately from the polymer aerogel. In some embodiments, it may be particularly advantageous if the aerogel / foam material combination exhibits a thermal conductivity that is at least 10% lower than the thermal conductivity of the polymer aerogel (when measured separately from the melamine formaldehyde foam); and the aerogel / foam material combination exhibits a thermal conductivity that is at least 10% lower than the thermal conductivity of the melamine formaldehyde foam (when measured separately from the polymer aerogel). In some embodiments, the aerogel / foam material combination exhibits any of these properties after being subjected to a standard heating cycle in which the elevated temperature is 200°C (or 250°C, 300°C, or 350°C).
[0169] In some embodiments, the aerogel / foam material combination exhibits a reduction in thermal conductivity of greater than or equal to 1%, greater than or equal to 2%, greater than or equal to 5%, greater than or equal to 10%, greater than or equal to 15%, greater than or equal to 20%, greater than or equal to 25%, greater than or equal to 30%, greater than or equal to 35%, greater than or equal to 40%, greater than or equal to 45%, greater than or equal to 50%, greater than or equal to 55%, or greater than or equal to 60% (and / or, in some embodiments, up to 80%, 90% or more) relative to the lower of the thermal conductivity of the melamine formaldehyde foam when measured separately from the polymer aerogel and the thermal conductivity of the polymer aerogel when measured separately from the melamine formaldehyde foam. In some embodiments, it may be particularly advantageous if the aerogel / foam material combination exhibits a reduction in thermal conductivity of greater than or equal to 10% relative to the lower of the thermal conductivity of the melamine formaldehyde foam when measured separately from the polymer aerogel and the thermal conductivity of the polymer aerogel when measured separately from the melamine formaldehyde foam. In some embodiments, the aerogel / foam combination exhibits any of these properties after being subjected to a standard heating cycle wherein the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0170] In some embodiments, the aerogel / foam combination can exhibit relatively high sound attenuation. The sound attenuation of the aerogel / foam combination can be expressed as sound transmission loss. The term sound transmission loss is defined in standard ASTM C634. In certain embodiments, the aerogel / foam material combination exhibits a sound transmission loss of greater than or equal to 1 dB / cm, greater than or equal to 5 dB / cm, greater than or equal to 10 dB / cm, greater than or equal to 11 dB / cm, greater than or equal to 12 dB / cm, greater than or equal to 13 dB / cm, greater than or equal to 14 dB / cm, greater than or equal to 15 dB / cm, greater than or equal to 16 dB / cm, greater than or equal to 17 dB / cm, greater than or equal to dB / cm, greater than or equal to 18 dB / cm, greater than or equal to 19 dB / cm, greater than or equal to 20 dB / cm, greater than or equal to 30 dB / cm, greater than or equal to 40 dB / cm, and / or greater than or equal to 50 dB / cm (and / or up to 80 dB / cm, up to 100 dB / cm, or more) when measured in accordance with ASTM E2611 standard. In certain embodiments, the aerogel / foam material combination exhibits a sound transmission loss of greater than or equal to 1 dB / cm, greater than or equal to 5 dB / cm, greater than or equal to 10 dB / cm, greater than or equal to 11 dB / cm, greater than or equal to 12 dB / cm, greater than or equal to 13 dB / cm, greater than or equal to 14 dB / cm, greater than or equal to 15 dB / cm, greater than or equal to 16 dB / cm, greater than or equal to 17 dB / cm, greater than or equal to dB / cm, greater than or equal to 18 dB / cm, greater than or equal to 19 dB / cm, greater than or equal to 20 dB / cm, greater than or equal to 30 dB / cm, greater than or equal to 40 dB / cm, and / or greater than or equal to 50 dB / cm (and / or up to 80 dB / cm, up to 100 dB / cm, or more) when measured according to ASTM E90 standard. In some embodiments, it may be particularly advantageous if the aerogel / foam material combination exhibits an average sound transmission loss of greater than or equal to 5 dB / cm in the frequency range of 300 Hz-2000 Hz. In some embodiments, the aerogel / foam material combination exhibits any of these properties after undergoing a standard heating cycle in which the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0171] In some embodiments, the aerogel / foam material combination has at least one dimension that is greater than or equal to 1 mm, greater than or equal to 2 mm, greater than or equal to 3 mm, greater than or equal to 4 mm, greater than or equal to 5 mm, greater than or equal to 6 mm, greater than or equal to 7 mm, greater than or equal to 8 mm, greater than or equal to 9 mm, greater than or equal to 10 mm, greater than or equal to 15 mm, greater than or equal to 20 mm, greater than or equal to 25 mm, greater than or equal to 30 mm, greater than or equal to 35 mm, greater than or equal to 40 mm, greater than or equal to 45 mm, greater than or equal to 50 mm, greater than or equal to 10 cm, greater than or equal to 30 cm, greater than or equal to 50 cm, and / or greater than or equal to 100 cm (and / or, in some embodiments, up to 1 meter, up to 25 meters, up to 100 meters, up to 1000 meters or more). In some embodiments, it may be particularly advantageous if the aerogel / foam material combination has at least one dimension that is greater than or equal to 30 cm. In some embodiments, the dimension is a first dimension.
[0172] In some embodiments, the aerogel / foam material combination has a second dimension that is different from and perpendicular to the first dimension and is greater than or equal to 1 mm, greater than or equal to 2 mm, greater than or equal to 3 mm, greater than or equal to 4 mm, greater than or equal to 5 mm, greater than or equal to 6 mm, greater than or equal to 7 mm, greater than or equal to 8 mm, greater than or equal to 9 mm, greater than or equal to 10 mm, greater than or equal to 15 mm, greater than or equal to 20 mm, greater than or equal to 25 mm, greater than or equal to 30 mm, greater than or equal to 35 mm, greater than or equal to 40 mm, greater than or equal to 45 mm, greater than or equal to 50 mm, greater than or equal to 10 cm, greater than or equal to 30 cm, greater than or equal to 50 cm, and / or greater than or equal to 100 cm (and / or, in some embodiments, up to 1 meter, up to 25 meters, up to 50 meters, or more). In some embodiments, it may be particularly advantageous if the second dimension of the aerogel / foam material combination is greater than or equal to 1 foot.
[0173] In some embodiments, the aerogel / foam combination has a third dimension, different from and perpendicular to the first and second dimensions, that is greater than or equal to 1 mm, greater than or equal to 2 mm, greater than or equal to 3 mm, greater than or equal to 4 mm, greater than or equal to 5 mm, greater than or equal to 6 mm, greater than or equal to 7 mm, greater than or equal to 8 mm, greater than or equal to 9 mm, greater than or equal to 10 mm, greater than or equal to 15 mm, greater than or equal to 20 mm, greater than or equal to 25 mm, greater than or equal to 30 mm, greater than or equal to 35 mm, greater than or equal to 40 mm, greater than or equal to 45 mm, greater than or equal to 50 mm, greater than or equal to 10 cm, greater than or equal to 30 cm, greater than or equal to 50 cm, and / or greater than or equal to 100 cm (and / or, in some embodiments, up to 1 meter, up to 25 meters, up to 50 meters, or more). In some embodiments, it may be particularly advantageous if the third dimension of the aerogel / foam combination is greater than or equal to 1 foot.
[0174] As will be understood by one of ordinary skill in the art, the length of a particular dimension of an article (e.g., an aerogel / foam combination) corresponds to the distance between the outer boundaries of the article along that dimension. As will be further understood by one of ordinary skill in the art, when measuring three dimensions of an article, each dimension is perpendicular to the other two dimensions (such that the second dimension is perpendicular to the first dimension, and the third dimension is perpendicular to the first and second dimensions).
[0175] In some embodiments, the aerogel / foam material combination comprises an infrared (IR) sunscreen. The IR sunscreen can be added, for example, before, during or after gelling of the gel / foam material combination and / or before, during or after forming the aerogel / foam material combination.
[0176] Any of a variety of materials can be used in the IR sunscreen. In some embodiments, the IR sunscreen includes metals (e.g., magnesium, zinc, antimony and / or combinations of these or other metals, such as magnesium-zinc blends and / or magnesium-zinc-antimony blends), metal carbides (e.g., titanium carbide), metalloid carbides (e.g., silicon carbide), metal oxides (e.g., iron oxide, titanium oxide, zinc oxide, aluminum oxide and / or antimony oxide), metalloid oxides (e.g., silicon oxide), graphitic carbon (e.g., graphite, graphene, carbon nanotubes and / or fullerenes), elemental carbon (e.g., carbon black), amorphous carbon (e.g., carbon made from polymer aerogels), phosphates, borates, metal silicates, metalloid silicates, metallocenes, molybdates, stannates, hydroxides and / or carbonates. In some embodiments, the IR sunscreen is a particulate material having a measurable maximum cross-sectional size. For example, Figure 8The foam / aerogel material combination including particulate material is schematically shown. In the figure, the foam / aerogel material combination 807 includes particulate material 827. The particulate material can be located at the surface of the aerogel / foam material combination and / or in the body of the aerogel / foam material combination. For example, in Figure 8 In FIG. 8 , 828 shows the boundary of the aerogel / foam material combination volume that has been cut out, and particulate material 829 is present within the bulk of the aerogel / foam material combination.
[0177] The average maximum cross-sectional size is taken as a number mean and can be measured using a microscope. In some embodiments, the average maximum cross-sectional size of the IR sunscreen can be determined by placing a representative sample of the IR sunscreen on a slide or other suitable analytical substrate, imaging the particles (e.g., using image capture hardware and software to capture an image of the IR sunscreen sample at an appropriate magnification), and then determining the maximum cross-sectional size of each particle (e.g., using image processing software to find the maximum cross-sectional size of each discrete particle present in the sample). Suitable magnification devices include optical microscopes or scanning electron microscopes (SEMs). The maximum cross-sectional sizes of all discrete particles are then averaged to determine the average maximum cross-sectional size of the sample. In some embodiments, the average maximum cross-sectional size of the IR sunscreen is greater than or equal to 50 nanometers and less than or equal to 1 centimeter. In some embodiments, the IR sunscreen has an average maximum cross-sectional dimension of greater than or equal to 50 nm, greater than or equal to 100 nm, greater than or equal to 250 nm, greater than or equal to 500 nm, greater than or equal to 1 micron, greater than or equal to 10 microns, greater than or equal to 25 microns, greater than or equal to 50 microns, greater than or equal to 100 microns, greater than or equal to 250 microns, greater than or equal to 500 microns, greater than or equal to 1 millimeter, and / or less than or equal to 1 centimeter, less than or equal to 5 millimeters, less than or equal to 1 millimeter, less than or equal to 100 microns, less than or equal to 50 microns, or less than or equal to 5 microns. In certain embodiments, it may be particularly advantageous if the IR sunscreen has a maximum cross-sectional dimension greater than or equal to 1 micron and less than or equal to 5 microns.
[0178] In some embodiments, the aerogel / foam combination can be carbonizable. In some embodiments, a carbonized derivative of the aerogel / foam combination can be produced. In some embodiments, the carbonized derivative of the aerogel / foam combination can be produced by pyrolysis. In some embodiments, the carbonized derivative is fibrous.
[0179] In some embodiments, the aerogel / foam material combination further comprises silica aerogel. In some embodiments, the aerogel / foam material combination further comprises trimethylsilyl-functionalized silica aerogel. In some embodiments, the aerogel / foam material combination further comprises trimethylsilyl-functionalized silica aerogel containing sodium ions. In some embodiments, the aerogel / foam material combination comprises discrete particles of silica aerogel. In some embodiments, the aerogel / foam material combination comprises discrete particles of trimethylsilyl-functionalized silica aerogel. In some embodiments, the aerogel / foam material combination comprises at least 0.001 wt%, at least 0.01 wt%, at least 0.1 wt%, and / or less than or equal to 25 wt%, less than or equal to 20 wt%, less than or equal to 15 wt%, less than or equal to 10 wt%, or less than or equal to 5 wt% of silica relative to the mass of the aerogel / foam material combination. In some embodiments, the addition of silica aerogel particles increases the hydrophobicity of the aerogel / foam material combination. Without wishing to be bound by any particular theory, it is believed that adding trimethylsilyl functionalized silica aerogels comprising sodium ions to polymer aerogels can increase the resistance of the polymer aerogels to absorption liquids comprising surfactants. In some embodiments, the increased resistance of the polymer aerogels to absorption liquids comprising surfactants can produce polymer aerogels that can be washed without significant increases in density, decreases in pore size, and / or changes in internal surface area after washing.
[0180] The aerogel material in the aerogel / foam material combination can have any of a variety of suitable properties. In some cases, polyimide aerogels can be particularly useful because they often exhibit one or more material properties that are particularly valuable for engineering applications.
[0181] In general, aerogels are dry, highly porous solid phase materials that can exhibit a variety of extreme and valuable material properties, such as low density, low thermal conductivity, high density normalized strength and stiffness, and / or high specific internal surface area. In some embodiments, the pore diameter within the aerogel material is less than or equal to 100 nm; and in some embodiments, the pore diameter within the aerogel material is between 2-50 nm, that is, the aerogel is a mesoporous aerogel. In some embodiments, the aerogel may contain pores with a diameter greater than 100 nm, and in some embodiments, the aerogel may even contain pores with a diameter of several microns. In some embodiments, at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 95%, at least 99% or more of the pore volume is composed of pores with a diameter less than or equal to 100 nm. In some embodiments, at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 95%, at least 99% or more of the pore volume is composed of pores with a diameter less than or equal to 50 nm. In some embodiments, it may be particularly advantageous if at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 95%, at least 99%, or more of the pore volume consists of pores having a diameter less than or equal to 25 nm. In some embodiments, the aerogel may comprise a unimodal pore distribution, a bimodal pore distribution, or a multimodal pore distribution.
[0182] In some embodiments, the polymer aerogel is hydrophobic.
[0183] In some embodiments, when measured according to standard ASTM C1511, the liquid water absorption rate of the aerogel can be less than or equal to 200 wt%, less than or equal to 150 wt%, less than or equal to 100 wt%, less than or equal to 80 wt%, less than or equal to 70 wt%, less than or equal to 60 wt%, less than or equal to 50 wt%, less than or equal to 40 wt%, less than or equal to 30 wt%, less than or equal to 20 wt%, less than or equal to 10 wt%, less than or equal to 5 wt%, less than or equal to 4 wt%, less than or equal to 3 wt%, less than or equal to 2 wt%, less than or equal to 1 wt%, or less than or equal to 0.1 wt% (and / or, in some embodiments, as little as 0.01 wt%, as little as 0.001 wt%, less than 0.0001 wt% or less). In some embodiments, the aerogel exhibits any of these properties after being subjected to a standard heating cycle in which the elevated temperature is 200°C (or 250°C, 300°C, or 350°C).
[0184] In some embodiments, when measured according to standard ASTM C1763, the liquid water absorption rate of the aerogel can be less than or equal to 200 wt%, less than or equal to 150 wt%, less than or equal to 100 wt%, less than or equal to 80 wt%, less than or equal to 70 wt%, less than or equal to 60 wt%, less than or equal to 50 wt%, less than or equal to 40 wt%, less than or equal to 30 wt%, less than or equal to 20 wt%, less than or equal to 10 wt%, less than or equal to 5 wt%, less than or equal to 4 wt%, less than or equal to 3 wt%, less than or equal to 2 wt%, less than or equal to 1 wt%, or less than or equal to 0.1 wt% (and / or, in some embodiments, as little as 0.01 wt%, as little as 0.001 wt%, less than 0.0001 wt% or less). In some embodiments, the aerogel exhibits any of these properties after being subjected to a standard heating cycle in which the elevated temperature is 200°C (or 250°C, 300°C, or 350°C).
[0185] In some embodiments, the liquid water absorption of the aerogel may be less than or equal to 200 wt%, less than or equal to 150 wt%, less than or equal to 100 wt%, less than or equal to 80 wt%, less than or equal to 70 wt%, less than or equal to 60 wt%, less than or equal to 50 wt%, less than or equal to 40 wt%, less than or equal to 30 wt%, less than or equal to 20 wt%, less than or equal to 10 wt%, less than or equal to 5 wt%, less than or equal to 4 wt%, less than or equal to 3 wt%, less than or equal to 2 wt%, less than or equal to 1 wt%, or less than or equal to 0.1 wt% (and / or, in some embodiments, as little as 0.01 wt%, as little as 0.001 wt%, less than 0.0001 wt% or less), relative to the weight of the aerogel before contact with liquid water, when measured according to standard EN 1609. In some embodiments, the aerogel exhibits any of these properties after being subjected to a standard heating cycle in which the elevated temperature is 200°C (or 250°C, 300°C, or 350°C).
[0186] In some embodiments, the water vapor absorption of the aerogel may be less than or equal to 100 wt%, less than or equal to 80 wt%, less than or equal to 70 wt%, less than or equal to 60 wt%, less than or equal to 50 wt%, less than or equal to 40 wt%, less than or equal to 30 wt%, less than or equal to 20 wt%, less than or equal to 10 wt%, less than or equal to 5 wt%, less than or equal to 4 wt%, less than or equal to 3 wt%, less than or equal to 2 wt%, less than or equal to 1 wt%, or less than or equal to 0.1 wt% (and / or, in some embodiments, as little as 0.01 wt%, as little as 0.001 wt%, as little as 0.0001 wt% or less) relative to the weight of the aerogel before exposure to water vapor when measured according to standard ASTM C1104. In some embodiments, the aerogel exhibits any of these properties after undergoing a standard heating cycle in which the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.)
[0187] In some embodiments, the aerogel may have a water contact angle greater than 90°, greater than 100°, greater than 110°, greater than 120°, greater than 130°, greater than 140°, greater than 150°, greater than 160°, greater than 170° (and / or, in some embodiments, up to 175°, up to 178°, up to 179°, up to 179.9° or more) when measured according to standard ASTM D7490 in an ambient air environment of 1 atm and 25° C. It is particularly advantageous that the aerogel exhibits a contact angle with water greater than 90°, greater than 100°, greater than 110°, greater than 120°, greater than 130°, greater than 140°, greater than 150°, greater than 160°, greater than 170° (and / or, in some embodiments, up to 175°, up to 178°, up to 179°, up to 179.9° or more). In some embodiments, the aerogel exhibits any of these properties after being subjected to a standard heating cycle in which the elevated temperature is 200°C (or 250°C, 300°C, or 350°C).
[0188] According to certain embodiments, the hydrophobic aerogel does not contain any fluorine or contains only a limited amount of fluorine (eg, the amount of fluorine in the aerogel is 0-0.1 wt%, 0-0.01 wt%, or 0-0.001 wt%).
[0189] In some embodiments, the polymer aerogel has anti-surfactant properties. In some embodiments, the polymer aerogel is washable. In some embodiments, the polymer aerogel has a relatively low detergent absorption rate. The detergent absorption rate can be determined according to the following test. 0.97g of sodium dodecyl sulfate is added to 1 liter of analytical reagent grade deionized (DI) water and dissolved to make a detergent solution. 50mL of detergent solution is added to a cylindrical vial 1.5 inches high by 3 inches wide. A sample of a 1cm x 1cm x 2mm aerogel is prepared and added to the vial. The mesh cloth is pressed into the vial so that the sample remains completely immersed at 20°C for 24 hours. The sample is then removed from the detergent solution and the surface liquid is removed mechanically. The sample is then weighed. The difference between the mass of the sample after the test and before the test is the detergent absorption rate, and is usually expressed as a percentage of the mass increase relative to the original mass of the sample. In some embodiments, the polymer aerogel exhibits a detergent absorption rate according to this test of less than or equal to 300%, less than or equal to 200%, less than or equal to 100%, less than or equal to 50%, less than or equal to 10%, less than or equal to 5%, less than or equal to 1% (and / or, as little as 0.1%, as little as 0.01%, as little as 0.001% or less).
[0190] In some embodiments, the bulk density of the polymer aerogel (e.g., polyimide aerogel) can be greater than or equal to 0.01 g / cc, greater than or equal to 0.05 g / cc, greater than or equal to 0.1 g / cc, greater than or equal to 0.2 g / cc, greater than or equal to 0.3 g / cc, greater than or equal to 0.4 g / cc, greater than or equal to 0.5 g / cc, greater than or equal to 0.6 g / cc, greater than or equal to 0.7 g / cc, or less than or equal to 0.8 g / cc. In certain embodiments, the bulk density of the polyimide aerogel can be between 0.01 g / cc and 0.8 g / cc. In some embodiments, it may be particularly advantageous if the polyimide aerogel exhibits a bulk density greater than or equal to 0.01 g / cc and less than or equal to 0.5 g / cc when separated from the melamine formaldehyde foam.
[0191] The aerogel can exhibit any of a variety of suitable skeletal densities. In some embodiments, the aerogel has a skeletal density greater than or equal to 1 g / cc, greater than or equal to 1.2 g / cc, greater than or equal to 1.3 g / cc, greater than or equal to 1.4 g / cc, greater than or equal to 1.5 g / cc, greater than or equal to 1.6 g / cc, greater than or equal to 1.7 g / cc, greater than or equal to 1.8 g / cc, greater than or equal to 1.9 g / cc, greater than or equal to 2.0 g / cc, greater than or equal to 2.1 g / cc, greater than or equal to 2.2 g / cc, greater than or equal to 2.3 g / cc, In some embodiments, the aerogel exhibits any of these properties after being subjected to a standard heating cycle in which the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0192] In certain embodiments, the thermal conductivity of the aerogel at 25° C. as measured by the CHP method (described above) may be less than or equal to 100 mW / m·K, less than or equal to 75 mW / m·K, less than or equal to 50 mW / m·K, less than or equal to 35 mW / m·K, less than or equal to 25 mW / m·K, less than or equal to 23 mW / m·K, less than or equal to 20 mW / m·K, less than or equal to 15 mW / m·K, or less than or equal to 12 mW / m·K, and / or greater than or equal to 0.1 mW / m·K, greater than or equal to 1 mW / m·K, greater than or equal to 2 mW / m·K, greater than or equal to 5 mW / m·K, or greater than or equal to 15 mW / m·K. In some embodiments, it may be particularly advantageous if the aerogel exhibits a thermal conductivity of less than or equal to 30 mW / m·K, or less than or equal to 25 mW / m·K at 25° C. In some embodiments, the aerogel exhibits any of these properties after being subjected to a standard heating cycle in which the elevated temperature is 200°C (or 250°C, 300°C, or 350°C).
[0193] In some embodiments, the aerogel has a BET surface area greater than or equal to 5 m 2 / g, greater than or equal to 50m 2 / g, greater than or equal to 100m 2 / g, greater than or equal to 200m 2 / g, greater than or equal to 300m2 / g, greater than or equal to 400m 2 / g, greater than or equal to 500m 2 / g, greater than or equal to 600m 2 / g, greater than or equal to 700m 2 / g, greater than or equal to 800m 2 / g, greater than or equal to 1000m 2 / g, greater than or equal to 2000m 2 / g, greater than or equal to 3000m 2 / g, and / or less than or equal to 1500m 2 / g, or less than or equal to 4000m 2 / g. In some embodiments, the BET surface area of the aerogel is greater than or equal to 5m 2 / g and less than or equal to 4000m 2 In some embodiments, the aerogel exhibits any of these properties after being subjected to a standard heating cycle in which the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0194] The aerogel may exhibit any of a variety of suitable pore structures. In some embodiments, the aerogel comprises pores less than or equal to 100 microns, less than or equal to 10 microns, less than or equal to 1 micron, less than or equal to 500 nm, less than or equal to 250 nm, less than or equal to 100 nm, less than or equal to 50 nm, less than or equal to 25 nm, less than or equal to 20 nm, less than or equal to 15 nm, and / or less than or equal to 10 nm. In some embodiments, the aerogel comprises pores greater than or equal to 10 nm, greater than or equal to 15 nm, greater than or equal to 20 nm, greater than or equal to 25 nm, greater than or equal to 50 nm, greater than or equal to 100 nm, greater than or equal to 250 nm, greater than or equal to 500 nm, greater than or equal to 1 micron, greater than or equal to 10 microns, and / or greater than or equal to 100 microns. In some embodiments, the average pore width of the aerogel is less than or equal to 10 nm, less than or equal to 20 nm, less than or equal to 30 nm, less than or equal to 40 nm, less than or equal to 50 nm, less than or equal to 60 nm, less than or equal to 70 nm, less than or equal to 80 nm, less than or equal to 90 nm, less than or equal to 100 nm, less than or equal to 500 nm, less than or equal to 1 μm, less than or equal to 10 μm, less than or equal to 100 μm, or less than or equal to 1 mm. In some embodiments, the aerogel exhibits a BJH average pore size greater than or equal to 2 nm and less than or equal to 50 nm when measured using nitrogen adsorption. In some embodiments, the aerogel exhibits a BJH average pore size greater than or equal to 10 nm and less than or equal to 25 nm when measured using nitrogen adsorption. In some embodiments, the aerogel exhibits any of these properties after undergoing a standard heating cycle in which the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0195] In some embodiments, the pore width distribution of the aerogel can be unimodal (i.e., exhibit a single maximum). In some embodiments, the pore width distribution maximum is found to be located at less than or equal to 10 nm, less than or equal to 20 nm, less than or equal to 30 nm, less than or equal to 40 nm, less than or equal to 50 nm, less than or equal to 60 nm, less than or equal to 70 nm, less than or equal to 80 nm, less than or equal to 90 nm, less than or equal to 100 nm, less than or equal to 500 nm, less than or equal to 1 μm, less than or equal to 10 μm, less than or equal to 100 μm, or less than or equal to 1 mm. In some embodiments, the aerogel comprises a unimodal pore size distribution. In some embodiments, the aerogel exhibits any of these characteristics after undergoing a standard heating cycle in which the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0196] In some embodiments, the pore width distribution of the aerogel can be bimodal, or at least bimodal. In some embodiments, the aerogel can have two different pore populations, one pore population having an average pore size less than or equal to a certain critical pore width, and the other pore population having an average pore size greater than a certain critical pore width. In some embodiments, the critical pore width is less than or equal to 10 nm, less than or equal to 20 nm, less than or equal to 30 nm, less than or equal to 40 nm, less than or equal to 50 nm, less than or equal to 60 nm, less than or equal to 70 nm, less than or equal to 80 nm, less than or equal to 90 nm, less than or equal to 100 nm, less than or equal to 500 nm, less than or equal to 1 μm, less than or equal to 10 μm, less than or equal to 100 μm, or less than or equal to 1 mm. In some embodiments, the aerogel comprises a bimodal pore size distribution. In some embodiments, the aerogel exhibits any of these properties after undergoing a standard heating cycle in which the elevated temperature is 200°C (or 250°C, 300°C, or 350°C).
[0197] In some embodiments, the aerogel exhibits a surface area greater than or equal to 0.05 cm 3 / g and less than or equal to 5cm 3 / g BJH pore volume. In some embodiments, the aerogel exhibits a BJH pore volume greater than or equal to 0.05 g / cm 3 , greater than or equal to 1g / cm 3 , greater than or equal to 2g / cm 3 , greater than or equal to 3g / cm 3 , greater than or equal to 4g / cm 3 , and / or less than or equal to 5g / cm 3 In some embodiments, the aerogel exhibits any of these properties after being subjected to a standard heating cycle in which the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0198] In some embodiments, the aerogel can exhibit an internal specific surface area. In some embodiments, the aerogel has a BET surface area greater than or equal to 5 m 2 / g, greater than or equal to 50m 2 / g, greater than or equal to 100m 2 / g, greater than or equal to 200m 2 / g, greater than or equal to 300m 2 / g, greater than or equal to 400m 2 / g, greater than or equal to 500m 2 / g, greater than or equal to 600m 2 / g, greater than or equal to 700m 2 / g, greater than or equal to 800m 2 / g, greater than or equal to 1000m 2 / g, greater than or equal to 2000m 2 / g, greater than or equal to 3000m 2 / g, and / or less than or equal to 1500m 2 / g, or less than or equal to 4000m 2 / g. In some embodiments, the BET surface area of the aerogel is greater than or equal to 5m 2 / g and less than or equal to 4000m 2 / g. In some embodiments, if the aerogel exhibits a gravitational field greater than or equal to 100 m 2 / g and less than or equal to 800m 2 A BET surface area of 200 m / g may be particularly advantageous. Aerogels may have BET surface area values outside these ranges. In certain embodiments, aerogels exhibiting a BET surface area greater than or equal to 200 m / g may have a BET surface area greater than or equal to 200 m / g. 2 / g and less than or equal to 400m 2 In some embodiments, the aerogel exhibits any of these properties after being subjected to a standard heating cycle in which the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0199] In certain embodiments, the compression modulus of the aerogel is greater than or equal to 100 kPa, greater than or equal to 500 kPa, greater than or equal to 1 MPa, greater than or equal to 10 MPa, greater than or equal to 50 MPa, greater than or equal to 100 MPa, and / or less than or equal to 100 MPa, less than or equal to 50 MPa, less than or equal to 10 MPa, less than or equal to 1 MPa, less than or equal to 500 kPa, less than or equal to 100 kPa, or less than or equal to 50 kPa. The compression modulus of the aerogel may be a combination of the above ranges or a value outside these ranges. In some embodiments, it may be particularly advantageous if the aerogel exhibits a compression modulus greater than or equal to 1 MPa. In some embodiments, the aerogel exhibits any of these properties after undergoing a standard heating cycle in which the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0200] The aerogel may exhibit any of a variety of suitable compressive yield strengths. In certain embodiments, the compressive yield strength of the aerogel is greater than or equal to 40 kPa, greater than or equal to 100 kPa, greater than or equal to 500 kPa, greater than or equal to 1 MPa, greater than or equal to 5 MPa, greater than or equal to 10 MPa, greater than or equal to 50 MPa, greater than or equal to 100 MPa, greater than or equal to 500 MPa, and / or less than or equal to 500 MPa, less than or equal to 100 MPa, less than or equal to 50 MPa, less than or equal to 10 MPa, less than or equal to 5 MPa, less than or equal to 1 MPa, less than or equal to 1 MPa, less than or equal to 500 kPa, less than or equal to 100 kPa, or less than or equal to 50 kPa. The compressive yield strength of the aerogel may be a combination of the above ranges or values outside these ranges. In some embodiments, it may be particularly advantageous if the aerogel exhibits a compressive yield strength greater than or equal to 300 kPa. In some embodiments, the aerogel exhibits any of these properties after being subjected to a standard heating cycle in which the elevated temperature is 200°C (or 250°C, 300°C, or 350°C).
[0201] In certain embodiments, the flexural modulus of the aerogel as measured by the methods described herein can be at least 0.00689 MPa, at least 0.01 MPa, at least 0.02 MPa, at least 0.03 MPa, at least 0.04 MPa, at least 0.05 MPa, at least 0.06 MPa, at least 0.07 MPa, at least 0.08 MPa, at least 0.09 MPa, at least 0.1 MPa, at least 0.2 MPa, at least 0.3 MPa, at least 0.4 MPa, at least 0.5 MPa, at least 0.6 MPa. a, at least 0.7 MPa, at least 0.8 MPa, at least 0.9 MPa, at least 1 MPa, at least 2 MPa, at least 5 MPa, at least 10 MPa, at least 20 MPa, at least 50 MPa, at least 100 MPa, at least 200 MPa, at least 300 MPa, and / or less than or equal to 1 GPa, less than or equal to 500 MPa, less than or equal to 300 MPa, less than or equal to 200 MPa, less than or equal to 100 MPa, less than or equal to 50 MPa, and / or less than or equal to 20 MPa. In some embodiments, it may be particularly advantageous if the aerogel exhibits a flexural modulus greater than or equal to 1 MPa. In some embodiments, the aerogel exhibits any of these properties after undergoing a standard heating cycle in which the elevated temperature is 200° C. (or 250° C., 300° C., or 350° C.).
[0202] In some embodiments, the aerogel has a flexural strength greater than or equal to 0.00689 MPa, at least 0.01 MPa, at least 0.02 MPa, at least 0.03 MPa, at least 0.04 MPa, at least 0.05 MPa, at least 0.06 MPa, at least 0.07 MPa, at least 0.08 MPa, at least 0.09 MPa, at least 0.1 MPa, at least 0.2 MPa, greater than or equal to 0.5 MPa, greater than or equal to 1 MPa, greater than or equal to 1.5 MPa, greater than or equal to 2 MPa, greater than or equal to 2.5 MPa, greater than or equal to 3 MPa, greater than or equal to 3.5 MPa, or greater than or equal to 4 MPa, at least 5 MPa, at least 10 MPa, at least 20 MPa, at least 50 MPa, at least 100 MPa, at least 200 MPa, at least 300 MPa, and / or less than or equal to 1 GPa. In some embodiments, it may be particularly advantageous if the aerogel exhibits a flexural strength greater than or equal to 0.5 MPa.In some embodiments, the aerogel exhibits any of these properties after being subjected to a standard heating cycle with an elevated temperature of 200°C (or 250°C, 300°C, or 350°C).
[0203] In some embodiments, the aerogel of the aerogel / foam material combination comprises a polymer aerogel. A polymer aerogel is an aerogel made at least in part of a polymer material. In some embodiments, at least 25wt%, at least 50wt%, at least 75wt%, at least 90wt%, at least 95wt%, at least 98wt%, at least 99wt%, at least 99.9wt% or all of the polymer aerogel is made of a polymer material. In some embodiments, at least 25wt%, at least 50wt%, at least 75wt%, at least 90wt%, at least 95wt%, at least 98wt%, at least 99wt%, at least 99.9wt% or all of the polymer aerogel is made of an organic polymer (i.e., a polymer having carbon atoms in its backbone).
[0204] In some embodiments, the aerogel of the aerogel / foam material combination comprises a polyimide aerogel. A polyimide aerogel is an aerogel made at least in part of a polyimide material. In some embodiments, at least 25 wt%, at least 50 wt%, at least 75 wt%, at least 90 wt%, at least 95 wt%, at least 98 wt%, at least 99 wt%, at least 99.9 wt%, or all of the polymer aerogel is composed of polyimide.
[0205] Aerogels containing polyimides can potentially combine a variety of valuable material properties into a single material package, including but not limited to: high-quality normalized strength and stiffness properties, low density, low and constant dielectric constant and loss tangent over a wide frequency range, low sound velocity, high sound transmission loss, low flammability or non-flammability, machinability, and low thermal conductivity. Potential applications of aerogels containing polyimides include aircraft interior parts, such as wall panels, floor panels, cockpit doors, and kitchen furniture; automotive engine hoods; shock wave reflecting and / or energy absorbing materials in ballistic shields; insulating components for shoes, boots, and shoe insoles; shock absorbing and soundproofing materials for rocket fairings; low-k substrates for electronics and antennas; and other applications. Most commercial polyimide materials, such as thin films and bulk plastics, traditionally contain hydrophilic polymers, i.e., they absorb and retain moisture and / or liquid water. Therefore, most aerogels containing polyimides are also hydrophilic. However, many potential engineering applications of polyimide aerogels require materials that can resist contact with water in liquid and / or vapor phases without degradation, significant weight gain, or performance degradation. Therefore, aerogels comprising polyimides that also exhibit water-resistant properties are highly desirable for many applications. Therefore, in some embodiments, the aerogel comprises a hydrophobic polyimide portion. FIG. 3A to FIG. 3B Schematically depicted is a hydrophobic polyimide portion of an aerogel, which may be used according to certain embodiments. The hydrophobic portion may impart at least some hydrophobicity to the aerogel (or combination of materials comprising the aerogel).
[0206] In some embodiments, the polyimide aerogel comprises the following moieties [M1]:
[0207]
[0208] FIG. 3A to FIG. 3BAlso shown in the figure is part [M1]. Dashed lines indicate points of attachment to other parts. In some embodiments, the polyimide aerogel comprises repeating units of part [M1]. In some embodiments, the polyimide aerogel comprises at least 2, at least 3, at least 4, at least 5, at least 10, at least 15, at least 20, at least 30, at least 40 and / or at least 50 repeating units of part [M1]. In some embodiments, the aerogel comprises 2 to 20 repeating units of part [M1]. In some cases, part [M1] may account for at least 50 wt%, at least 60 wt%, at least 70 wt%, at least 80 wt%, at least 90 wt%, at least 95 wt% and / or at least 99 wt% of the polymer in the aerogel. In some embodiments, at least 50 wt%, at least 60 wt%, at least 70 wt%, at least 80 wt%, at least 90 wt%, at least 95 wt% and / or at least 99 wt% of the aerogel is composed of part [M1]. In some embodiments it may be particularly advantageous if at least 90 wt % of the aerogel consists of fraction [M1].
[0209] In some preferred embodiments, the moiety comprises a specific repeating octamer of the reaction products of four monomers, having the following order, with the understanding that the imide groups replace the amine and anhydride from the monomers accordingly: biphenyl-3,3',4,4'-tetracarboxylic dianhydride (BPDA), then 2,2'-dimethylbenzidine (DMBZ), then BPDA, then 4,4'-[1,3-phenylbis(1-methyl-ethylene)]dianiline (dianiline-m), then BPDA, then 4,4'-diaminodiphenyl ether (ODA), then BPDA, then dianiline-m. In some preferred embodiments, polyimide aerogels comprising the moiety exhibit excellent strength, stiffness, flexibility, machinability, low thermal conductivity, low flammability, and / or high water resistance.
[0210] In some preferred embodiments, the polyimide chains comprising the moiety [M1] are interconnected by a crosslinker. In some embodiments, the pattern of the specific alternating composition monomers derived from the moiety [M1] produces the hydrophobic and / or water-resistant properties of the polyimide aerogel. Without wishing to be bound by any particular theory, the moiety [M1] can impart enhanced water resistance to the polyimide aerogel because it has a high density of aromatic, isopropyl and methyl groups (which are all hydrophobic groups) to offset the inherent hydrophilicity of the imide groups. Without wishing to be bound by any particular theory, the addition of an ODA unit comprising a flexible oxygen bridge can impart flexibility to the moiety, which provides reduced brittleness to the polyimide aerogel compared to a moiety that does not comprise a flexible oxygen bridge.
[0211] In some embodiments, the polyimide aerogel comprises one or more of the following:
[0212]
[0213]
[0214] Polyimide aerogels can be made using any of a variety of methods.
[0215] In some embodiments, the polyimide gel suitable for producing polyimide aerogel is prepared by the reaction of one or more amines and one or more anhydrides. In some embodiments, the amine can be a monoamine, a diamine or a polyamine. In some embodiments, the anhydride can be a monoanhydride, a dianhydride or a polyanhydride. In some embodiments, the amine and the anhydride react to form a poly(amic acid), which is then imidized to form a polyimide. In certain embodiments, the poly(amic acid) is chemically imidized. In some embodiments, the poly(amic acid) is thermally imidized.
[0216] In some embodiments of forming a polyimide aerogel, biphenyl-3,3',4,4'-tetracarboxylic dianhydride (BPDA), 2,2'-dimethylbenzidine (DMBZ) and 4,4'-diaminodiphenyl ether (4,4-ODA or ODA) are combined to form an anhydride-terminated poly (amic acid) oligomer, wherein the oligomer comprises repeating units of the reaction product of BPDA, ODA and DMBZ, for example, units of the reaction product of BPDA-ODA-BPDA-DMBZ, and comprises terminal anhydride and / or amine groups, and the oligomer has an average degree of polymerization (number of repeating units) of 10 to 50. In some embodiments, the oligomer is crosslinked by a crosslinking agent (also referred to as a crosslinker). In some embodiments, the crosslinking agent comprises three or more amine groups. In some embodiments, the crosslinking agent comprises a functional group that reacts with the terminal groups on the oligomer to produce a crosslinker-terminated oligomer. In certain embodiments, the crosslinking agent comprises a functional group that reacts with another crosslinking agent molecule to link the crosslinking agent-terminated oligomer together. In certain embodiments, the crosslinking agent is introduced with a balanced stoichiometry of the functional group on the crosslinking agent, and the crosslinking agent is reactive to the terminal groups on the polyimide oligomer and even to the complementary terminal groups on the polyimide oligomer. In certain embodiments, chemical imidization (e.g., by adding acetic anhydride (AA)) is carried out to produce a porous, highly crosslinked polyimide network. In certain embodiments, two or more oligomers are connected to the same crosslinking agent. In certain embodiments, chemical imidization is carried out to produce a porous crosslinked polyimide network to the obtained network. In certain embodiments, before crosslinking, oligomer is imidized. In certain embodiments, oligomer is imidized simultaneously with crosslinking.
[0217] In some embodiments of forming a polyimide aerogel, the method includes combining a certain amount of biphenyl-3,3',4,4'-tetracarboxylic dianhydride (BPDA), a first diamine, and a solvent. This combination can be performed in any of a variety of ways. Some embodiments include first combining BPDA and a solvent and then adding the first diamine. Other embodiments include first combining the first diamine and a solvent and then adding BPDA. Still other embodiments include combining BPDA, the first diamine, and a solvent simultaneously.
[0218] In some embodiments of forming a polyimide aerogel, amounts of BPDA, a first diamine, and a solvent are combined such that a first intermediate medium comprising an anhydride terminated poly(amic acid) trimer is formed.
[0219] In some embodiments of forming a polyimide aerogel, the method includes combining a first intermediate medium and a second diamine. In some embodiments, the first intermediate medium and the second diamine are combined such that a second intermediate medium comprising a pentamer is formed.
[0220] In some embodiments of forming a polyimide aerogel, the method includes combining the second intermediate with an additional amount of BPDA. In certain embodiments, the second intermediate and the additional amount of BPDA are combined such that a third intermediate comprising a heptamer is formed.
[0221] In some embodiments of forming a polyimide aerogel, the method includes combining a third intermediate medium and a third diamine such that a fourth intermediate medium is formed. In certain embodiments, the third intermediate medium and the third diamine are combined such that a fourth intermediate medium comprising oligomer chains is formed.
[0222] In some embodiments of forming polyimide aerogel, the method includes combining the fourth intermediate medium and a crosslinking agent. In some embodiments, the fourth intermediate medium and the crosslinking agent are combined to form a gel. In some embodiments, the crosslinking agent comprises three or more amine groups. In some embodiments, the crosslinking agent comprises a functional group that reacts with the end groups on the oligomer to produce a crosslinker-terminated oligomer. In some embodiments, the crosslinking agent comprises a functional group that reacts with another crosslinking agent molecule and / or another crosslinker-terminated oligomer to connect the crosslinker-terminated oligomer together. In some embodiments, the crosslinking agent is introduced with a balanced stoichiometry of the functional groups on the crosslinking agent, and the crosslinking agent is reactive to the end groups on the polyimide oligomer and even to the complementary end groups on the polyimide oligomer. In some embodiments, two or more oligomers are connected to the same crosslinking agent. In some embodiments, the resulting network is chemically imidized to produce a porous crosslinked polyimide network. In some embodiments, the oligomer is imidized before crosslinking. In some embodiments, the oligomer is imidized simultaneously with crosslinking.
[0223] In some embodiments of forming a polyimide aerogel, the crosslinking agent includes a triamine; an aliphatic triamine; an aromatic amine containing three or more amine groups; an aromatic triamine; 1,3,5-tris(aminophenoxy)benzene (TAB); tris(4-aminophenyl)methane (TAPM); tris(4-aminophenyl)benzene (TAPB); tris(4-aminophenyl)amine (TAPA); 2,4,6-tris(4-aminophenyl)pyridine (TAPP); 4,4',4"-methanetriyltriphenylamine; N,N,N',N'-tetrakis(4-aminophenyl)-1,4-phenylenediamine; polyoxypropylene triamine; N',N'-bis(4-aminophenyl)benzene-1,4-diamine; triisocyanates; aliphatic triisocyanates; aromatic isocyanates containing three or more isocyanate groups; aromatic triisocyanates; triisocyanates based on hexamethylene diisocyanate; trimers of hexamethylene diisocyanate; hexamethylene diisocyanate; polyisocyanates; polyisocyanates including isocyanurates; Desmodur N3200; Desmodur N3300; Desmodur N100; Desmodur N3400; Desmodur N3390; Desmodur N3390 BA / SN; Desmodur N3300 BA; Desmodur N3600; Desmodur N3790 BA; 2675; Desmodurbulogiq 3190; Desmodur XP 2860; Desmodur N3400; Desmodur XP 2840; Desmodur N3580BA; MR; Mondur MRS; diphenylmethane diisocyanate; diphenylmethane 2,2'-, 2,4'- and / or 4,4'-diisocyanate (MDI); naphthalene 1,5-diisocyanate (NDI); toluene diisocyanate; toluene 2,4- and / or 2,6-diisocyanate (TDI); 3,3'-dimethylbiphenyl diisocyanate; 1,2-diphenylethane diisocyanate and / or p-phenylene diisocyanate (PPDI); trimethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, heptamethylene diisocyanate and / or octamethylene diisocyanate; 2-methylpentamethylene 1,5-diisocyanate; 2-ethylbutylene 1,4-diisocyanate; pentamethylene 1,5-diisocyanate; butylene 1,4-diisocyanate; 1-isocyanato-3,3 ,5-trimethyl-5-isocyanatomethylcyclohexane (isophorone diisocyanate, IPDI); 1,4- and / or 1,3-bis(isocyanatomethyl)cyclohexane (HXDI); cyclohexane 1,4-diisocyanate; 1-methylcyclohexane 2,4- and / or 2,6-diisocyanate; dicyclohexylmethane 4,4'-, 2,4'- and / or 2,2'-diisocyanate; octa(aminophenoxy) (4,4-diaminodiphenyl ether (ODA); (3-aminopropyl)triethoxysilane (APTES); modified graphene oxide (m-GO); 1,3,5-benzene trimesoyl trichloride (BTC); poly(maleic anhydride) (PMA); imidazole or substituted imidazole; triazole or substituted triazole; purine or substituted purine; pyrazole or substituted pyrazole; and / or melamine.
[0224] In some embodiments of forming a polyimide aerogel, the crosslinking agent includes isocyanurate groups, siloxy bridges, trisubstituted benzene rings, silsesquioxane groups, phenoxy groups, tri(phenyl)methyl groups, imidazole groups, and / or alkyl groups.
[0225] In some embodiments forming a polyimide aerogel, the first diamine is different from the second diamine and the third diamine. In certain embodiments, the second diamine is different from the third diamine.
[0226] In some embodiments of forming a polyimide aerogel, the first diamine, the second diamine, and the third diamine are selected from the group consisting of: 3,4'-diaminodiphenyl ether (3,4-ODA); 4,4'-diaminodiphenyl ether (4,4-ODA or ODA); p-phenylenediamine (pPDA); m-phenylenediamine (mPDA); p-phenylenediamine (mPDA); 2,2'-dimethylbenzidine (DMBZ); 4,4'-bis(4-aminophenoxy)biphenyl; 2,2'-bis[4-(4-aminophenoxy)phenyl]propane; dianiline-p-xylidine (BAX); 4,4'-methylenedianiline (MDA); 4,4'-[1,3-phenylenebis(1-methyl-ethylene)]dianiline ( diphenylamine-m); 4,4'-[1,4-phenylenebis(1-methyl-ethylene)] diphenylamine (diphenylamine-p); 3,3'-dimethyl-4,4'-diaminobiphenyl (o-tolidine); 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP); 3,3'-dihydroxy-4,4'-diaminobiphenyl (HAB); 3,3'-diaminodiphenyl sulfone (3,3'-DDS); 4,4'-diaminodiphenyl sulfone (4,4'-DDS); 4,4'-diaminodiphenyl sulfide (ASD); 2,2-bis[4-(4-aminophenoxy)phenyl]sulfone (BAPS); 2,2-bis[4-(3-aminophenoxy)benzene] (m-BAPS); 1 ,4-bis(4-aminophenoxy)benzene (TPE-Q); 1,3-bis(4-aminophenoxy)benzene (TPE-R); 1,3'-bis(3-aminophenoxy)benzene (APB-133); 4,4'-bis(4-aminophenoxy)biphenyl (BAPB); 4,4'-diaminobenzanilide (DABA); 9,9'-bis(4-aminophenyl)fluorene (FDA); o-tolidine sulfone (TSN); methylenebis(o-aminobenzoic acid) (MBAA); 1,3'-bis(4-aminophenoxy)-2,2-dimethylpropane (DANPG); 2,3,5,6-tetramethyl-1,4-phenylenediamine (TMPD); 3,3',5,5'-tetramethylbenzidine (3355TMB); 1,5-bis(4-aminophenoxy)pentane (DA5MG); 2,5-diaminobenzotrifluoride (25DBTF); 3,5-diaminobenzotrifluoride (35DBTF); 1,3-diamino-2,4,5,6-tetrafluorobenzene (DTFB); 2,2'-bis(trifluoromethyl)benzidine (22TFMB); 3,3'-bis(trifluoromethyl)benzidine (33TFMB); 2,2-bis[4-(4-aminophenoxyphenyl)]hexafluoropropane (HFBAPP); 2,2-bis(4-aminophenyl)hexafluoropropane (Bis-A-AF); 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (Bis-AP-AF);2,2-Bis(3-amino-4-methylphenyl)hexafluoropropane (Bis-AT-AF); o-phenylenediamine; diaminobenzanilide; 3,5-diaminobenzoic acid; 3,3'-diaminodiphenyl sulfone; 4,4'-diaminodiphenyl sulfone; l,3-bis(4-aminophenoxy)benzene; l,3-bis(3-aminophenoxy)benzene; 1,4-bis(4-aminophenoxy)benzene; l,4-bis(3-aminophenoxy)benzene; 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane; 2,2-bis(3-aminophenyl)hexafluoropropane; 4,4'-isopropylenediamine; l-(4-aminophenoxy)-3-(3-aminophenoxy)benzene; l-(4-aminophenoxy)-4-(3-aminophenoxy) 1,2-Diaminobenzene; 4,4'-diaminodiphenylmethane; 2,2-Bis(4-aminophenyl)propane; 4,4'-diaminodiphenylpropane; 4,4'-diaminodiphenyl sulfide; 4,4-diaminodiphenyl sulfone; 3,4'-diaminodiphenyl ether; 4,4'-diaminodiphenyl ether; 2,6-Diaminopyridine; bis(3-aminophenyl)diethylsilane; 4,4'-diaminodiphenyldiethylsilane; 3'-diaminodiphenylbenzene ...3'-diaminodiphenylbenzene; 3'-diaminodiphenylbenzene; 3'-diaminodiphenylbenzene; 3'-diaminodiphenylbenzene; 3'-diaminodiphenylbenzene; 3'-diaminodiphenylbenzene; 3'-diaminodiphenylbenzene; 3'-diaminodiphenylbenzene; 3' Chlorobenzidine; 3,3'-dimethoxybenzidine; 4,4'-diaminobenzophenone; N,N-bis(4-aminophenyl)butylamine; N,N-bis(4-aminophenyl)methylamine; 1,5-diaminonaphthalene; 3,3'-dimethyl-4,4'-diaminobiphenyl; 4-aminophenyl-3-aminobenzoate; N,N-bis(4-aminophenyl)aniline; di(p-β-aminotert-butylphenyl)ether; p-bis-2-(2-methyl-4-aminopentyl)benzene; p-bis(1,1-dimethyl-5-aminopentyl)benzene; l,3-bis(4-aminophenoxy)benzene; m-xylenediamine; p-xylenediamine; 4,4'-diaminodiphenyl ether phosphine oxide; 4,4'-diaminodiphenyl N-methylamine; 4,4' -diaminodiphenyl N-aniline; amino-terminated polydimethylsiloxane; amino-terminated polypropylene oxide; amino-terminated polybutylene oxide; 4,4'-methylenebis(2-methylcyclohexylamine); 1,2-diaminoethane; 1,3-diaminopropane; 1,4-diaminobutane; 1,5-diaminopentane; 1,6-diaminohexane; 1,7-diaminoheptane; 1,8-diaminooctane; 1,9-diaminononane; 1,10-diaminodecane; 4,4'-methylenebis(aniline); 2,2'-dimethylbenzidine; dianiline-p-xylidine; 4,4'-bis(4-aminophenoxy)biphenyl; 3,3'-bis(4-aminophenoxy)biphenyl; 4,4'-(1,4-phenylenediisopropylidene)dianiline;and / or 4,4'-(1,3-phenylene diisopropylidene) dianiline. ;
[0227] In some embodiments of forming a polyimide aerogel, the first diamine, the second diamine, and the third diamine are selected from the group consisting of 2,2'-dimethylbenzidine (DMBZ), 4,4'-diaminodiphenyl ether (4,4-ODA), and 4,4'-[1,3-phenylenebis(1-methyl-ethylene)] dianiline (dianiline-m). In some embodiments, it may be particularly advantageous if the first, second, or third diamine is dianiline-m.
[0228] In some embodiments of forming polyimide aerogels, the first diamine is DMBZ, the second diamine is 4,4-ODA, and the third diamine is dianiline-m. In certain embodiments, the first diamine is dianiline-m, the second diamine is DMBZ, and the third diamine is 4,4-ODA. In certain embodiments, the first diamine is dianiline-m, the second diamine is 4,4-ODA, and the third diamine is DMBZ. In certain embodiments, the first diamine is 4,4-ODA, the second diamine is DMBZ, and the third diamine is dianiline-m. In certain embodiments, the first diamine is 4,4-ODA, the second diamine is DMBZ, and the third diamine is dianiline-m. In certain embodiments, it may be particularly advantageous if the first diamine is DMBZ, the second diamine is dianiline-m, and the third diamine is 4,4-ODA.
[0229] In some embodiments of forming a polyimide aerogel, combining an amount of BPDA, a first diamine, and a solvent comprises combining the first diamine and an amount of BPDA in relative amounts between 0.9:1 and 1.1:1, between 1.4:1 and 1.6:1, between 1.6:1 and 1.8:1, between 1.9:1 and 2.1:1, and / or between 2.9:1 and 3.1:1, based on the ratio of the amount of BPDA to the first diamine. In some embodiments, it may be particularly advantageous if combining an amount of BPDA, a first diamine, and a solvent comprises combining the first diamine and an amount of BPDA in relative amounts between 1.9:1 and 2.1:1 (based on the ratio of the amount of BPDA to the first diamine). In some embodiments, combining the first intermediate medium and the second diamine comprises combining the anhydride-terminated poly(amic acid) trimer and the second diamine in a relative amount, based on a molar ratio of the second diamine to the anhydride-terminated poly(amic acid) trimer, between 0.9:1 and 1.1:1, between 1.4:1 and 1.6:1, between 1.6:1 and 1.8:1, between 1.9:1 and 2.1:1, and / or between 2.9:1 and 3.1:1. In some embodiments, it may be particularly advantageous if combining the first intermediate medium and the second diamine comprises combining the anhydride-terminated poly(amic acid) trimer and the second diamine in a relative amount, wherein the relative amount is between 1.9:1 and 2.1:1 based on a molar ratio of the second diamine to the anhydride-terminated poly(amic acid) trimer. In some embodiments, combining the second intermediate medium with the additional amount of BPDA comprises combining the pentamer with the additional amount of BPDA in a relative amount based on a molar ratio of the additional amount of BPDA to the pentamer of between 0.9:1 and 1.1:1, between 1.4:1 and 1.6:1, between 1.6:1 and 1.8:1, between 1.9:1 and 2.1:1, and / or between 2.9:1 and 3.1:1. In some embodiments, it may be particularly advantageous if combining the second intermediate medium with the additional amount of BPDA comprises combining the pentamer with the additional amount of BPDA in a relative amount based on a molar ratio of the additional amount of BPDA to the pentamer of between 1.9:1 and 2.1:1. In some embodiments, combining the third intermediate medium with the third diamine comprises combining the heptamer with the third diamine in a relative amount between 0.4:1 and 0.6:1, between 0.8:1 and 1.1:1, between 0.8:1 and 1.1:1, between 1.8:1 and 2.2:1, based on a molar ratio of the third diamine to the heptamer. In some embodiments, it may be particularly advantageous if combining the third intermediate medium with the third diamine comprises combining the heptamer with the third diamine in a relative amount between 0.8:1 and 1.1:1, based on a molar ratio of the third diamine to the heptamer.In some embodiments, combining the fourth intermediate medium with the crosslinking agent comprises combining the oligomer chains with the crosslinking agent in relative amounts between 0.5:1 and 0.75:1, between 0.8:1 and 1.1:1, and / or between 1.4:1 and 1.6:1 based on a molar ratio of crosslinking agent to oligomer chains. In some embodiments, the ratio is between 0.9:1 and 1.1:1, between 1.4:1 and 1.6:1, between 1.6:1 and 1.8:1, between 1.9:1 and 2.1:1, and / or between 2.9:1 and 3.1:1. In some embodiments, it may be particularly advantageous if combining the fourth intermediate medium with the crosslinking agent comprises combining the oligomer chains with the crosslinking agent in relative amounts between 1.9:1 and 2.1:1 based on a molar ratio of crosslinking agent to oligomer chains.
[0230] In some embodiments of forming a polyimide aerogel, combining the fourth intermediate medium with a crosslinking agent includes combining oligomer chains with the crosslinking agent in relative amounts between 0.5:1 and 0.75:1 based on a molar ratio of crosslinking agent to oligomer chains.
[0231] In some embodiments of forming a polyimide aerogel, combining the fourth intermediate medium with the crosslinking agent further comprises combining a catalyst with the fourth intermediate medium and the crosslinking agent. In some embodiments, the catalyst comprises pyridine; picoline; quinoline; isoquinoline; 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU); DBU phenolate; carboxylate of DBU; triethylenediamine; carboxylate of triethylenediamine; lutidine; n-methylmorpholine; triethylamine; tripropylamine; tributylamine; N,N-dimethylbenzylamine; N,N'-dimethylpiperazine; N,N-dimethylcyclohexylamine; N,N',N"-tris(dialkylaminoalkyl)-s-hexahydrotriazine, such as N,N',N"-tris(dimethylaminopropyl)-s-hexahydrotriazine ; tris(dimethylaminomethyl)phenol; bis(2-dimethylaminoethyl)ether; N,N,N,N,N-pentamethyldiethylenetriamine; methylimidazole; dimethylimidazole; dimethylbenzylamine; 1,6-diazabicyclo[5.4.0]undec-7-ene (IUPAC: 1,4-diazabicyclo[2.2.2]octane); triethylenediamine; dimethylaminoethanolamine; dimethylaminopropylamine; N,N-dimethylaminoethoxyethanol; N,N,N-trimethylaminoethylethanolamine; triethanolamine; diethanolamine; triisopropanolamine; diisopropanolamine; and / or any suitable trialkylamine. In some embodiments, it may be particularly advantageous if the catalyst comprises triethylamine and / or tripropylamine.
[0232] In some embodiments of forming polyimide aerogel, combining the fourth intermediate medium with a crosslinking agent also includes combining a water scavenger with the fourth intermediate medium and the crosslinking agent. In some embodiments, combining the fourth intermediate medium with a crosslinking agent includes combining oligomer chains with water scavengers in a relative amount, and the relative amount is based on the molar ratio of water scavenger to BPDA, between 2:1 and 4:1, between 4:1 and 6:1, between 6:1 and 8:1, or between 8:1 and 10:1. In some embodiments, if the ratio is between 7:1 and 9:1, it may be particularly advantageous. In some embodiments, the water scavenger includes acetic anhydride, propionic anhydride, n-butyric anhydride, benzoic anhydride, trifluoroacetic anhydride, phosphorus trichloride, and / or dicyclohexylcarbodiimide. In some embodiments, if the water scavenger includes acetic anhydride, it may be particularly advantageous.
[0233] In some embodiments of forming polyimide aerogels, a solvent is used. In some embodiments, the solvent includes dimethyl sulfoxide; diethyl sulfoxide; N,N-dimethylformamide; N,N-diethylformamide; N,N-dimethylacetamide; N,N-diethylacetamide; N-methyl-2-pyrrolidone; 1-methyl-2-pyrrolidone; N-cyclohexyl-2-imidazolidinone; diethylene glycol dimethoxy ether; o-dichlorobenzene; phenols; cresol; xylenol; catechol; butyrolactone; acetone; methyl ethyl ketone; ethyl ethyl ketone; methyl propyl ketone; acetonitrile; ethyl acetate; and / or hexamethylphosphoramide. In some embodiments, it may be particularly advantageous if the solvent includes N-methyl-2-pyrrolidone.
[0234] In some embodiments of forming polyimide aerogels, the total amount of monomers is determined relative to the amount of solvent used. In certain embodiments, the total mass of all monomers is greater than 5% of the total mass of solvent.
[0235] In some embodiments of forming a polyimide aerogel, the polyimide gel is derived from the reaction of one or more anhydrides with one or more isocyanates. In some embodiments, the anhydride comprises a dianhydride. In some embodiments, the isocyanate comprises a diisocyanate, a triisocyanate, tris(isocyanatophenyl)methane, toluene diisocyanate trimer and / or methylene diphenyl diisocyanate trimer. In some embodiments, the anhydride and the isocyanate are contacted in a suitable solvent.
[0236] In some embodiments of forming a polyimide aerogel, the isocyanate includes a triisocyanate; an aliphatic triisocyanate; an aromatic isocyanate containing three or more isocyanate groups; an aromatic triisocyanate; a triisocyanate based on hexamethylene diisocyanate; a trimer of hexamethylene diisocyanate; hexamethylene diisocyanate; a triisocyanate including an isocyanurate; a diisocyanate including an isocyanurate; Desmodur N3200; Desmodur N3300; Desmodur N100; Desmodur N3400; Desmodur N3390; Desmodur N3390 BA / SN; Desmodur N3300 BA; Desmodur N3600; Desmodur N3790 BA; Desmodur N3800; Desmodur N3900; Desmodur XP Desmodur XP 2860; Desmodur N3400; Desmodur XP 2840; Desmodur N3580 BA; Desmodur N3500; Desmodur RE; Tris(isocyanatophenyl)methane; Desmodur RC; MR; Mondur MRS; diphenylmethane diisocyanate; diphenylmethane 2,2'-, 2,4'- and / or 4,4'-diisocyanate (MDI); naphthalene 1,5-diisocyanate (NDI); toluene diisocyanate; toluene 2,4- and / or 2,6-diisocyanate (TDI); 3,3'-dimethylbiphenyl diisocyanate; 1,2-diphenylethane diisocyanate and / or p-phenylene diisocyanate (PPDI); trimethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, heptamethylene diisocyanate and / or octamethylene diisocyanate; 2-methylpentamethylene 1,5-diisocyanate esters; 2-ethylbutylene 1,4-diisocyanate; pentamethylene 1,5-diisocyanate; butylene 1,4-diisocyanate; 1-isocyanato-3,3,5-trimethyl-5-isocyanatomethylcyclohexane (isophorone diisocyanate, IPDI); 1,4- and / or 1,3-bis(isocyanatomethyl)cyclohexane (HXDI); cyclohexane 1,4-diisocyanate; 1-methylcyclohexane 2,4-diisocyanate; 1-methylcyclohexane 2,6-diisocyanate; dicyclohexylmethane 4,4'-diisocyanate; dicyclohexylmethane 2,4'-diisocyanate; and / or dicyclohexylmethane 2,2'-diisocyanate.
[0237] In some embodiments of forming a polyimide aerogel, the anhydride includes an aromatic dianhydride; an aromatic tertianhydride; an aromatic tetradianhydride; an aromatic anhydride having 6 to 24 carbon atoms and 1 to 4 aromatic rings, which aromatic rings may be fused, coupled by a biaryl bond, or connected by one or more connecting groups selected from C1-6 alkylene, oxygen, sulfur, ketone, sulfoxide, sulfone, etc.; biphenyl-3,3',4,4'-tetracarboxylic dianhydride (BPDA); 3,3',4,4'-biphenyltetracarboxylic dianhydride; 2,3,3',4'-biphenyltetracarboxylic dianhydride (a-BPDA); 2,2',3,3'-biphenyltetracarboxylic dianhydride Formic dianhydride; 3,3',4,4'-benzophenonetetracarboxylic dianhydride; benzophenone-3,3',4,4'-tetracarboxylic dianhydride (BTDA); pyromellitic dianhydride; 4,4'-hexafluoroisopropylidene diphthalic dianhydride (6FDA); 4,4'-(4,4'-isopropylidene diphenoxy)-bis(phthalic anhydride); 4,4'-oxydiphthalic anhydride (ODPA); 4,4'-oxydiphthalic anhydride; 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride (DSDA); hydroquinone dianhydride; hydroquinone diphthalic anhydride (HQDEA) ; 4,4'-bisphenol A dianhydride (BPADA); ethylene glycol bis(trimellitic anhydride) (TMEG); 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride; bis(3,4-dicarboxyphenyl)sulfoxide dianhydride; poly(siloxane-containing dianhydride); 2,3,2',3'-benzophenonetetracarboxylic dianhydride; 3,3',4,4'-benzophenonetetracarboxylic dianhydride; naphthalene-2,3,6,7-tetracarboxylic dianhydride; naphthalene-1,4,5,8-tetracarboxylic dianhydride; 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride; 3,4,9,10-perylenetetracarboxylic dianhydride; bis(3,4-dicarboxyphenyl)propane dianhydride 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride; 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropylene; 2,6-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride; 2,7-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride; 2,3,6,7-tetrachloronaphthalene-1,4,5,8-tetracarboxylic dianhydride; phenanthrene-8,9,10-tetracarboxylic dianhydride; pyrazine-2,3,5,6-tetracarboxylic dianhydride; benzene-1,2,3,4-tetracarboxylic dianhydride; and / or thiophene-2,3,4,5-tetracarboxylic dianhydride. In some embodiments, it may be particularly advantageous if the dianhydride includes biphenyl-3,3',4,4'-tetracarboxylic dianhydride (BPDA).
[0238] In some embodiments of forming polyimide aerogel, the polyimide gel is derived from the reaction of amine and anhydride. In some embodiments, the reaction of amine and anhydride forms poly(amic acid) oligomer. In some embodiments, poly(amic acid) oligomer is chemically imidized to obtain polyimide oligomer. In some embodiments, chemical imidization is achieved by contacting poly(amic acid) oligomer with a dehydrating agent. In some embodiments, the dehydrating agent includes acetic anhydride, propionic anhydride, n-butyric anhydride, benzoic anhydride, trifluoroacetic anhydride, phosphorus trichloride, and / or dicyclohexylcarbodiimide. In some embodiments, chemical imidization is catalyzed by contacting a solution consisting of a poly(amic acid) oligomer and a dehydrating agent with an imidization catalyst.
[0239] In some embodiments of forming a polyimide aerogel, the polyimide gel is derived from the reaction of an amine with an anhydride. In some embodiments, the reaction of an amine and an anhydride forms a poly(amic acid) oligomer. In some embodiments, the poly(amic acid) oligomer is thermally imidized to produce a polyimide oligomer. In some embodiments, the poly(amic acid) oligomer is heated to a temperature greater than or equal to 80°C, greater than or equal to 90°C, greater than or equal to 100°C, greater than or equal to 150°C, greater than or equal to 180°C, greater than or equal to 190°C, or any suitable temperature.
[0240] In some embodiments of forming polyimide aerogel, diamine and / or dianhydride can be selected based on commercial availability and / or price. In certain embodiments, diamine and / or dianhydride can be selected based on desired material properties. In certain embodiments, specific diamine and / or dianhydride can give polymer specific properties. For example, in certain embodiments, diamine and / or dianhydride with flexible linking group between phenyl can be used to manufacture polyimide aerogel with increased flexibility. In certain embodiments, diamine and / or dianhydride comprising side chain methyl can be used to manufacture polyimide aerogel with increased hydrophobicity. In other embodiments, diamine and / or dianhydride comprising fluorinated part (such as trifluoromethyl) can be used to manufacture polyimide aerogel with increased hydrophobicity.
[0241] In some embodiments of forming polyimide aerogels, two or more diamines and / or two or more dianhydrides are used. In an illustrative embodiment, two diamines are used. The molar percentage of the first diamine relative to the total amount of the two diamines can vary from 0% to 100%. In some embodiments, the molar percentage of the first diamine relative to the total amount of the two diamines includes less than or equal to 99.9%, less than or equal to 90%, less than or equal to 80%, less than or equal to 70%, less than or equal to 60%, less than or equal to 50%, less than or equal to 40%, less than or equal to 30%, less than or equal to 20%, less than or equal to 10%, less than or equal to 0.1% or less. In other embodiments using more than two diamines, the molar percentage of each diamine relative to the total diamine can vary from 0.1% to 99.9%. In a further illustrative example, two dianhydrides are used. The molar percentage of the first dianhydride relative to the total amount of the two dianhydrides can vary from 0.1% to 99.9%. In some embodiments, the mole percentage of the first dianhydride relative to the total amount of the two dianhydrides includes less than or equal to 99.9%, less than or equal to 90%, less than or equal to 80%, less than or equal to 70%, less than or equal to 60%, less than or equal to 50%, less than or equal to 40%, less than or equal to 30%, less than or equal to 20%, less than or equal to 10%, less than or equal to 0.1% or less. In other embodiments using more than two dianhydrides, the mole percentage of each dianhydride relative to the total dianhydride can vary from 0.1% to 99.9%.
[0242] In some embodiments of forming polyimide aerogel, multiple diamines are used. In some embodiments, a first diamine is added to a solvent and then a dianhydride is added. In some embodiments, each amino site on the diamine reacts with an anhydride site on different dianhydrides to form an anhydride-terminated oligomer. In some embodiments, a second diamine is then added to the solution. These diamines react with the terminal anhydrides on the oligomers in the solution to form longer amino-terminated oligomers. Such processes can produce oligomers of different lengths and form an alternating motif of a first diamine, then a dianhydride, and then a second diamine. Without wishing to be bound by any particular theory, it is believed that this method can promote spatial uniformity of properties within the entire gel network, and simply mixing all monomers together at the same time and allowing dianhydrides and diamines to react randomly with other monomers at the same time may result in phase separation and / or spatial heterogeneity of domains rich in a particular diamine.
[0243] In some embodiments of forming a polyimide aerogel, the weight (i.e., mass) percentage of polymer in the solution is controlled during the polyimide gel synthesis process. The term "weight percentage of polymer in solution" refers to the weight of the monomers in the solution minus the weight of the byproducts produced by the condensation reaction between the monomers, relative to the weight of the solution. The weight percentage of the polymer in the solution can be less than or equal to 1%, less than or equal to 2%, less than or equal to 3%, less than or equal to 4%, less than or equal to 5%, less than or equal to 6%, less than or equal to 7%, less than or equal to 8%, less than or equal to 9%, less than or equal to 10%, less than or equal to 12%, less than or equal to 14%, less than or equal to 16%, less than or equal to 18%, less than or equal to 20%, and / or between 20% and 30%. In some embodiments, it may be particularly advantageous if the weight percentage of the polymer is between 5% and 15%.
[0244] In some embodiments of forming polyimide aerogels, the reaction of diamine and dianhydride produces an oligomer comprising repeating units of at least one diamine and dianhydride. In some embodiments, the oligomer comprises 1 repeating unit, 2 repeating units, less than or equal to 5 repeating units, less than or equal to 10 repeating units, less than or equal to 20 repeating units, less than or equal to 30 repeating units, less than or equal to 40 repeating units, less than or equal to 50 repeating units, less than or equal to 60 repeating units, less than or equal to 80 repeating units, less than or equal to 100 repeating units, or less than or equal to 200 repeating units. In some embodiments, the average degree of polymerization of the oligomer is less than or equal to 10, less than or equal to 20, less than or equal to 30, less than or equal to 40, less than or equal to 60, less than or equal to 80, or less than or equal to 100. In some embodiments, the oligomer comprises a terminal anhydride group, i.e., both ends of the oligomer comprise a terminal anhydride group. In some embodiments, the oligomer comprises a terminal amine group, i.e., both ends of the oligomer comprise a terminal amine group.
[0245] In some embodiments of forming a polyimide aerogel, a method for making the aerogel includes providing a solvent (e.g., any solvent described elsewhere herein), adding a first diamine (e.g., any diamine described elsewhere herein) to the solvent, adding a first amount of a dianhydride (e.g., any dianhydride described elsewhere herein) to the solvent after adding the first diamine, adding a second diamine (e.g., any dianhydride described elsewhere herein) to the solvent after adding the first amount of the dianhydride, adding a second amount of a dianhydride (e.g., any dianhydride described elsewhere herein) to the solvent after adding the second diamine, adding a third diamine to the solvent after adding the second amount of the dianhydride, adding a crosslinker (e.g., any crosslinker described herein) and / or a crosslinking agent (e.g., any crosslinking agent described herein) to the solvent. A method of forming an aerogel is disclosed in the present invention wherein: the step of adding a first liquid to the aerogel comprises adding a first liquid (e.g., a first catalyst) to the aerogel, adding a second ...
[0246] Although various embodiments above and elsewhere herein describe polyimide aerogels, aerogels may include a variety of other suitable materials. In some embodiments, the aerogel component of the aerogel / foam material combination includes polyurea, polyurethane, polyisocyanate, polyisocyanurate, polyimide, polyamide, poly(imide-amide), polyacrylonitrile, polycyclopentadiene, polybenzoxazine, polybenzazazine, polyacrylamide, polynorbornene, poly(ethylene terephthalate), poly(etheretherketone), poly(etherketoneketone), phenolic polymers, resorcinol-formaldehyde polymers, melamine-formaldehyde polymers, resorcinol-melamine-formaldehyde polymers, furfural-formaldehyde polymers, resol resins, novolacs, acetic acid-based polymers, polymer cross-linked oxides, silica-polysaccharide polymers, silica-pectin polymers, polysaccharides, glycoproteins, proteoglycans, collagen, proteins, polypeptides, nucleic acids, Amorphous carbon, graphitic carbon, graphene, diamond, carbon nanotubes, boron nitride, boron nitride nanotubes, two-dimensional boron nitride, alginate, chitin, chitosan, pectin, gelatin, gellan gum, gum, agarose, agar, cellulose, virus, biopolymer, organic modified silicate (ormosil), organic-inorganic hybrid material, rubber, polybutadiene, poly(methylpentene), polyester, polyetheretherketone, polyetherketoneketone, polypentene, polybutene, polytetrafluoroethylene, polyethylene, polypropylene, polyolefin, metal nanoparticles, metalloid nanoparticles, metal chalcogenides, metalloid chalcogenides, metals, metalloids, metal carbides, metalloid carbides, metal nitrides, metalloid nitrides, metal silicides, metal silicides, metal phosphides, metalloid phosphides, phosphorus-containing organic polymers, and / or carbonizable polymers. Other non-limiting examples of suitable materials include, for example, silicon dioxide, metal and / or metalloid oxides, metal chalcogenides, metal and / or metalloids, metal and / or metalloid carbides, metal and / or metalloid nitrides, organic polymers, biopolymers, amorphous carbon, graphitic carbon, diamond, and discrete nanoscale objects such as carbon nanotubes, boron nitride nanotubes, viruses, semiconductor quantum dots, graphene, 2D boron nitride, or combinations thereof. Other materials may also be used.
[0247] In some embodiments, it may be particularly advantageous if the polymer aerogel comprises a three-dimensional network of an organic polymer comprising monomers and / or crosslinks having three or more functionalities, for example, it comprises the reaction product of a crosslinker and three or more oligomers and / or the reaction product of a monomer with three or more other monomers. For example, Figure 4Non-limiting examples of molecular structures of monomers that can be used to make aerogels are shown, including ODA (4,4'-diaminodiphenyl ether), DMBZ (2,2'-dimethylbenzidine), diphenylamine-m, and BPDA (biphenyltetracarboxylic dianhydride). In some embodiments, it may be particularly advantageous if the polymer network containing trifunctional or higher functionality monomers and / or crosslinkers provides the aerogel with suitable strength, stiffness, and toughness properties for use as a structural material. In some embodiments, the strength, stiffness, and toughness properties of the aerogel are suitable for producing aerogel parts of larger sizes (e.g., greater than or equal to 30 cm).
[0248] In some embodiments, the aerogel of the aerogel / foam material combination includes a polyurea aerogel. For example, in some embodiments, at least 25wt%, at least 50wt%, at least 75wt%, at least 90wt%, at least 95wt%, at least 98wt%, at least 99wt%, at least 99.9wt% or all of the aerogel in the aerogel / foam material combination is composed of polyurea. In some embodiments, the polyurea can be derived from the reaction of isocyanate with water, wherein amines are formed in situ. In some embodiments, the polyurea is derived from the reaction of isocyanate with amines. For example, the manufacture of polyurea aerogels is described in U.S. Patent No. 10,301,445, published on May 28, 2019 and entitled "Three-dimensional porous polyurea network and method for making the same", which is incorporated herein by reference in its entirety for all purposes.
[0249] In some embodiments, the aerogel of the aerogel / foam combination comprises a polyurethane aerogel. For example, in some embodiments, at least 25wt%, at least 50wt%, at least 75wt%, at least 90wt%, at least 95wt%, at least 98wt%, at least 99wt%, at least 99.9wt% or all of the aerogel in the aerogel / foam combination is made of polyurethane. In some embodiments, the polyurethane can be derived from the reaction of isocyanate and polyol. For example, the manufacture of polyurethane aerogels is described in U.S. Patent No. 8,927,079, published on January 6, 2015 and entitled "Porous Polyurethane Network and Method for Preparing the Same", which is incorporated herein by reference in its entirety for all purposes.
[0250] In some embodiments, the aerogel of the aerogel / foam material combination comprises a polyimide aerogel. For example, in some embodiments, at least 25wt%, at least 50wt%, at least 75wt%, at least 90wt%, at least 95wt%, at least 98wt%, at least 99wt%, at least 99.9wt% or all of the aerogel in the aerogel / foam material combination is composed of polyimide. In some embodiments, the polyimide can be derived from the reaction of a dianhydride with a diisocyanate. For example, the manufacture of polyimide aerogels is described in U.S. Patent No. 9,745,198, published on August 29, 2017 and entitled "Nanostructured porous polyimide network and method for making the same", which is incorporated herein by reference in its entirety for all purposes.
[0251] In some embodiments, the aerogel of the aerogel / foam combination comprises a polyamide aerogel. For example, in some embodiments, at least 25 wt%, at least 50 wt%, at least 75 wt%, at least 90 wt%, at least 95 wt%, at least 98 wt%, at least 99 wt%, at least 99.9 wt%, or all of the aerogel in the aerogel / foam combination is composed of polyamide. In some embodiments, the polyamide can be derived from the reaction of an amine and a carboxyl group. In some embodiments, the polyamide can be derived from the reaction of an amine and an acyl chloride.
[0252] In some embodiments, the aerogel of the aerogel / foam combination comprises a polyisocyanurate aerogel. For example, in some embodiments, at least 25 wt%, at least 50 wt%, at least 75 wt%, at least 90 wt%, at least 95 wt%, at least 98 wt%, at least 99 wt%, at least 99.9 wt%, or all of the aerogel in the aerogel / foam combination is composed of polyisocyanurate. The polyisocyanurate may be derived from the reaction of diphenylmethane diisocyanate with a polyol.
[0253] In some embodiments, the aerogel of the aerogel / foam combination comprises a polyester aerogel. For example, in some embodiments, at least 25wt%, at least 50wt%, at least 75wt%, at least 90wt%, at least 95wt%, at least 98wt%, at least 99wt%, at least 99.9wt% or all of the aerogel in the aerogel / foam combination is made of polyester. In some embodiments, the polyester can be derived from the reaction of an acid and an alcohol. In certain embodiments, the polyester is derived from the alcoholysis and / or acidolysis of a low molecular weight ester. In some embodiments, the polyester is derived from the alcoholysis of an acyl chloride.
[0254] Any of a variety of foams may be used as the foam component of the aerogel / foam combination.
[0255] As described herein, foam is distinguished from batting. Batting contains individual fibers that are mechanically interwoven, whereas foam contains ligaments that are connected to each other in a continuous permeable network. In some embodiments, the ligaments of the foam are connected by intermolecular forces. In some embodiments, the ligaments of the foam are connected by covalent bonds.
[0256] In some embodiments, the foam can be melamine formaldehyde foam. In some embodiments, greater than or equal to 1wt%, greater than or equal to 2wt%, greater than or equal to 3wt%, greater than or equal to 5wt%, greater than or equal to 10wt%, greater than or equal to 15wt%, greater than or equal to 20wt%, greater than or equal to 25wt%, greater than or equal to 30wt%, greater than or equal to 35wt%, greater than or equal to 40wt%, greater than or equal to 45wt%, greater than or equal to 50wt%, greater than or equal to 55wt%, greater than or equal to 60wt%, greater than or equal to 65wt%, greater than or equal to 70wt%, greater than or equal to 75wt%, greater than or equal to 80wt%, greater than or equal to 85wt%, greater than or equal to 90wt%, or greater than or equal to 95wt% of the solid components of all melamine formaldehyde foams are made of melamine formaldehyde resin. The melamine formaldehyde foam can be open-cell or closed-cell. In some embodiments, it is particularly advantageous to use open-cell foam.
[0257] Melamine formaldehyde foam is usually made of melamine formaldehyde resin. Melamine formaldehyde resin is a thermosetting resin obtained by the reaction of melamine and formaldehyde. It is a kind of amino resin, and the resin with a larger molecular weight can be used as the surface layer of tableware or tables. Compared with other organic resin foams, melamine formaldehyde foam usually exhibits excellent flame retardancy. An example of melamine formaldehyde foam is BASF's product under the trade name In some embodiments, the melamine formaldehyde foam comprises a band of melamine formaldehyde polymer. In some embodiments, the air volume fraction in the melamine formaldehyde foam may be at least 70%, at least 75%, at least 80%, at least 85%, at least 90%, at least 95%, at least 99%, and / or less than or equal to 99.999%, less than or equal to 99%, less than or equal to 95%, less than or equal to 90%, less than or equal to 85%, less than or equal to 80%, or less than or equal to 75%. Combinations of these ranges are also possible (e.g., between 99% and 99.999%, between 95% and 99%, between 90% and 95%, between 85% and 90%, between 80% and 85%, between 75% and 80%, or between 70% and 75%).
[0258] In some embodiments, the melamine formaldehyde foam is hydrophobic. In some embodiments, the body area of the solid from which the melamine formaldehyde foam is made is hydrophobic. In some embodiments, a hydrophobic material is positioned above (e.g., coated on) the solid from which the melamine formaldehyde foam is made. In some embodiments, the melamine formaldehyde foam is made hydrophobic by reacting the melamine formaldehyde foam with a hydrophobe. In some embodiments, the melamine formaldehyde foam is made hydrophobic by immersing the melamine formaldehyde foam in a bath containing a hydrophobe.
[0259] In some embodiments, the melamine formaldehyde foam (when separated from the polymer aerogel) can have a bulk density greater than, or equal to, 0.005 g / cc, greater than, or equal to, 0.01 g / cc, greater than, or equal to, 0.02 g / cc, greater than, or equal to, 0.03 g / cc, greater than, or equal to, 0.04 g / cc, greater than, or equal to, 0.05 g / cc, greater than, or equal to, 0.06 g / cc, greater than, or equal to, 0.07 g / cc, greater than, or equal to, 0.08 g / cc, greater than, or equal to, 0.09 g / cc, greater than, or equal to, 0.1 g / cc, greater than, or equal to, 0.11 g / cc, greater than, or equal to, 0.12 g / cc, greater than, or equal to, 0.13 g / cc, greater than, or equal to, 0.14 g / cc, greater than, or equal to, 0.15 g / cc, or greater than, or equal to, 0.16 g / cc (and / or, in some embodiments, up to 1.0 g / cc, up to 1.1 g / cc, up to 1.2 g / cc, or more). In some embodiments, it may be particularly advantageous if the melamine formaldehyde foam, when separated from the polymer aerogel, has a bulk density greater than or equal to 0.005 g / cc and less than or equal to 0.15 g / cc.
[0260] In some embodiments, an article comprising an aerogel / foam combination comprises an adhesive applied to at least a portion of an outer surface of the aerogel / foam combination. FIG. 12C to FIG. 12DThe adhesive 1242 on the outer surface of the aerogel / foam combination 1206 is schematically shown. In some embodiments, the adhesive is applied in the form of a transfer tape. In some embodiments, the adhesive is sprayed onto the aerogel / foam combination. In some embodiments, the adhesive is poured onto the aerogel / foam combination. In other embodiments, the adhesive is distributed on the aerogel / foam combination. In some embodiments, the adhesive is applied to the outer surface of the aerogel / foam combination in a uniform layer. In other embodiments, the adhesive is applied to the outer surface of the aerogel / foam combination in the form of a non-uniform layer. In some embodiments, the adhesive includes epoxy, acrylic, acrylonitrile, polyamide, polyester, polysulfide, polyvinyl acetate, polyethylene, polypropylene, polyvinyl pyrrolidone, polyvinyl alcohol, cyanoacrylate, biopolymer, polyurethane, polyurea, isocyanate, silicone and / or gelatin. In some embodiments, the adhesive is covalently bonded to the aerogel / foam combination. In some embodiments, the adhesive penetrates into one or more pores of the aerogel / foam combination by capillary action. In some embodiments, the adhesive is non-flammable. In some embodiments, the adhesive is heat activated.
[0261] In some embodiments, the article comprises a layer of an aerogel / foam material combination and a facing material. For example, Fig. 12A The aerogel / foam material combination 1206 is schematically shown, wherein the outer surface of the aerogel / foam material combination 1206 has a facing material 1241. The facing material can be arranged on the aerogel / foam material combination in any of a variety of ways. For example, Fig. 12A The facing material is schematically depicted over the entire outer surface of the aerogel / foam material combination 1206. In other embodiments, the facing material covers a portion of the outer surface of the aerogel / foam material combination, but not necessarily the entirety thereof. Fig. 12B In, relative to Fig. 12A In the embodiment shown in FIG. 1 , facing material 1241 covers only a portion of the outer surface of aerogel / foam material combination 1206 .
[0262] In some embodiments, the facing material comprises a polymer, a metal, a ceramic, a fiber sheet, and / or carbon. In some embodiments, the facing material is chemically attached to the aerogel / foam combination. In some embodiments, the facing material is mechanically attached to the aerogel / foam combination. In some embodiments, the facing material is attached to the aerogel / foam combination using an adhesive. For example, Fig.12D In the embodiment, facing material 1241 is adhered to aerogel / foam material combination 1206 by adhesive 1242.
[0263] In some embodiments, the article comprising the aerogel / foam combination further comprises more than one layer of facing material. In some embodiments, the article comprising the aerogel / foam combination comprises a continuous layer of facing material. In other embodiments, the article comprising the aerogel / foam combination comprises a discontinuous layer of facing material. In some embodiments, the article comprising the aerogel / foam combination comprises a layer of facing material of uniform thickness. In other embodiments, the article comprising the aerogel / foam combination comprises a layer of facing material of non-uniform thickness.
[0264] In some embodiments, the facing material is in physical contact with the aerogel / foam material combination. Physical contact includes direct physical contact and indirect physical contact. When one or more physical materials exist between two physical objects and at least one path from the first physical object to the second physical object can be traced only through the physical materials, the two physical objects are said to be in "indirect physical contact". As an example, if a physical interlayer is located between the aerogel / material combination and the facing material, the material combination and the facing material are said to be in indirect physical contact because a path can be traced from the aerogel / material combination, through the physical interlayer (physical object), to the facing layer. In contrast, when two physical objects are in direct physical contact with each other, they are said to be in "direct contact".
[0265] In some aspects, the aerogel / foam material combination described herein can be part of a layered (e.g., multilayer) article. Typically, a layer is a material arrangement having a thickness dimension, a width dimension (perpendicular to the thickness dimension), and a depth dimension (perpendicular to the thickness dimension and the width dimension), wherein the width dimension is at least 5 times the thickness dimension and the depth dimension is at least 5 times the thickness dimension. In some embodiments, the layer is arranged so that the width dimension is at least 10 times, at least 50 times, at least 100 times, at least 500 times, or at least 1000 times the thickness dimension. In certain embodiments, the layer is arranged so that the depth dimension is at least 10 times, at least 50 times, at least 100 times, at least 500 times, or at least 1000 times the thickness dimension.
[0266] In some embodiments, the article comprises a first layer comprising an aerogel / foam material combination (e.g., comprising melamine formaldehyde foam and a polymer aerogel at least partially located within the outer boundary of the melamine formaldehyde foam), which is adhered to a second layer (e.g., comprising an aerogel / foam material combination, such as a second melamine formaldehyde foam, having a polymer aerogel at least partially located within the outer boundary of the melamine formaldehyde foam). In some embodiments, multiple aerogel / foam material combination layers are adhered to each other to achieve the desired thickness of the overall multilayer article. In some embodiments, the multiple layers include 2 layers, 3 layers or more, 4 layers or more, 5 layers or more, 6 layers or more, 7 layers or more, 8 layers or more, 9 layers or more, 10 layers or more, 15 layers or more, 20 layers or more, 25 layers or more, 30 layers or more, 35 layers or more, 40 layers or more, 45 layers or more, or 50 layers or more. In some embodiments, it may be advantageous to include at least 2 and less than or equal to 10 aerogel / foam material combination layers in the article.
[0267] In some embodiments, the aerogel / foam combination layer is secured with an adhesive. As an illustrative example, in some embodiments, one side of a first aerogel / foam combination layer (e.g., a layer comprising melamine formaldehyde foam and a polyimide aerogel at least partially within an outer boundary of the melamine formaldehyde foam) is adhered to a first side of a second aerogel / foam combination layer (e.g., a second layer comprising melamine formaldehyde foam and a polyimide aerogel at least partially within an outer boundary of the melamine formaldehyde foam), and a second side of the second aerogel / foam combination layer is adhered to one side of a third aerogel / foam combination layer (e.g., a third layer comprising melamine formaldehyde foam and a polyimide aerogel at least partially within an outer boundary of the melamine formaldehyde foam). Fig.12E An example of such an arrangement is shown in which the top surface of a first aerogel / foam combination layer 1206A is adhered (using adhesive 1242A) to the bottom surface of a second aerogel / foam combination layer 1206B, and the top surface of the second aerogel / foam combination layer 1206B is adhered (using adhesive 1242B) to the bottom surface of a third aerogel / foam combination layer 1242C.
[0268] The aerogel / foam material combinations described herein may be used in any of a variety of applications.
[0269] In some embodiments, the aerogel / foam combination is used in a vehicle. In some embodiments, the vehicle is a car, an airplane, a rocket, and / or a boat. In some embodiments, the aerogel / foam combination is used as an aircraft siding. In some embodiments, the aerogel / foam combination is used in an engine hood. In some embodiments, the aerogel / foam combination is used in a battery pack.
[0270] In some embodiments, the aerogel / foam combination is suitable for use as a soundproofing material, a component in a ballistic shield, panel, armor, protective vest, and / or ballistic armor, and / or a shock absorbing insulating material. In some embodiments, the use of the aerogel / foam combination in ballistic armor, shields, panels, and / or protective vests may be particularly advantageous.
[0271] In some embodiments, the aerogel / foam material combination is used as a flexible tape. In some embodiments, the flexible tape can be used in architectural applications. In some other embodiments, the flexible tape can be used in aerospace applications. In other embodiments, the flexible tape can be used in automotive applications.
[0272] In some embodiments, the aerogel / foam material combination is used in clothing. In some embodiments, the clothing is a jacket, a hat, a glove, a shirt, a sock, a trousers, or any other clothing. For example, Fig.13 Pants 1344 containing an aerogel / foam material combination are schematically depicted. In some embodiments, the aerogel / foam material combination is used in a diving suit. In some embodiments, the aerogel / foam material combination is used in a shoe, boot, or insole. By way of illustration and not limitation, Fig.14 Shoe 1443 is schematically depicted, which includes an insole 1406 that includes an aerogel / foam material combination. In some embodiments, the aerogel / foam material combination is sewn into clothing. In some embodiments, the aerogel / foam material combination is laminated (e.g., chemically laminated) to a textile in clothing. In some embodiments, the aerogel / foam material combination is adhered to a textile in clothing. In some embodiments, the aerogel / foam material combination is sandwiched between two panels of clothing.
[0273] Examples
[0274] The following examples are intended to illustrate certain embodiments of the invention, but are not intended to exemplify the full scope of the invention.
[0275] Example 1: Combination of melamine formaldehyde foam and polymer materials
[0276] A material combination of 2 mm thick melamine formaldehyde (MF) open-cell foam and a polymer sol was prepared for MF foam and polymer aerogel. The density of the MF foam and the polymer weight percentage of the polymer aerogel were changed. In addition, for purposes such as improving IR light shielding and hydrophobicity, we modified the particulate material and tried various loading levels of the particulate material. Two polymer systems were used to make the material combination: polyimide and polyurea. The bulk density and water absorption were determined at ambient temperature, and the thermal conductivity was measured according to the calibrated hot plate method described elsewhere in this article. Table 1 below provides a table summarizing various material combinations.
[0277] Table 1: Properties of MF foam and polymer aerogel material combinations
[0278]
[0279]
[0280] The polyimide sol was synthesized by reacting an amine with an anhydride. To prepare a 7.5 wt% polyimide sol, 0.71 g of 2,2'-dimethylbenzidine (DMBZ) was dissolved in 79.75 g of N-methyl-2-pyrrolidone (NMP). The mixture was stirred until the DMBZ was completely dissolved (no visible particles). After stirring for about 10 minutes, 1.96 g of biphenyl-3,3',4,4'-tetracarboxylic dianhydride (BPDA) was added to the mixture and stirred for 10 minutes. After stirring for 10 minutes, 2.30 g of 4,4'-[1,3-phenylenebis(1-methyl-ethylene)] dianiline (dianiline-m) was added to the mixture and stirred for 10 minutes. After stirring for 10 minutes, 1.96 g of BPDA was added to the mixture and stirred for 10 minutes. After stirring for 10 minutes, 0.60 g of 4,4'-diaminodiphenyl ether (ODA) was added to the mixture and stirred for 10 minutes. After 10 minutes, a mixture of 0.12 g of Desmodur N3300A and 8.86 g of NMP was added to the first mixture and stirred for 10 minutes. After stirring for 10 minutes, 10.90 g of acetic anhydride and 2.70 g of triethylamine were added in rapid succession. The resulting sol was stirred for 2 to 5 minutes until mixed, and then a piece of MF foam (approximately 4 inches x 6 inches x 2 mm) was immersed in the polyimide aerogel precursor for about 1 to 2 minutes until the MF foam appeared to have absorbed its maximum capacity of polyimide aerogel precursor. The combination of the polyimide aerogel precursor and the MF foam was then removed from the bath of the precursor and the excess was allowed to drip from the injected foam. When most of the excess polyimide aerogel precursor dripped from the foam, the combination of polyimide aerogel precursor and MF foam was placed in a sealed container and left at room temperature for 24 hours. After 24 hours, the combination of polyimide gel and MF foam was removed from the container and transferred to a solvent exchange bath (in this case, the sealed container was partially filled with about 500 mL of acetone). The combination was immersed in acetone in the container for 72 hours, during which time the acetone was decanted and replaced with an equal amount of new acetone twice.
[0281] After the solvent exchange is complete, the combination of polyimide gel and MF foam is transferred to a pressure vessel and immersed in excess acetone. The pressure vessel is then sealed and liquid CO2 is introduced into the pressure vessel. The CO2-acetone mixture is periodically vented while fresh liquid CO2 is supplied until all the acetone is removed. The pressure vessel is then separated from the CO2 supply while still filled with liquid CO2. The pressure vessel is heated until the internal temperature reaches 54°C, during which time the pressure increases. The pressure is regulated by solenoid valve activation and is not allowed to exceed 1400psi. At this point, the CO2 in the container is in a supercritical state and is maintained under this condition for three hours, at which time the pressure vessel is slowly isothermally exhausted, allowing the supercritical fluid to enter the gaseous state without forming a two-phase liquid-gas system until the pressure vessel returns to atmospheric pressure. Finally, the pressure vessel is cooled to room temperature and the combination of polyimide aerogel and MF foam is taken out.
[0282] Polyurea sol is synthesized by the amine reaction of isocyanate and original position formation. 8.87g Desmodur N3300 (isocyanurate trimer of hexamethylene diisocyanate) is dissolved in 70.40g acetone, and stir until uniform (about 10 minutes). In this mixture, 0.84g deionized water is added and stirred for about 20 seconds. Next, 1.64g triethylamine is added in the mixture, and stirred for another 20 seconds. MF foam is immersed in the polyurea sol, and then solvent exchange and drying are carried out as mentioned above.
[0283] Samples 11-13 were prepared using polyimide sols as described above, except that 3 μm silicon carbide (SiC) particulate material was added to the sol and mixed for about 5 minutes before adding triethylamine. The remaining procedures continued as outlined above. The SiC concentrations in the three samples were different. The concentration of sample 11 was 10 g SiC / 1 L sol, the concentration of sample 12 was 5 g SiC / 1 L sol, and the concentration of sample 13 was 20 g SiC / 1 L sol.
[0284] Samples 14-19 were prepared using the polyimide sol as described above and with one additional step. In sample 14, the MF foam was immersed in a bath of acetone and dioctylamine (the molar ratio of dioctylamine:acetone was 0.075:1) for about 24 hours. The MF foam was then removed from the bath and immersed in a new bath of acetone for about 24 hours to rinse the foam. The MF foam was then removed from the acetone and allowed to evaporate and dry for about 24 hours and then immersed in the polyimide sol. The remainder of the material combination preparation procedure continued as outlined above. The combination of the polyimide gel and MF foam of sample 15 was immersed in a bath of acetone and dioctylamine (the molar ratio of dioctylamine:acetone was 0.01:1) followed by solvent exchange. The combination was then solvent exchanged and dried as described above.
[0285] In Sample 16, the MF foam was immersed in a bath of ethanol and 1,1,1,3,3,3-hexamethyldisilazane (HMDZ) (the molar ratio of HMDZ:ethanol was 0.1:1) for about 24 hours. The MF foam was then removed from the bath and immersed in a new ethanol bath for about 24 hours to rinse the foam. The MF foam was then removed from the ethanol and allowed to evaporate and dry for about 24 hours before being immersed in a polyimide sol. The remainder of the material combination preparation procedure continued as outlined above. The polyimide gel and MF combination of Sample 17 was immersed in a bath of ethanol and HMDZ (the molar ratio of HMDZ:ethanol was 0.01:1) followed by solvent exchange. The material combination was then solvent exchanged and dried as described above.
[0286] In Sample 18, the MF foam was immersed in a bath of ethanol and hexamethyldisiloxane (HMDSO) (the molar ratio of HMDSO:ethanol was 0.1:1) and a drop of 37% HCl for about 24 hours. The MF foam was then removed from the bath and immersed in a new ethanol bath for about 24 hours to rinse the foam. The MF foam was then removed from the ethanol and allowed to evaporate and dry for about 24 hours before being immersed in a polyimide sol. The remainder of the material combination preparation procedure continued as outlined above. The polyimide gel and MF foam combination of Sample 19 was immersed in a bath of ethanol and HMDSO (the molar ratio of HMDSO:ethanol was 0.01:1) and a drop of 37% HCl, followed by solvent exchange. The material combination was then solvent exchanged and dried as described above.
[0287] The material combination described by Sample 2 was placed in an oven uniformly heated to a temperature of 200°C for 20 minutes. After 20 minutes, the material combination (now Sample 2a) was removed from the oven, cooled to ambient temperature, and then characterized. The material combination of Sample 2 was placed in an oven uniformly heated to a temperature of 300°C for 20 minutes. After 20 minutes, the material combination (now Sample 2b) was removed from the oven, cooled to ambient temperature, and then characterized.
[0288] In general, the samples produced had thermal conductivity below 30 mW / mK, were flexible, and had a density less than 0.3 g / cc.
[0289] Comparative Example 1: Combination of polyurethane foam and polymer materials
[0290] As a comparative example, a piece of open-cell polyurethane (PU) foam was immersed in a polyimide sol following the same procedure of sol preparation and immersion outlined in Example 1. The polyurethane foam partially dissolved in the polyimide sol and no final material combination could be produced.
[0291] Although several embodiments of the present invention have been described and shown herein, it is easy for a person of ordinary skill in the art to conceive of a variety of other devices and / or structures to perform the functions described herein, and / or obtain the results and / or one or more advantages thereof, and each of such changes and / or modifications is considered to fall within the scope of the present invention. More generally, it is easy for a person skilled in the art to recognize that all parameters, dimensions, materials, and configurations described herein are intended to be exemplary, and the actual parameters, dimensions, materials, and / or configurations will depend on one or more specific applications of the teachings of the present invention. A person skilled in the art will recognize or be able to confirm many equivalents of the specific embodiments of the invention described herein using only routine experiments. Therefore, it should be understood that the foregoing embodiments are presented only by way of example, and within the scope of the appended claims and their equivalents, the present invention can be practiced differently from the specific description and protection. The present invention relates to each individual feature, system, product, material, and / or method described herein. In addition, if such features, systems, products, materials, and / or methods are not mutually contradictory, any combination of two or more such features, systems, products, materials, and / or methods is included within the scope of the present invention.
[0292] Unless expressly indicated to the contrary, the indefinite articles "a" and "an" as used herein in the specification and claims should be understood to mean "at least one".
[0293] The phrase "and / or" as used herein in the specification and claims should be understood to mean "either or both" of the elements so combined, i.e., elements that are present in combination in some cases and not in combination in other cases. Other elements may optionally be present in addition to the elements specifically designated by the "and / or" term, whether related or unrelated to those specifically designated, unless expressly indicated to the contrary. Thus, as a non-limiting example, when used in conjunction with open language such as "comprising", a reference to "A and / or B" can refer to A without B (optionally including elements other than B) in one embodiment; to B without A (optionally including elements other than A) in another embodiment; to both A and B (optionally including other elements) in yet another embodiment; etc.
[0294] Some embodiments may be embodied as methods, various examples of which have been described. The actions performed as part of these methods may be ordered in any suitable manner. Thus, embodiments may be constructed in which the behaviors are performed in a different order than shown, may include behaviors that are different (e.g., more or less) than the described behaviors, and / or may involve performing some behaviors simultaneously, even though these behaviors are shown as being performed sequentially in the embodiments specifically described above.
[0295] As used herein in the specification and claims, "or" should be understood to have the same meaning as "and / or" as defined above. For example, when the items in the list are separated, "or" or "and / or" should be interpreted as inclusive, i.e., including at least one (but also including more than one) of several elements or lists of elements and optionally additional unlisted items. Only when the terms that are clearly indicated as opposite (such as, "only one of ..." or "exactly one of ...", or when used in the claims, "consisting of ...") will refer to including exactly one element in several elements or lists of elements. In general, the term "or" as used herein should be interpreted as indicating exclusive alternatives (i.e., "one or the other, but not two") only when exclusive terms (such as, "any one", "one of ...", "only one of ..." or "exactly one of ...") are in front. When used in the claims, "essentially consisting of ..." should have its ordinary meaning as used in the field of patent law.
[0296] As used herein in the specification and claims, when referring to a list of one or more elements, the phrase "at least one" should be understood to mean at least one element selected from any one or more elements in the list of elements, but does not necessarily include at least one of each element specifically listed in the list of elements, and does not exclude any combination of elements in the list of elements. This definition also allows that elements other than the elements specifically identified in the list of elements to which the phrase "at least one" refers may optionally be present, whether related or unrelated to those specifically identified elements. Thus, as a non-limiting example, "at least one of A and B" (or equivalently "at least one of A or B", or equivalently "at least one of A and / or B") may refer to at least one (optionally including more than one) A without B (and optionally including elements other than B) in one embodiment; to at least one (optionally including more than one) B without A (and optionally including elements other than A) in another embodiment; to at least one (optionally including more than one) A and at least one (optionally including more than one) B (and optionally including other elements) in yet another embodiment; etc.
[0297] In the claims and the above description, all transitional phrases such as "comprises," "comprising," "carrying," "having," "containing," "involving," "having," etc. shall be understood to be open-ended, i.e., meaning including but not limited to. Only the transitional phrases "consisting of" and "consisting essentially of" shall be closed or semi-closed transitional phrases, respectively, as set forth in the Patent Examination Procedure Section 2111.03 of the U.S. Patent Office Manual.
Claims
1. A material combination comprising: Melamine formaldehyde foam, including outer borders; and A polyimide aerogel is at least partially located within the outer boundary of the melamine formaldehyde foam.
2. The material combination according to claim 1, wherein: The polyimide aerogel includes an outer boundary, and At least 75 vol% of the melamine formaldehyde foam falls within the outer boundaries of the polyimide aerogel, and / or At least 75 vol% of the polyimide aerogel falls within the outer boundaries of the melamine formaldehyde foam.
3. The material combination of any one of claims 1-2, wherein the polyimide aerogel is hydrophobic.
4. The material combination according to any one of claims 1 to 3, wherein the polyimide aerogel comprises the following parts:
5. The material combination according to any one of claims 1 to 4, wherein the polyimide aerogel comprises one or more of the following parts:
6. The material combination according to any one of claims 1 to 5, wherein the polyimide aerogel comprises the following parts:
7. The material combination according to any one of claims 1 to 6, wherein the bulk density of the melamine formaldehyde foam and the polyimide aerogel when separated is greater than or equal to 0.005 g / cc and less than or equal to 0.15 g / cc.
8. The material combination of any one of claims 1-7, wherein the melamine formaldehyde foam is hydrophobic.
9. The material combination of claim 8, wherein the solid bulk region of which the melamine formaldehyde foam is made is hydrophobic.
10. The material combination of any one of claims 8-9, wherein the hydrophobic material is positioned above the solids making up the melamine formaldehyde foam.
11. The material combination of any one of claims 1-10, wherein the material combination exhibits a bulk density greater than or equal to 0.01 g / cc and less than or equal to 0.5 g / cc.
12. The material combination of any one of claims 1-11, wherein the material combination exhibits a thermal conductivity greater than or equal to 15 mW / m·K and less than or equal to 35 mW / m·K when measured according to a calibrated hot plate method with an average sample temperature of 25°C.
13. The material combination of any one of claims 1-12, wherein the material combination exhibits a thermal conductivity greater than or equal to 15 mW / m·K and less than or equal to 35 mW / m·K when measured according to ASTM test method E1225.
14. The material combination according to any one of claims 1 to 13, wherein: The material combination exhibits a lower thermal conductivity than the polyimide aerogel when measured separately from the melamine formaldehyde foam; and When measured separately from the polyimide aerogel, the material combination exhibits lower thermal conductivity than the melamine formaldehyde foam.
15. The material combination according to any one of claims 1 to 14, wherein: The combination of materials exhibits a thermal conductivity at least 10% lower than the thermal conductivity of the polyimide aerogel when measured separately from the melamine formaldehyde foam; and The material combination exhibits a thermal conductivity at least 10% lower than the thermal conductivity of the melamine formaldehyde foam when measured separately from the polyimide aerogel.
16. The material combination according to any one of claims 1 to 15, wherein: The material combination exhibits a reduction in thermal conductivity greater than or equal to 10% relative to the lower of the thermal conductivity of the melamine formaldehyde foam when measured separately from the polyimide aerogel and the thermal conductivity of the polyimide aerogel when measured separately from the melamine formaldehyde foam.
17. The material combination of any one of claims 1-16, wherein when the material combination is immersed in water at 25°C for 24 hours, the material combination absorbs water within its outer boundary by a mass less than or equal to 75% of the dry mass of the material combination before immersion in the water.
18. The material combination of any one of claims 1-17, wherein the material combination meets the standards of flame time, dripping flame time and / or burning length specified in Section 25.853a of the Federal Aviation Regulations of the United States.
19. The material combination according to any one of claims 1 to 18, wherein the material combination meets the fire performance standards of Class A1, Class A2 and / or Class B of European classification standard EN13501-1.
20. The material combination of any one of claims 1 to 19, wherein the material combination exhibits a relative humidity greater than or equal to 100 m 2 / g and less than or equal to 800m 2 / g of BET surface area.
21. The material combination of any one of claims 1 to 20, wherein the material combination exhibits a relative humidity greater than or equal to 200 m 2 / g and less than or equal to 450m 2 / g of BET surface area.
22. The material combination of any one of claims 1-21, wherein the material combination exhibits a BJH average pore size greater than or equal to 2 nm and less than or equal to 50 nm when measured using nitrogen adsorption.
23. The material combination of any one of claims 1-22, wherein the material combination exhibits a BJH average pore size between greater than or equal to 10 nm and less than or equal to 25 nm.
24. The material combination of any one of claims 1-23, wherein the material combination exhibits a flexural modulus of at least 0.00689 MPa when measured according to ASTM D790-10, except that the sample span is equal to a fixed value of 45 mm.
25. The material combination of any one of claims 1-24, wherein the material combination exhibits a flexural strength less than or equal to 1 GPa when measured according to ASTM D790-10, except that the sample span is equal to a fixed value of 45 mm.
26. The material combination of any one of claims 1-25, wherein the material combination further comprises a silica aerogel.
27. The material combination of any one of claims 1-26, wherein the material combination further comprises a trimethylsilyl-functionalized silica aerogel.
28. The material combination of any one of claims 1-27, wherein the material combination further comprises a trimethylsilyl-functionalized silica aerogel containing sodium ions.
29. The material combination of any one of claims 1-28, wherein the dimensions of the material combination do not change by more than 10% when subjected to a standard heating cycle at an elevated temperature of 200°C.
30. The material combination of any one of claims 1-29, wherein the material combination does not change dimensions by more than 10% when subjected to a standard heating cycle at an elevated temperature of 300°C.
31. The material combination of any one of claims 1-30, wherein the material combination further comprises an infrared (IR) sunscreen.
32. The material combination of claim 31 , wherein the IR sunscreen comprises a metal, a metal carbide, a metalloid carbide, a metal oxide, a metalloid oxide, graphitic carbon, elemental carbon, a phosphate, a borate, a metal silicate, a metalloid silicate, a metallocene, a molybdate, a stannate, a hydroxide and / or a carbonate.
33. The material combination of any one of claims 31-32, wherein the IR sunscreen agent comprises a plurality of particles, and an average maximum cross-sectional dimension of the IR sunscreen agent particles is greater than or equal to 1 micron and less than or equal to 5 microns.
34. The material combination of any one of claims 1-33, wherein the material combination undergoes an irreversible one-time linear shrinkage of less than or equal to 20% when first exposed to the maximum operating temperature.
35. The material combination of any one of claims 1 to 34, wherein the average dust concentration of the material combination in ten bending cycles is less than or equal to 4 mg / m 3 .
36. The material combination of any of claims 1-35, wherein a sample of the material combination having dimensions of 4 inches x 6 inches x 2 mm and a face area defined by the 4 inch and 6 inch dimensions is capable of forming a radius of curvature less than or equal to 1 / 4 inch when bent perpendicular to the 4 inch dimension.
37. The material combination as described in any one of claims 1-36, wherein the cross-sectional size of the material combination is greater than or equal to 1 mm and less than or equal to 15 mm.
38. The material combination of claim 37, wherein the dimension is a first dimension and the material combination has a second dimension different from the first dimension, the second dimension being greater than or equal to 1 foot.
39. The material combination of any one of claims 1-38, wherein after being subjected to a standard heating cycle of elevated temperatures to 200°C, the material combination exhibits a thermal conductivity less than or equal to 100 mW / m·K when measured according to a calibrated hot plate method at 25°C.
40. The material combination of any one of claims 1 to 39, wherein after being subjected to a standard heating cycle at an elevated temperature of 200°C, the material combination exhibits a thermal conductivity greater than or equal to 5 m / s. 2 / g of BET surface area.
41. A material combination as described in any of claims 1-40, wherein after being subjected to a standard heating cycle of elevated temperatures to 200°C and subsequently immersed in water at 25°C for 24 hours, the material combination absorbs within its outer boundaries a mass of water less than or equal to 200 wt% relative to the dry mass of the material combination prior to immersion in water.
42. A material combination as described in any of claims 1-41, wherein after being subjected to a standard heating cycle of elevated temperatures to 200°C and subsequently immersed in water at 25°C for 24 hours, the material combination absorbs within its outer boundaries a mass of water less than or equal to 75 wt% relative to the dry mass of the material combination prior to immersion in water.
43. The material combination of any one of claims 1-42, wherein when the material combination is immersed in water at 25°C for 24 hours, the material combination absorbs water within its outer boundary in a mass less than or equal to 20% of the dry mass of the material combination before immersion in water.
44. An article comprising the material combination of any one of claims 1 to 43 and a layer of facing material in physical contact with the material combination.
45. The article of claim 44, wherein the facing material comprises a polymer, a metal, a ceramic, a fiber sheet, and / or carbon.
46. An article comprising the combination of materials of any one of claims 1-45 or the article of any one of claims 44-45, wherein the adhesive is in physical contact with at least a portion of the outer surface of the combination of materials.
47. The article of claim 46, wherein the adhesive comprises an epoxy, an acrylic, an acrylonitrile, a polyamide, a polyester, a polysulfide, polyvinyl acetate, polyethylene, polypropylene, polyvinyl pyrrolidone, polyvinyl alcohol, a cyanoacrylate, a biopolymer, a polyurethane, a polyurea, an isocyanate, a silicone and / or a gelatin.
48. An article comprising: A first layer comprising the material combination of any one of claims 1-43, the first layer adhered to a second layer, the second layer comprising melamine formaldehyde foam and a polyimide aerogel at least partially located within the outer boundary of the melamine formaldehyde foam.
49. The article of claim 48, wherein the second layer comprises the material combination of any one of claims 1-43.
50. A shoe, boot or insole comprising the material combination of any one of claims 1-43 or the article of any one of claims 44-49.
51. A flexible belt comprising the material combination of any one of claims 1-43 or the article of any one of claims 44-49.
52. A garment comprising the combination of materials as claimed in any one of claims 1 to 43 or the article as claimed in any one of claims 44 to 49.
53. The garment of claim 52, wherein the garment is a jacket, a hat, a glove, a shirt, a sock, or a pair of pants.
54. A diving suit comprising the material combination of any one of claims 1-43 or the article of any one of claims 44-49.
55. A battery comprising the material combination of any one of claims 1-43 or the article of any one of claims 44-49.
56. A carbonized derivative of the material combination of any one of claims 1-43.
57. A method comprising: establishing contact between the melamine formaldehyde foam and a liquid containing a polyimide aerogel precursor such that the polyimide aerogel precursor penetrates an outer boundary of the melamine formaldehyde foam; as well as A polyimide aerogel is formed from the polyimide aerogel precursor such that the polyimide aerogel exists within an outer boundary of the melamine formaldehyde foam.
58. The method of claim 57, wherein the melamine formaldehyde foam is contacted with a hydrophobe before the melamine formaldehyde foam is contacted with the polyimide aerogel precursor.
59. The method of any one of claims 57-58, wherein the melamine formaldehyde foam is contacted with a hydrophobe after the melamine formaldehyde foam is contacted with the polyimide aerogel precursor.
60. The method of any one of claims 57-59, wherein the combination of the polyimide aerogel and the melamine formaldehyde foam is contacted with a hydrophobe.
61. The method of any one of claims 57-60, wherein the combination of the polyimide aerogel and the melamine formaldehyde foam is contacted with a hydrophobe.
62. The method of any one of claims 57-61, wherein the combination of the polyimide aerogel and the melamine formaldehyde foam is contacted with a vapor comprising a hydrophobe such that exposed reactive sites on the melamine formaldehyde foam react with the hydrophobe.
63. The method of any one of claims 58-62, wherein the hydrophobe comprises hexamethyldisilazane, hexamethylenedisiloxane, dioctylamine, didodecylamine, hexylamine, dihexylamine, isocyanate, aldehyde, amine, alkylchlorosilane and / or a hydrophobe of formula HN(R 1 )(R 2 ) wherein: R 1 are each independently a first organic moiety; and R 2 Each independently is H or a second organic moiety; The premise is: The first and second organic moieties are both not H; and HR determined at about 25°C and about 1 atm 1 and / or HR 2 The log P is not less than 1.
64. The method of any one of claims 57-63, further comprising forming the melamine formaldehyde foam from a precursor foam.
65. The method of claim 64, further comprising thermally or mechanically treating the precursor foam to increase the density of the melamine formaldehyde foam relative to the precursor foam prior to contacting the polyimide aerogel precursor.
66. The method of any one of claims 57-65, wherein before establishing contact between the melamine formaldehyde foam and the liquid comprising a polyimide aerogel precursor, the melamine formaldehyde foam is heated to a temperature greater than or equal to 200°C and less than or equal to 300°C and compressed to a thickness greater than or equal to 15% and less than or equal to 90% of the thickness of the melamine formaldehyde foam just before compression.
67. The method of any one of claims 57-66, wherein establishing contact between the melamine formaldehyde foam and the liquid containing a polyimide aerogel precursor comprises spraying the liquid containing a polyimide aerogel precursor onto the melamine formaldehyde foam.
68. The method of any one of claims 57-67, wherein establishing contact between the melamine formaldehyde foam and the liquid containing a polyimide aerogel precursor comprises pouring the liquid containing a polyimide aerogel precursor onto the melamine formaldehyde foam.
69. The method of any one of claims 57-68, wherein establishing contact between the melamine formaldehyde foam and the liquid containing a polyimide aerogel precursor comprises injecting the liquid containing a polyimide aerogel precursor into the melamine formaldehyde foam.
70. The method of any one of claims 57-69, wherein establishing contact between the melamine formaldehyde foam and the liquid comprising a polyimide aerogel precursor comprises immersing the melamine formaldehyde foam in the liquid comprising a polyimide aerogel precursor.
71. The method of any one of claims 57-70, wherein establishing contact between the melamine formaldehyde foam and the liquid containing a polyimide aerogel precursor comprises moving the melamine formaldehyde foam through a bath of the liquid containing a polyimide aerogel precursor such that the liquid containing a polyimide aerogel precursor is absorbed by the melamine formaldehyde foam.
72. The method of claim 71, wherein the melamine formaldehyde foam is moved through the bath of the liquid containing the polyimide aerogel precursor and compressed while in contact with the liquid containing the polyimide aerogel precursor, so that the liquid containing the polyimide aerogel precursor is absorbed into the pores of the melamine formaldehyde foam when the foam is depressurized.
73. The method of any one of claims 57-72, wherein the polyimide aerogel precursor forms a polyimide gel on or within the pores of the melamine formaldehyde foam, thereby forming a gel / foam material combination.
74. The method of any one of claims 57-73, wherein the liquid in the pores of the melamine formaldehyde foam is exchanged for a transfer solvent.
75. The method of claim 74, wherein the liquid in the pores of the melamine formaldehyde foam is exchanged for the transfer solvent in a continuous manner.
76. The method of any one of claims 74-75, wherein the transfer solvent comprises an alcohol, a ketone, a nitrile, an acetate, a pyrrolidone, an alkane, a pentanone, an alkane, dimethyl sulfoxide, and / or liquid carbon dioxide.
77. The method of any one of claims 74-76, wherein after the exchange, the transfer solvent is frozen.
78. The method of any one of claims 74-77, wherein the transfer solvent and / or liquid in the pores of the gel / foam material combination is removed by supercritical extraction.
79. The method of any one of claims 57-78, wherein forming the polyimide aerogel comprises forming a gel comprising the liquid and the polyimide aerogel precursor, subsequently at least partially replacing the liquid in the gel with carbon dioxide, and subsequently removing the carbon dioxide to form the polyimide aerogel.
80. The method of any one of claims 57-78, wherein forming the polyimide aerogel comprises forming a gel comprising the liquid and the polyimide aerogel precursor, replacing at least a portion of the liquid with a transfer solvent, and removing the transfer solvent by evaporation and / or boiling.
81. The method of any one of claims 57-78, wherein forming the polyimide aerogel comprises forming a gel comprising the liquid and the polyimide aerogel precursor, replacing at least a portion of the liquid with a transfer solvent, and removing the transfer solvent by vacuum freeze drying.
82. The method of any one of claims 57-78, wherein forming the polyimide aerogel comprises forming a gel comprising the liquid and the polyimide aerogel precursor, replacing at least a portion of the liquid with a transfer solvent, freeze drying the transfer solvent, and removing the transfer solvent at an absolute pressure equal to or greater than 1 atmosphere.
83. The method of any one of claims 57-82, wherein forming the polyimide aerogel comprises removing the liquid from the melamine formaldehyde foam in a continuous manner.
84. A material combination comprising: Melamine formaldehyde foam, including outer borders; and A polymer aerogel is at least partially located within the outer boundary of the melamine formaldehyde foam.
85. The material combination of claim 84, wherein the polymer aerogel comprises polyurea, polyurethane, polyamide, polymer, polyisocyanurate and / or polyester.
86. The material combination of any one of claims 84-84, wherein: The polymer aerogel includes an outer boundary, and At least 75 vol% of the melamine formaldehyde foam falls within the outer boundaries of the polymer aerogel, and / or At least 75 vol% of the polymer aerogel falls within the outer boundaries of the melamine formaldehyde foam.
87. The material combination of any one of claims 84-86, wherein the polymer aerogel is hydrophobic.
88. The material combination of any one of claims 84-87, wherein the bulk density of the melamine formaldehyde foam when separated from the polymer aerogel is greater than or equal to 0.005 g / cc and less than or equal to 0.15 g / cc.
89. The material combination of any one of claims 84-88, wherein the melamine formaldehyde foam is hydrophobic.
90. The material combination of claim 89, wherein the solid bulk region of which the melamine formaldehyde foam is made is hydrophobic.
91. The material combination of any of claims 89-90, wherein the hydrophobic material is positioned above the solids making up the melamine formaldehyde foam.
92. The material combination of any of claims 84-91, wherein the material combination exhibits a bulk density greater than or equal to 0.01 g / cc and less than or equal to 0.5 g / cc.
93. The material combination of any one of claims 84-92, wherein the material combination exhibits a thermal conductivity greater than or equal to 15 mW / m·K and less than or equal to 35 mW / m·K when measured according to a calibrated hot plate method with an average sample temperature of 25°C.
94. The material combination of any of claims 84-93, wherein the material combination exhibits a thermal conductivity greater than or equal to 15 mW / m·K and less than or equal to 35 mW / m·K when measured according to ASTM test method E1225.
95. The material combination of any one of claims 84-94, wherein: The combination of materials exhibits a lower thermal conductivity than the polymer aerogel when measured separately from the melamine formaldehyde foam; and When measured separately from the polymer aerogel, the material combination exhibits lower thermal conductivity than the melamine formaldehyde foam.
96. The material combination of any one of claims 84-95, wherein: The combination of materials exhibits a thermal conductivity at least 10% lower than the thermal conductivity of the polymer aerogel when measured separately from the melamine formaldehyde foam; and The material combination exhibits a thermal conductivity at least 10% lower than the thermal conductivity of the melamine formaldehyde foam when measured separately from the polymer aerogel.
97. The material combination of any one of claims 84-96, wherein: The material combination exhibits a reduction in thermal conductivity greater than or equal to 10% relative to the lower of the thermal conductivity of the melamine formaldehyde foam when measured separately from the polymer aerogel and the thermal conductivity of the polymer aerogel when measured separately from the melamine formaldehyde foam.
98. The material combination of any one of claims 84-97, wherein when the material combination is immersed in water at 25°C for 24 hours, the material combination absorbs within its outer boundary a mass of water less than or equal to 75% of the dry mass of the material combination before immersion in the water.
99. The material combination of any one of claims 84-98, wherein the material combination meets the flame time, dripping flame time and / or burning length criteria specified in Section 25.853a of the Federal Aviation Regulations.
100. The material combination of any one of claims 84-99, wherein the material combination complies with the A1, A2 and / or B fire performance standards of European classification standard EN 13501-1.
101. The material combination of any one of claims 84-100, wherein the material combination exhibits a relative humidity greater than or equal to 100 m 2 / g and less than or equal to 800m 2 / g of BET surface area.
102. The material combination of any one of claims 84-101, wherein the material combination exhibits a relative humidity greater than or equal to 200 m 2 / g and less than or equal to 450m 2 / g of BET surface area.
103. The material combination of any one of claims 84-102, wherein the material combination exhibits a BJH average pore size greater than or equal to 2 nm and less than or equal to 50 nm when measured using nitrogen adsorption.
104. The material combination of any of claims 84-103, wherein the material combination exhibits a BJH average pore size between greater than or equal to 10 nm and less than or equal to 25 nm.
105. The material combination of any of claims 84-104, wherein the material combination exhibits a flexural modulus of at least 0.00689 MPa when measured in accordance with ASTM D790-10, except that the sample span is equal to a fixed value of 45 mm.
106. The material combination of any of claims 84-105, wherein the material combination exhibits a flexural strength less than or equal to 1 GPa when measured according to ASTM D790-10, except that the sample span is equal to a fixed value of 45 mm.
107. The material combination of any one of claims 84-106, wherein the material combination further comprises silica aerogel.
108. The material combination of any one of claims 84-107, wherein the material combination further comprises a trimethylsilyl-functionalized silica aerogel.
109. The material combination of any one of claims 84-108, wherein the material combination further comprises a trimethylsilyl-functionalized silica aerogel containing sodium ions.
110. The material combination of any of claims 84-109, wherein the dimensions of the material combination do not change by more than 10% when subjected to a standard heating cycle at an elevated temperature of 200°C.
111. The material combination of any of claims 84-110, wherein the dimensions of the material combination do not change by more than 10% when subjected to a standard heating cycle at an elevated temperature of 300°C.
112. The material combination of any one of claims 84-111, wherein the material combination further comprises an infrared (IR) sunscreen.
113. The material combination of claim 112, wherein the IR sunscreen comprises a metal, a metal carbide, a metalloid carbide, a metal oxide, a metalloid oxide, graphitic carbon, elemental carbon, a phosphate, a borate, a metal silicate, a metalloid silicate, a metallocene, a molybdate, a stannate, a hydroxide and / or a carbonate.
114. The material combination of any of claims 112-113, wherein the IR sunscreen agent comprises a plurality of particles, and an average maximum cross-sectional dimension of the IR sunscreen agent particles is greater than or equal to 1 micron and less than or equal to 5 microns.
115. The material combination of any of claims 84-114, wherein the material combination undergoes an irreversible one-time linear shrinkage of less than or equal to 20% when first exposed to the maximum operating temperature.
116. The material combination of any one of claims 84 to 115, wherein the average dust concentration of the material combination during ten bending cycles is less than or equal to 4 mg / m 3 .
117. The material combination of any one of claims 84-116, wherein a sample of the material combination having dimensions of 4 inches x 6 inches x 2 mm and a face area defined by the 4 inch and 6 inch dimensions is capable of forming a radius of curvature less than or equal to 1 / 4 inch when bent perpendicular to the 4 inch dimension.
118. The material combination of any one of claims 84-117, wherein a cross-sectional dimension of the material combination is greater than or equal to 1 mm and less than or equal to 15 mm.
119. The material combination of claim 118, wherein the dimension is a first dimension and the material combination has a second dimension different from the first dimension, the second dimension being greater than or equal to 1 foot.
120. The material combination of any one of claims 84-119, wherein after being subjected to a standard heating cycle of elevated temperatures to 200°C, the material combination exhibits a thermal conductivity less than or equal to 100 mW / m·K when measured according to a calibrated hot plate method at 25°C.
121. The material combination of any one of claims 84-120, wherein after being subjected to a standard heating cycle at an elevated temperature of 200°C, the material combination exhibits a thermal conductivity greater than or equal to 5 m / s. 2 / g of BET surface area.
122. A material combination as described in any of claims 84-121, wherein after being subjected to a standard heating cycle of elevated temperatures to 200°C and subsequently immersed in water at 25°C for 24 hours, the material combination absorbs within its outer boundaries a mass of water less than or equal to 200 wt% relative to the dry mass of the material combination prior to immersion in the water.
123. A material combination as described in any of claims 84-122, wherein after being subjected to a standard heating cycle of elevated temperatures to 200°C and subsequently immersed in water at 25°C for 24 hours, the material combination absorbs within its outer boundaries a mass of water less than or equal to 75 wt% relative to the dry mass of the material combination prior to immersion in the water.
124. The material combination of any one of claims 84-123, wherein when the material combination is immersed in water at 25°C for 24 hours, the material combination absorbs water within its outer boundary in a mass less than or equal to 20% of the dry mass of the material combination before immersion in water.
125. An article comprising the material combination of any one of claims 84-124 and a layer of a facing material in physical contact with the material combination.
126. The article of claim 125, wherein the facing material comprises a polymer, a metal, a ceramic, a fiber sheet, and / or carbon.
127. An article comprising the combination of materials of any one of claims 84-126 or the article of any one of claims 125-126, wherein the adhesive is in physical contact with at least a portion of the outer surface of the combination of materials.
128. An article as described in claim 127, wherein the adhesive comprises an epoxy resin, an acrylic resin, an acrylonitrile, a polyamide, a polyester, a polysulfide, polyvinyl acetate, polyethylene, polypropylene, polyvinyl pyrrolidone, polyvinyl alcohol, cyanoacrylate, a biopolymer, a polyurethane, a polyurea, an isocyanate, a silicone and / or a gelatin.
129. An article comprising: A first layer comprising the material combination of any one of claims 84-124 adhered to a second layer comprising melamine formaldehyde foam and a polymer aerogel at least partially within an outer boundary of the melamine formaldehyde foam.
130. The article of claim 129, wherein the second layer comprises the material combination of any one of claims 84-124.
131. A shoe, boot or insole comprising the material combination of any one of claims 84-124 or the article of any one of claims 125-130.
132. A flexible belt comprising the combination of materials of any one of claims 84-124 or the article of any one of claims 125-130.
133. A garment comprising the combination of materials of any one of claims 84-124 or the article of any one of claims 125-130.
134. The garment of claim 133, wherein the garment is a jacket, a hat, a glove, a shirt, a sock, or a pair of pants.
135. A diving suit comprising the material combination of any one of claims 84-124 or the article of any one of claims 125-130.
136. A battery comprising the material combination of any one of claims 84-124 or the article of any one of claims 125-130.
137. A carbonized derivative of the material combination of any one of claims 84-124.
138. A method comprising: establishing contact between the melamine formaldehyde foam and a liquid comprising a polymer aerogel precursor such that the polymer aerogel precursor penetrates an outer boundary of the melamine formaldehyde foam; as well as A polymer aerogel is formed from the polymer aerogel precursor such that the polymer aerogel exists within an outer boundary of the melamine formaldehyde foam.
139. The method of claim 138, wherein the melamine formaldehyde foam is contacted with a hydrophobe before the melamine formaldehyde foam is contacted with the polymer aerogel precursor.
140. The method of any one of claims 138-139, wherein the melamine formaldehyde foam is contacted with a hydrophobe after the melamine formaldehyde foam is contacted with the polymer aerogel precursor.
141. The method of any one of claims 138-140, wherein the combination of the polymer aerogel and the melamine formaldehyde foam is contacted with a hydrophobe.
142. The method of any one of claims 138-141, wherein the combination of the polymer aerogel and the melamine formaldehyde foam is contacted with a hydrophobe.
143. The method of any one of claims 138-142, wherein the combination of the polymer aerogel and the melamine formaldehyde foam is contacted with a vapor comprising a hydrophobe such that exposed reactive sites on the melamine formaldehyde foam react with the hydrophobe.
144. The method of any one of claims 138-143, wherein the hydrophobe comprises hexamethyldisilazane, hexamethylenedisiloxane, dioctylamine, didodecylamine, hexylamine, dihexylamine, isocyanate, aldehyde, amine, alkylchlorosilane and / or a silane of formula HN(R 1 )(R 2 ) wherein: R 1 are each independently a first organic moiety; and R 2 Each independently is H or a second organic moiety; The premise is: The first and second organic moieties are both not H; and HR determined at about 25°C and about 1 atm 1 and / or HR 2 The log P is not less than 1.
145. The method of any one of claims 138-144, further comprising forming the melamine formaldehyde foam from a precursor foam.
146. The method of claim 145, further comprising thermally or mechanically treating the precursor foam to increase the density of the melamine formaldehyde foam relative to the precursor foam prior to contacting the polymer aerogel precursor.
147. The method of any one of claims 138 to 146, wherein before establishing contact between the melamine formaldehyde foam and the liquid comprising a polymer aerogel precursor, the melamine formaldehyde foam is heated to a temperature greater than or equal to 200°C and less than or equal to 300°C and compressed to a thickness greater than or equal to 15% and less than or equal to 90% of the thickness of the melamine formaldehyde foam just before compression.
148. The method of any one of claims 138-147, wherein establishing contact between the melamine formaldehyde foam and the liquid comprising a polymer aerogel precursor comprises spraying the liquid comprising a polymer aerogel precursor onto the melamine formaldehyde foam.
149. The method of any one of claims 138-148, wherein establishing contact between the melamine formaldehyde foam and the liquid comprising a polymer aerogel precursor comprises pouring the liquid comprising a polymer aerogel precursor onto the melamine formaldehyde foam.
150. The method of any one of claims 138-149, wherein establishing contact between the melamine formaldehyde foam and the liquid containing polymer aerogel precursors comprises injecting the liquid containing polymer aerogel precursors into the melamine formaldehyde foam.
151. The method of any one of claims 138-150, wherein establishing contact between the melamine formaldehyde foam and the liquid comprising a polymer aerogel precursor comprises immersing the melamine formaldehyde foam in the liquid comprising a polymer aerogel precursor.
152. The method of any one of claims 138-151, wherein establishing contact between the melamine formaldehyde foam and the liquid containing a polymer aerogel precursor comprises moving the melamine formaldehyde foam through a bath of the liquid containing a polymer aerogel precursor such that the liquid containing a polymer aerogel precursor is absorbed by the melamine formaldehyde foam.
153. A method as claimed in claim 152, wherein the melamine formaldehyde foam is moved through the bath of the liquid containing the polymer aerogel precursor and compressed while in contact with the liquid containing the polymer aerogel precursor, so that the liquid containing the polymer aerogel precursor is absorbed into the pores of the melamine formaldehyde foam when the foam is depressurized.
154. The method of any one of claims 138-153, wherein the polymer aerogel precursor forms a polymer gel on or within the pores of the melamine formaldehyde foam, thereby forming a gel / foam material combination.
155. The method of any one of claims 138-154, wherein the liquid in the pores of the melamine formaldehyde foam is exchanged for a transfer solvent.
156. The method of claim 155, wherein the liquid in the pores of the melamine formaldehyde foam is exchanged for the transfer solvent in a continuous manner.
157. The method of any one of claims 155-156, wherein the transfer solvent comprises an alcohol, a ketone, a nitrile, an acetate, a pyrrolidone, an alkane, a pentanone, an alkane, dimethyl sulfoxide, and / or liquid carbon dioxide.
158. The method of any one of claims 155-157, wherein after the exchanging, the transfer solvent is frozen.
159. The method of any one of claims 155-158, wherein the transfer solvent and / or liquid in the pores of the gel / foam material combination is removed by supercritical extraction.
160. The method of any one of claims 138-159, wherein forming the polymer aerogel comprises forming a gel comprising the liquid and the polymer aerogel precursor, subsequently at least partially replacing the liquid in the gel with carbon dioxide, and subsequently removing the carbon dioxide to form the polymer aerogel.
161. The method of any one of claims 138-159, wherein forming the polymer aerogel comprises forming a gel comprising the liquid and the polymer aerogel precursor, replacing at least a portion of the liquid with a transfer solvent, and removing the transfer solvent by evaporation and / or boiling.
162. The method of any one of claims 138-159, wherein forming the polymer aerogel comprises forming a gel comprising the liquid and the polymer aerogel precursor, replacing at least a portion of the liquid with a transfer solvent, and removing the transfer solvent by vacuum freeze drying.
163. The method of any one of claims 138-159, wherein forming the polymer aerogel comprises forming a gel comprising the liquid and the polymer aerogel precursor, replacing at least a portion of the liquid with a transfer solvent, freeze drying the transfer solvent, and removing the transfer solvent at an absolute pressure equal to or greater than 1 atmosphere.
164. The method of any one of claims 138-163, wherein forming the polymer aerogel comprises removing the liquid from the melamine formaldehyde foam in a continuous manner.
Citation Information
Patent Citations
Three-dimensional porous polyurea networks and methods of manufacture
US10301445B2
Porous polyurethane networks and methods of preparation
US8927079B2
Porous nanostructured polyimide networks and methods of manufacture
US9745198B2
Systems and methods for producing aerogel material
WO2016127084A1
Aerogel materials and methods for their production
WO2016161123A1
Cited By
Self-healing type fire physical evidence logistics transportation buffer material and preparation method thereof
CN119708755A
A self-healing buffer material for the physical evidence of fire during logistics transportation and its preparation method
CN119708755B